Complexation with β-cyclodextrin derivatives enhanced the bioavailability of quercetin through improving solubility and inhibiting recrystallization - Qiao Chen; Hai-Xia Xu; Ji-Guang Chen; Lin Dai; Bao-Geng Fu; Qing-Feng Zhang (Journal of Food Engineering, 2027)

Delayed flooding after green manure incorporation enhances microbial necromass formation and stabilization in paddy soils - Zhengbo Ma; Danna Chang; Qingxu Ma; Haoran Fu; Jinxin Sun; Ting Liang; Cheng Cai; Sheng Tang; Guopeng Zhou; Davey L. Jones; Wolfgang Wanek; Qing Zhang; et al. (Soil Biology and Biochemistry, 2026)

Tirzepatide improves neutrophilic inflammation in obese asthmatic mice by downregulating Th17 cell differentiation - Lu Sun; Su-Yan Yao; Zhong-Fu Zuo; Sheng-Xue Yu; Hong-Dan Yu; Qing-Lin Sun; Han-Song Zheng; Yang Hou; Si-Jing Lu; Tie-Feng Yao (Molecular Biology Reports, 2026)

Prediction of chemoresistance in ovarian cancer based on deep learning with pathological images - Leyan Niu; Xiang Li; Zhiquan Mao; Fen Fu; Mingjie Wang; Hengbin Zhang; Le Chen; Qing Zhang; Xiaoli Tang; Weiming Lou (Functional & Integrative Genomics, 2026)

Seasonal grazing drives complementary adaptive strategies in grasses and forbs via niche divergence: Evidence from a long-term experiment in alpine meadows - Peng Jiang; Hao-Zhe Zheng; Qing-Shan Fan; Lu-Ji Ade; Shu-Lin Wang; Fu-Jiang Hou (Agriculture, Ecosystems & Environment, 2026)

Mechanism and parametric analysis on cooperative seismic mitigation of base-isolated structures equipped with negative stiffness amplifying damper based on a distributed parameter model - Qing Lyu; Xianlei Li; Bo Fu; Liangkun Liu; Zhaoyang Zhang (Soil Dynamics and Earthquake Engineering, 2026)

F-doped FeNC catalyst with axial ligand engineering: breaking the strong adsorption barrier for efficient non-radical peroxymonosulfate (PMS) activation and antibiotic removal - Yuxuan Lv; Xiaoyu Shao; Yang Tao; Liang Ouyang; Zekang Li; Qing Fu; Sanying Hou (Environmental Research, 2026)

Microwave synchronous excitation of strong electric field and electrodeless ultraviolet radiation for effective air disinfection - Ying-Xiang Fu; Yu Chen; Yu-Qing Huang; Zhi-Bo Zhang; Yue-Hao Ma; Hua-Cheng Zhu; Ye Du (ENGINEERING Environment, 2026)

Ebselen inhibits PRRSV replication by activating the TRIM16/SQSTM1–KEAP1–NRF2-mediated oxidative stress response pathway - Xinrong Wang; Yan Guo; Linjie Hou; Lingqiao You; Qing Zhang; Junhai Zhu; Longxiang Zhang; Nan Yan; Jun Lu; Lizhi Fu; Yue Wang (Veterinary Microbiology, 2026)

Genomic insights into nematode microbiomes reveal novel endosymbionts Rickettsiella - Fan Guo; Weiqi Fu; Olivera Topalović; Qi Zhang; Kemei Li; Hongmei Li; Xue Qing (Molecular Phylogenetics and Evolution, 2026)

Mechanical response of layered heterogeneous hydrate-bearing sediments to depressurization - Hua Du; Huie Chen; Fansheng Kong; Qing Wang; Yonggui Luo; Xiang Gao; Jinzhong Zhu; Lanting Fu; Rui Fu (International Journal of Rock Mechanics and Mining Sciences, 2026)

Transient geomorphic processes revealed by luminescence sensitivity of Yellow River terrace sediments - Ya Liu; Zheng-Hao Gu; Jia-Fu Zhang; Xue Rui; Yu-Jie Guo; Song-Xi Du; Yu-He Shen; Qing-Hao Ma (Geomorphology, 2026)

Window-specific effects of ultraviolet radiation and air pollution on ovarian reserve in infertile women: A retrospective cohort study - Qi Tang; Cong Fu; Hongyu Du; Qing Liu; Kui Yang; Zhuoni Xiao; Yanqing Xu (Environmental Pollution, 2026)

Ambient-air fabrication of high-performance thick-film organic solar cells enabled by solid additive engineering - Kun Li; Cunbin An; Yuan Yao; Jianbin Zhong; Bin Hu; Wei Zhang; Yishi Wu; Bowei Xu; Dianyi Liu; Guanghao Lu; Qing Liao; Xiaozhang Zhu; et al. (Chemical Engineering Journal, 2026)

A GPC3 antigenic peptide based nanovaccine to potentiate immunotherapy of hepatocellular carcinoma - Yang Qin; Longtianyang Lei; Chaoyi Liu; Chonghao Liao; Zhenghao Tao; Yao Cheng; Qing Gao; Runshu Fu; Zhuoyi Rong; Haitao Zhang; Hua Wei; Cui-Yun Yu (Chemical Engineering Journal, 2026)

Spatial dominance over temporal dynamics in urban soil bacterial communities and its implications for forensic geolocation - Qing Zhang; Chang Zhao; Xiao Fu; Jiasheng Wu; Hengjun Zhang; Haiyan Chu; Meiqing Yuan; Teng Yang (Soil Ecology Letters, 2026)

Earthquake-induced displacement model for earth slopes incorporating soil softening effect based on material point method - Yu-Han Zhao; Qiang Wu; Zhi-Yong Fu; Dian-Qing Li; Wenqi Du (Soil Dynamics and Earthquake Engineering, 2026)

Molecular-level insights into the disinfection by-product precursor removal by biological activated carbon process using FT-ICR MS - Guojing Shi; Quan Gao; Qing-Long Fu; Huang Huang; Xin Yang (Journal of Environmental Sciences, 2026)

Study on the identification, generation mechanism and coloring effect of 5,7-dihydroxycoumarin formed from the autoxidation of EGCG - Zi-Xin Zhao; Zhuo-Shun Dai; Jie-Qiong Wang; Jun-Feng Yin; Liang Zhang; Yong-Quan Xu; Yan-Qing Fu (Food Chemistry, 2026)

Seismic response and critical acceleration analysis of anti-dip stratified rock slopes: Insights from shaking table tests and numerical simulations - Yang Wang; Qing Lv; Wenxi Fu; Leilei Jin; Fei Ye; Shuai Zhang (Engineering Geology, 2026)

Enhanced power factor n-type carbon nanotube thermoelectric films enabled by liquid-crystal ordering for self-powered encrypted signal sensing - Qing-Yi Ma; Wen-Qian Leng; Zi-Yan Li; Fei-Peng Du; Ping Fu; Chak-Yin Tang; Chi-Pong Tsui; Wing-Cheung Law; Yun-Fei Zhang (Chemical Engineering Journal, 2026)

A green and efficient biomass one-pot method for spent lithium-ion battery recycling - Quan Chen; Xuejiao Zhang; Qing Zhao; Zhi Sun; Xiaoli Zhao; Rongbing Fu; Fengchang Wu (Chemical Engineering Journal, 2026)

A GNSS multipath error mitigation method based on least-squares collocation with different covariance functions - Houxiang Zhou; Xiaoya Wang; YanLing Chen; Liqian Zhao; Hongmei Zhang; Qing Fu; Zhixiang Yang (Advances in Space Research, 2026)

IGF2BP3 promotes early angiogenesis in pulmonary fibrosis by stabilizing HIF-1α - Chunyan Yang; Bin Chen; Haiqing Jing; Qing Liu; Yanqiong Wang; Yanrui Wu; Jiayi Song; Yi Fu (Molecular and Cellular Biochemistry, 2026)

Study on calculation methods for predicting the ultimate uplift bearing capacity of pressure-cast-in-situ pile with spray-expanded frustum (PPSF) - Sheng-shi Qiao; Qian-qing Zhang; Jun-wei Liu; Yuan-chen Huang; Tao Fu (Transportation Geotechnics, 2026)

Early and prolonged oral edaravone for neuroprotection in acute ischemic stroke: the ERASE-STROKE randomized controlled phase 3 trial - Yang Xiang; Wang-Sheng Jin; Xin-Chen Zhu; Yan Song; Xiao Chen; Qing-Hua Wang; Hao-Lun Sun; Yang Zhao; Xiao-Rong Yu; Tao Feng; Ai-Hong Guo; Hong-Guo Dai; et al. (Science Bulletin, 2026)

Corrigendum to ‘The earliest sponge spicule tufts from the Cambrian Lower Yanjiahe Formation, Three Gorges area, South China’ [Palaeoworld 34 (2025) 200995] - Lei Zhang; Ying Wu; Fan Zhai; Chen-Zhang Duan; Shan-Shan Fu; Shan Chang; Yan Ye; Can Chen; Xia Wang; Xian-Guo Lang; Qing-Lai Feng; Marie-Béatrice Forel (Palaeoworld, 2026)

Development of an innovative in-situ solid-state fermentation system based on endophytic fungi and agrifood by-products pigeon pea roots to enhance genistein production - Jin-Xian Fu; Mo-Nan Wen; Jiao Jiao; Qing-Yan Gai; Yu-Jie Fu; Dan Qu (Innovative Food Science & Emerging Technologies, 2026)

A coupled elastoplastic damage subloading surface model for rock-like geomaterials subjected to triaxial cyclic compression - Jun Wu; Wei Wang; Ya-jun Cao; Shi-fan Liu; Wan-qing Shen; Jian-fu Shao (Computers and Geotechnics, 2026)

Engineering Brønsted acidity of the H–ZSM–5 framework for efficient oxidative carbonylation of methane to acetic acid - Yujing Fu; Qing-Wen Song; Ping Liu (Chemical Engineering Journal, 2026)

Effects of slope aspect on the evolution of frozen soil layers in cold regions: A case study of the Hada Mountain water conveyance canal in western Jilin Province - Jiaqi Liu; Boxin Wang; Qing Wang; Huie Chen; Tianlue Wang; Lanting Fu; Xiaorui Huang; Xinglin Peng; He Zheng; Jiaxin Lu (Cold Regions Science and Technology, 2026)

Deletion of electron-bifurcating [FeFe]-hydrogenase enhances H2-driven CO2 fixation and ethanol production in Clostridium ljungdahlii - Zhi-Qiong Wen; Yu-Zhen Li; Hai-Jia Su; Jun-Zhe Zhang; Zi-Yong Liu; Shu-Ning Wang; Hui Wang; Fu-Li Li; Xiao-Qing Ma (Bioresource Technology, 2026)

Seismic displacement and failure characteristics of rock slopes considering dynamic degradation of rock structural planes under pulse-like ground motions - Shuang Xiong; Dian-Qing Li; Zhiyong Fu; Wenqi Du (Bulletin of Engineering Geology and the Environment, 2026)

Chemical composition of the endogenous fungus Fusarium sp. L-3 derived from Chinese Qinan agarwood - Ming-Li Han; Qing-Yun Ma; Li Yang; Qing-Yi Xie; Jiao-Cen Guo; Hao-Fu Dai; Na Xiao; You-Xing Zhao (Natural Product Research, 2026)

Regional-scale prediction and assessment of soil organic matter content in the Yuanmou Dry-Hot Valley, Southwest China, using satellite-derived phenological time series and deep learning - Dengdeng Ding; Jida Yang; Sihe Deng; Hongye Zhu; Zhengbo Ma; Chengxiu Fu; Junlang Deng; Dingyun Zhao; Zhen Long; Xiaoyan Wang; Peiwen Yang; Qibin Chen; et al. (Environmental Monitoring and Assessment, 2026)

Inhibitory effect of gut microbiota-fermented trisaccharide GuFGa (Glc-Fuc-Gal) on Campylobacter jejuni: insights from transcriptomic and metabolomic analyses - Xinmiao Ren; Shuang Li; Changyun Wang; Francesco Secundo; Ningyang Li; Mengshi Xiao; Min Yang; Rong Li; Qing Kong; Han Sun; Xiaodan Fu; Haijin Mou (Marine Life Science & Technology, 2026)

Novel eudesmanolides from the flowers of Pentanema britannicum (L.) D.Gut.Larr with antidepressant activities - Yu-Qing Xie; Xin-Yue Zhang; Jun-Hui Zhang; Ping He; Sheng-He Yang; Yan Fu; Zhi-Yu Ni; Jian Su; Yu-Cheng Gu; Yi-Bing Wu (Natural Product Research, 2026)

Ethylene signaling, pathogenesis-related proteins (PRs) and SlCBF1 collectively regulate Botrytis cinerea resistance in postharvest tomato fruit under low temperature conditions - Pan Shu; Zhiyuan Wang; Bingqing Qian; Zhiyin Yu; Qinlu Zheng; Xin Yao; Hongye Fu; Yuan Qing; Xiaojuan Yin; Pan Zou; Jing Li; Lin Shen (Postharvest Biology and Technology, 2026)

The role of oxygen vacancies and metallic Ru in regulating oxide pathway mechanism for acidic water electrolysis - Dinghua Zhou; Yutian Ding; Tao Song; Jiayi Wu; Zengyu Su; Zhiyong Fang; Muhammad Bilal Hussain; Peili Zhang; Xian-Zhu Fu; Shao-Qing Liu; Shuwen Wu; Jing-Li Luo (Chemical Engineering Journal, 2026)

Influence of LED lighting on the cell growth, accumulation of bioactive flavonoids and terpenoids, antioxidant response, and photoreceptor-mediated light signal transduction in Ginkgo biloba L. callus cultures - Qing-Yan Gai; Jiao Jiao; Yu-Jie Fu; Hong-Yan Zhao; Xiao-Qing Wang; Dan Qu (Plant Cell, Tissue and Organ Culture (PCTOC), 2026)

Gastrodin Ameliorates Blood Pressure by Targeting the PPAR-γ/NF-κB/NLRP3 Signaling Axis in the Hypothalamic Paraventricular Nucleus - Yu Yang; Xiao-Jing Yu; Li-Yan Fu; Jie Qi; Kai-Li Liu; Xiu-Yue Jia; Wei Cui; Qing Su; Ting Huang; Yan-Feng Liang; Hua Tian; Huan Liu; et al. (Cardiovascular Toxicology, 2026)

Effects of personality and body weight on foraging behavior and vigilance: a case study in a small rodent - Yu-Chuang Hui; Shu-Jing Gao; Xuan-Wen Li; Wei-Qi Chen; Yue-Yue Yang; Xue-Dong Bai; Qin Su; Fu-Shun Zhang; Li-Qing Wang; Ling-Ying Shuai (Behavioral Ecology and Sociobiology, 2026)

Seismic dynamic response and sensitivity analysis of high-speed railway catenary systems under multidirectional excitations and traveling wave effects - Jin Chen; Qing-Bing Wan; Hao-Lin Xin; Bo Fu; Deliang Ma (Bulletin of Earthquake Engineering, 2026)

Integrated NGS-MassARRAY Screening Reveals Hidden Wilson Disease Burden - Jia Tang; Hao Geng; Haihong Shi; Ting Yu; Jinping Qiao; Qingjiang Guo; Kun Wang; Jingjing Jiang; Qing Zhao; Na Nian; Yun Cheng; Shijing Wang; et al. (Phenomics, 2026)

Monoterpenoids from the roots of Paeonia lactiflora Pall. and their neuroprotective activity - Bo Fu; Yi-Qiang Zhang; Jin-Ling Zhang; Si-Yi Wang; Jia-Tong Wu; Juan Pan; Wei Guan; Zhi-Chao Hao; Qing-Shan Chen; Li-Li Zhang; Hai-Xue Kuang; Yan Liu (Natural Product Research, 2026)

Light-driven community assembly and functional performance of aeration-free filamentous algae–partial nitrification/anammox granule - Cui-Zhong Chen; Hui-Min Fu; Tong-Xu Li; Xiao-Yu Gao; Qing Hu; Peng Yan; Jin-Song Guo; Xiao-Wei Xu; You-Peng Chen (Water Research, 2026)

Identification of pennogenin synthases in Paris polyphylla reveals enzyme plasticity underlying paralog evolution - Shuyu Li; Jingjing Liao; Jingjing Zhang; Chunjin Fu; Haining Lyu; Yuxiang Huang; Zhangrui Tang; Xinwei Zhang; Yuyang Liu; Xin Chai; Jiale Xing; Xin Zhao; et al. (Molecular Plant, 2026)

Low-dose fluoride and lead co-exposure alters bone mineral density in youth: A nationally representative cross-sectional study - Chunxiang Li; Zeyuan Niu; Yuhui Du; Lihong Yang; Fan Wu; Xinxin Hu; Xiaohang Meng; Zichen Feng; Shu Niu; Qing Sun; Yan Wang; Xiaoli Fu; et al. (Journal of Trace Elements in Medicine and Biology, 2026)

Leverage-based nutrient governance for drinking water sources using hydro-ecological zoning and source apportionment in the Yangtze River Basin - Haizhen Hu; Qing Fu; Sheng Chang; Yinying Zhu; Asaad Y. Shamseldin; Fan Zhang; Guang Yang; Chun Ye; Yueting Fan; Enrui Wang (Journal of Environmental Chemical Engineering, 2026)

Waste to wealth: Ternary single-atom catalysts derived from spent lithium-ion batteries for solar-driven hydrogen production - Quan Chen; Xiaoli Zhao; Tianjiao Zhai; Xuejiao Zhang; Qing Zhao; Rongbing Fu; Fengchang Wu (Journal of Environmental Chemical Engineering, 2026)

Synergistic in situ growth and interfacial modification of ZIF-8@PDMS membranes for efficient DMC/methanol separation - Qing Zeng; Zhihui Zhou; Hongdan Wu; Wenming Fu; Xianyuan Fan; Guoyuan Lei; Junlin Peng (Journal of Environmental Chemical Engineering, 2026)

Multifaceted biocontrol mechanisms of Bacillus amyloliquefaciens F028 against Botrytis cinerea in postharvest tomato fruit - Fu-Lai Han; Jin-Xiu Zhao; Ming-Yi Wang; Meng-Fei Li; Zhe Zhang; Xiao-Hang Cui; Yu-Fei Li; Hao-Jie Jiang; Qing-Xue Jiao; Jie Yang; Xin Liu; Guang-Chao Liu (International Journal of Food Microbiology, 2026)

Resonant effects of seismicity on substance migration in rock fractures - Zhi-Jie Che; Jia-Qing Zhou; Li-Guo Guo; Fu-Shuo Gan; Hong-Bin Liu; Changdong Li; Yi-Feng Chen (International Journal of Rock Mechanics and Mining Sciences, 2026)

Multifunctional Cu2O@Ag probe for ultra-sensitive SERS detection and inhibition of Escherichia coli O157: H7 - Hao Jiang; Yu-Qing Wang; Huan Cheng; Shi-Ying Fu; Hongmei Li; Jia-Sheng Lin; Yue-Jiao Zhang; Jian-Feng Li (Food Chemistry, 2026)

Volatility-tuned encapsulation in V-type starch: Phase-dependent efficiency and release kinetics - Kunheng Lai; Peiying He; Paul Van der Meeren; Bin Zhang; Xiong Fu; Qing Gao; Qiang Huang (Food Hydrocolloids, 2026)

A novel strategy for cooked sheep liver preservation: Integrating high-barrier polymer packaging with Cistanche deserticola aqueous extract treatment - Jiahui Du; Jiushi Guo; Ganqi Yang; Boyu Wang; Jie Cao; Tungalag Dong; Terigen Bao; Shan Qing; Ying Fu; Xueyan Yun (Food Control, 2026)

From air to adipose: Investigating PM2.5-bound chlorinated paraffins and overweight/obesity in Chinese children and adolescents - Qi Yang; Hai-Xin Tu; Yu He; Ya-Qin Zhang; Muhammad Amjad; Jing-Fu Lai; Jing-Wen Huang; Yun-Ting Zhang; Wan-Ting He; Li-Xia Liang; Wen-Wen Bao; Yang Zhou; et al. (Environmental Research, 2026)

Quantifying scale effects in pile scour depth prediction for field applications via interpretable machine learning - Yang-Xin Zhou; Qing-Kai Song; Wen-Gang Qi; Li-Jing Yang; Xiao-Bing Lu; Fu-Ping Gao (Coastal Engineering, 2026)

Data driven analysis on changing patterns of reactive nitrogen deposition in East and Southeast Asia - Jiani Tan; Yan Zhang; Xuejun Liu; Yun Fat LAM; Mohd Talib Latif; Kasemsan Manomaiphiboon; Joshua S. Fu; Maggie Chel Gee Ooi; Ling Huang; Yangjun Wang; Hui Chen; Kun Zhang; et al. (Atmospheric Environment, 2026)

From Adaptation to Collapse: Immune Remodeling, Mitochondrial Dysfunction, and Cell Death Induced by Polystyrene Nanoplastics in Procambarus clarkii Hepatopancreas - Shengyan Pu; Han Mingming; Yi Juin Tay; Xiao Qing; Fu Hongmei; Wang Yiting; Li Zhenchao; Zhang Jingyou; Anisah Lee Binti Abdullah; Ji Liang (Marine Biotechnology, 2026)

An ultrasensitive electrochemical immunosensor for SLC2A3 detection enables prognostic prediction in acute ischemic stroke - Yu Ren; Qing Fu; Juncheng Huang; Chengying Du; Juanjuan An; Qin Yang; Du Cao (Analytica Chimica Acta, 2026)

Microsphazaphilones H–Y: new azaphilone pigments with HIV latency reversal activity from the marine-derived fungus Microsphaeropsis arundinis P1B - Qing-Ren Lu; Xian-Yuan Yang; Lei Li; Lei-Ming Wu; Lu-Xiang Wan; Yi-Fan Fu; Xian-An Chen; Xin-Xiang Xu; Tao Yuan; Xin Chen; Abrar Ahmed; Nirmal Malik; et al. (Marine Life Science & Technology, 2026)

Cuproptosis: a novel mechanism and 3PM-oriented therapeutic strategy for cancer - Ding Yang; Wei-Ting Hu; Miao Li; Fang-Qing Shen; Hao-Yu Wang; Jin-Ying Ye; Fu-Lu Ren; Yun Wang (EPMA Journal, 2026)

Two new compounds from the roots of Paeonia lactiflora Pall. and their anti-inflammatory effects - Bo Fu; Jin-Ling Zhang; Jia-Tong Wu; Si-Yi Wang; Yi-Qiang Zhang; Juan Pan; Wei Guan; Zhi-Chao Hao; Hai-Xue Kuang; Qing-shan Chen; Li-Li Zhang; Bing-You Yang; et al. (Natural Product Research, 2026)

Spatially compartmentalized dual-epitope engineering: A strategy for multilayered plant defense - Xiumei Luo; Ramesh Raju Vetukuri; Kerimaliev Janybek; Zheng Qing Fu; Maozhi Ren (Molecular Plant, 2026)

Metagenomic analysis of urban water systems uncovers the interplay between antibiotic resistance genes and microbial communities in response to PFAS contamination - Kunfeng Zhang; Sheng Chang; Yinying Zhu; Hongru Shang; Qing Fu; Xiang Tu; Yanling Yu; Yujie Feng (Journal of Hazardous Materials, 2026)

Lactiplantibacillus plantarum ZJ316 synergizes with tryptophan diet to modulate gut microbiota and metabolite profiles in mice - Qingqing Zhou; Yingying Zhou; Lu Li; Kening Fu; Shibo Liu; Ping Li; Qing Gu (Food Bioscience, 2026)

Zircon evidence for exogenous water delivery to the lunar interior - Yong Wang; Xiao-Ping Xia; Jian Xu; Yong-Sheng Liu; Christopher J. Spencer; Trevor Ireland; Ze-Xian Cui; Xiao-Jia Zeng; Jan C.M. De Hoog; Aaron J. Cavosie; Bin Fu; Qing Yang; et al. (Earth and Planetary Science Letters, 2026)

Effects of different biomass amendments on the biogeochemical processes of arsenic transformation during tailings soil leaching: Insights into dissolved organic matter and arsenic-functional genes - Jun Zeng; Hong Wang; Qing Hu; Na Liu; Bowen Hu; Renchuan Fu; Longzhen Ding (Chemical Engineering Journal, 2026)

Preparation of cancer cell membrane-coated Gambogic acid-loaded pH-sensitive liposomes to enhance targeted anti-hepatocellular carcinoma effect - Yi-Feng Zhang; Kun Chen; Yu-Qing Zhu; Lin Liu; Xiang-Tao Kong; Yan Dai; Xiu-Juan Fu; Ya-Ling Li; Ming-Hua Liu; Dan Zhang (Drug Delivery and Translational Research, 2026)

Synthesis of rhodamine modified carbon quantum dots and application of ratiometric fluorescence detection for Cu2+ and triple-mode detection for 2,4-dichlorophenoxyacetic acid - Qing Li; Yage Guan; Qian Wang; Daxiang Gui; Yingqiang Fu (Analytica Chimica Acta, 2026)

Habitat complexity and spatial navigation: linking habitat to cognitive strategy in cyprinid fishes - Wu-Xin Li; Qing-Yin Wei; Ling-Qing Zeng; Shi-Jian Fu (Behavioral Ecology and Sociobiology, 2026)

Wave Equation Based Joint Velocity and Q Tomography with Local Traveltime Measurements - Qing-qing Li; Xin Tang; Li-yun Fu (Applied Geophysics, 2026)

A Mathematical Model for Dynamic Characterization of Reservoir Parameters in Coalbed Methane Development - Xinlu Yan; Shuheng Tang; Xiaokang Fu; Lei Xu; Qing Yan; Zhongcheng Li; Guangjing Liu (Natural Resources Research, 2026)

Carbon emission reduction strategy in shipping industry: A stochastic evolutionary game analysis - Yufang Fu; Qing Chen; Bojun Gu; Peng Tian (Transportation Research Part D: Transport and Environment, 2026)

Eocene topography differentiation between the western and eastern North China Craton: Insights from multi-method chronometry in the northern Taihangshan Mountains - Li-Xia Feng; Ping-Ping Li; Zeng-Zhen Wang; Rong Ren; Lin Wu; Bo Zheng; Bo Liu; Jian-Qing Ji; Bao-Fu Han (Tectonophysics, 2026)

Two new aromatic meroterpenoids from the fruiting bodies of Ganoderma calidophilum - Wei Liu; Li Yang; Qing-Yun Ma; Qing-Yi Xie; Jiao-Cen Guo; Hao-Fu Dai; Yan Hua; You-Xing Zhao (Phytochemistry Letters, 2026)

A novel endophytic fungus Fusarium oxysporum G-07 exhibits antagonism against Rhizoctonia solani and promotes growth in Scutellaria baicalensis - Xiao-Qing Wang; Jiao Jiao; Qing-Yan Gai; Jin-Xian Fu; Yu-Jie Fu; Hong-Yan Zhao; Ying Liu (Pesticide Biochemistry and Physiology, 2026)

Development of a sporopollenin-hydrogel-Cu2O composite for dye removal: Addressing the dual challenges of agglomeration and ‌embedding of metal nanoparticles in hydrogel-based catalysts - Ying Liu; Jiao Jiao; Qing-Yan Gai; Yi-Bo Qiu; Hong-Yan Zhao; Xiao-Qing Wang; Yu-Jie Fu (Journal of Environmental Sciences, 2026)

A comprehensive review on wine authentication and traceability: Current issues, solutions and future perspectives - Hai-Qing Qiang; Hui-Wen Gu; Xiao-Li Yin; Zhan Meng; Wanjun Long; Haiyan Fu; Yuanbin She (Food Chemistry, 2026)

A novel gallic acid modification and high-temperature alkali activation mesoporous biochar enables ultrafast and high-capacity removal of short- and long-chain PFAS from water - Kunfeng Zhang; Sheng Chang; Yanling Yu; Hongru Shang; Xiang Tu; Qing Fu; Abdul Qadeer; Yujie Feng (Chemical Engineering Journal, 2026)

A Multi-omics Atlas of Gonadal Sex Differences and Characterization of the dmrt1 Gene in Gymnocypris Eckloni Herzenstein - Luo Lei; Yinhua Zhou; Qing Liu; Hejiao Li; Wuga Sha; Chaoyang Li; Suxing Fu; Yuting Duan; Rongrong Liao; Can Liu; Dapeng Gu; Linzhen Li; et al. (Marine Biotechnology, 2026)

Chemodiversity of Dissolved Organic Matter in Groundwater Elucidated by the Ultrahigh-Resolution Mass Spectrometry: A Case Study of the Jianghan Plain, China - Jingjing Sun; Ying Liang; Qing-Long Fu (Journal of Earth Science, 2026)

Quantitative scattering analysis of rough surface based on the boundary scattering matrix - Yang-pu Chen; Li-Yun Fu; Qing-qing Li; Hong-en Li; Qing-he Meng (Applied Geophysics, 2026)

Electroporation-mediated exogenous gene delivery methodology into germ cells of the scallop, Chlamys farreri - Xiaolin Guo; Fang Liu; Yue Chen; Shukun Dai; Qing Wang; Siyu Lin; Yifan Fu; Zhifeng Zhang; Zhenkui Qin (Aquaculture, 2026)

Assessing road network resilience to extreme rainstorms: A percolation and hydrodynamic approach - Fei Ma; Rong Fu; Wei Ren; Qing-Chang Lu; Qing Liu; Zhijie Yang; Zhong Ma (Transportation Research Part D: Transport and Environment, 2026)

Balancing defense and growth: antagonist of systemin receptor - Qibin Wu; Wanying Zhao; Zheng Qing Fu; Youxiong Que (Trends in Plant Science, 2026)

Deployment of rooftop photovoltaic systems at the urban scale based on multi-objective optimization from the life cycle perspective - Xinrui Fu; Qing Zhong; Sophia Shuang Chen; Xiaoshan Yang; Jiajia Geng (Sustainable Cities and Society, 2026)

Soil science research in Research Center for Eco-Environmental Sciences: Review and outlook - Baodong Chen; Zhipeng Hao; Lei Luo; Nan Wu; Wenju Liu; Dong Zhu; Yuan Ge; Weiping Chen; Wentao Jiao; Xin Zhang; Siyi Liu; Jupei Shen; et al. (Journal of Environmental Sciences, 2026)

Advancements in metal-organic frameworks for alkaline oxygen evolution reaction: mechanistic insights, catalyst stability and applications - Ruo-Jin Liu; Xue-Ying Yang; Zheng-Yi Wu; Na Xu; Fu-Li Wang; Ren-Qing Lv; Guanqun Han; Bin Dong; Yong-Ming Chai (Fuel, 2026)

Fe(Ⅱ)-crosslinked whey protein fibril / iota-carrageenan complex gel for pH-responsive iron controlled release - Xuelian Yin; Qing Wang; Teng Li; Yuying Fu; Yun Zhai (Food Hydrocolloids, 2026)

Prolonged low pH reprograms carbon and nitrogen metabolism and micronutrient use in Symbiodinium kawagutii and reveals indicators for reef water quality management - Fu-Fang Wen; Qing-Ling Ma; Hao-Ran Guo; Yan Huang; Da-Wei Li; Wei-Dong Yang; Hong-Ye Li; Li-Gong Zou (Environmental Research, 2026)

Green upcycling of tigogenin from sisal waste: Chemoenzymatic cascade synthesis of progesterone derivatives as an alternative to traditional steroid production processes - Lu Song; Zhi-Kun Luo; Fu-Cheng He; Lan-Ya Huang; Liang-Bin Xiong; Yong-Jun Liu; Dong-Zhi Wei; Feng-Qing Wang (Chemical Engineering Journal, 2026)

The interplay between antihypertensive medication and lifestyle with cardiovascular outcomes in patients with hypertension: the PURE-China study - Biyan Wang; Zhiguang Liu; Tong Bu; Sumathy Rangarajan; Qiuyan Ma; Xiaocong Li; Qi Qiu; Yang Lin; Lap Ah Tse; Bo Hu; Salim Yusuf; Qiujing Cai; et al. (EPMA Journal, 2026)

Antifouling compounds from marine fungus Aspergillus iizukae GXIMD 00548 - Chun-Qing Fu; Meng-Fan Qi; Chun-Xiao Chen; Hua-Qing Huang; Xiao-Wei Luo; Cheng-Hai Gao; Yong-Hong Liu; Xin-Ya Xu (Biofouling, 2026)

Akkermansia muciniphila enhances the antitumour efficacy of αPD-1 therapy in gastric cancer by remodelling the tumour immune microenvironment - Ziyi Yang; Lanfan Liang; Xin Li; Xizhen Peng; Xinyi Qian; Zehua Huang; Xi Wang; Qing Hu; Xiangsheng Fu (Toxicology and Applied Pharmacology, 2026)

Two new compounds isolated from a sponge-derived fungus Diaporthe sp. ZYX-Z-582 - Jia-Le Chang; Qing-Yun Ma; Li Yang; Qing-Yi Xie; Hai-Tao Li; Jiao-Cen Guo; Hao-Fu Dai; Sha-Sha Liu; You-Xing Zhao (Phytochemistry Letters, 2026)

MsTIFY10a gene from alfalfa negatively regulates drought and salt tolerance in transgenic tobacco - Qi Chen; Yan Zhang; Ying Tian; Jing Xu; Qing-Wen Fu; Zhen-Yi Li; Feng-Ling Shi; Cui-Ping Gao; Zhi-Qiang Zhang (Journal of Plant Physiology, 2026)

Unique ecological functions of viral communities potentially influence microbial adaptability in deep-sea ferromanganese nodule deposits - Yu-Kang Li; Ge-Yi Fu; Zhen Rong; Jun-Qing Chen; Zhi-Hao Ding; Zu-Xin Zhang; Hua-Hua Jian; Wen-Sheng Shu; Yue-Hong Wu; Xue-Wei Xu (Journal of Hazardous Materials, 2026)

Grain-size controls on quartz OSL sensitivity in fluvial systems: insights from transport mechanisms in the upper Yellow River - Ya Liu; Song-Xi Du; Jia-Fu Zhang; Xue Rui; Yu-He Shen; Jia-Jing Wang; Qing-Hao Ma; Zheng-Hao Gu (Geomorphology, 2026)

Structural characterization and prebiotic activity of oligosaccharides derived from sesame meal produced by different oil extraction methods - Hui-Fang Duan; Xiao-Rong Chen; Ran Zhang; Yuan-Qing Luo; Chang-Yong Lu; Ke-Qing Liu; Rui-Fu Cui; Run-Yang Zhang; Hua-Min Liu (Food Research International, 2026)

Semi-dry encapsulation of D-borneol in V-type starch for effective stabilization and sustainable release - Peiying He; Bin Zhang; Xiong Fu; Rungtiwa Wongsagonsup; Namfone Lumdubwong; Qing Gao; Qiang Huang (Food Hydrocolloids, 2026)

Engineering of ethylene glycol (EG)-trophic Escherichia coli enables fast growth on EG for closed-loop PET biodegradation - Jia-Yu Chen; Sheng-Qi Gao; Qing-Song Huang; Xiao-Min Zhao; Qi-Sheng Fu; Kang-Qi Hu; Yan Huang; Jing Wu; Zheng-Fei Yan (Bioresource Technology, 2026)

Phytochemicals and health-promoting evaluations of Ophiorrhiza puffii , a chinese endemic plant - Qing Bu; Qi-Bin Yang; Zeng-Yue Ge; Ze-Xiong Shi; Lin-Fu Liang (Natural Product Research, 2026)

The role and therapeutic potential of purinergic signaling pathway in metabolic syndrome-related atherosclerosis - Xiang Li; Chengxin Gong; Chengxiao Fu; Qing Xia; Yue Zhang; Yue Du; Yuting Sun; Hong Xu (Purinergic Signalling, 2026)

Genome-wide identification of petunia C2H2 zinc finger family genes and their potential roles in floral volatile benzenoids/phenylpropanoids metabolism - Jiahong Chen; Xiaomeng Liu; Lingli Jiang; Hongsheng Qing; Jieyu Qian; Zixi Li; Chao Zhang; Jianxin Fu (Planta, 2026)

Lanostane triterpenoids from the fruiting bodies of Ganoderma multipileum and their anti-inflammatory activities - Mei-Juan Li; Qing-Yun Ma; Li Yang; Qing-Yi Xie; Jiao-Cen Guo; Hao-Fu Dai; Yan Hua; You-Xing Zhao (Natural Product Research, 2026)

Two new compounds isolated from an endophytic fungus Eutypella sp. XLE005 derived from Conus leopardus - Xin-Ming Li; Li Yang; Qing-Yun Ma; Qing-Yi Xie; Jiao-Cen Guo; Hao-Fu Dai; Du-Qiang Luo; You-Xing Zhao (Natural Product Research, 2026)

Cochliomycin H, a new 12-membered resorcylic acid lactone from sponge-derived fungus Curvularia sp. ZYX-Z-4 - Jiu-Jiu Zhou; Li Yang; Qing-Yun Ma; Qing-Yi Xie; Hao-Fu Dai; You-Hua Liu; Zhao You-Xing (Natural Product Research, 2026)

Persteroid, a new steroid from the marine-derived fungus Penicillium sp. ZYX-Z-143 - Lu-Ting Dai; Li Yang; Zi-Peng Wang; Jiao-Cen Guo; Qing-Yun Ma; Qing-Yi Xie; Hao-Fu Dai; Zhi-Fang Yu; You-Xing Zhao (Natural Product Research, 2026)

Crisis resolution pathways enhancement for building carbon emission based on dynamic QCA: Evidence from China - Jinmei Wang; Qing Yang; Ling He; Xingxing Liu; Lingmei Fu; Yandi Zheng (Sustainable Cities and Society, 2026)

Increased microbial extracellular polymeric substances as a key factor in deep soil organic carbon accumulation - Mengxi Feng; Ming Zhang; Peng Cai; Yichao Wu; Qingling Fu; Xin Zhang; Fei Miao; Wen Xing; Shuiqing Chen; Ke-Qing Xiao; Yong-Guan Zhu (Soil Biology and Biochemistry, 2026)

Corrigendum to “Chlorpyrifos induces placental oxidative stress and barrier dysfunction by mediating mitochondrial apoptosis via ERK/MAPK signaling pathway: In vitro and in vivo studies” [Sci. Total Environ. 903 (2023), 166449] - Jun Bai; Siwei Deng; Huiyang Fu; Qing Yang; Fazheng Ren; Shenming Zeng; Zhaohui Chen; Ying Yang; Zhenlong Wu (Science of The Total Environment, 2026)

Discovery, herbicidal activity evaluation, and mechanism of action of Heteroaryl chalcones as novel HPPD inhibitors - Li-xia Zhao; Dmitry B. Rubinov; Pan-xiu Zhang; Veronica G. Zinovich; Wen-qing Yu; Tatyana S. Khlebnicova; Fei Ye; Ying Fu; Fedor A. Lakhvich (Pesticide Biochemistry and Physiology, 2026)

Spatial distribution, source, and ecological risk of organochlorine pesticides (OCPs) in the Yellow and Bohai Seas - Long-Kun Sun; Jie Fu; Ming-Liang Zhao; Wen-Qing Wang; Zhen He; Gui-Peng Yang (Marine Environmental Research, 2026)

Degradation of organic refractory contaminants by phosphate buffer activated peroxymonosulfate: The overlooked roles of oxygen reactive species - Qing Liu; Siying Long; Xiaodi Duan; Qiqi Zhu; Qing Fu; Wei Wang; Jiarui Shi; Yaqi Wang; Chun Cai (Journal of Cleaner Production, 2026)

STIM1 N-linked glycosylation promotes arsenic-induced malignant phenotype by activating SOCE in bladder epithelial cells - Pinya Liu; Lei Zhang; Qing Zhou; Zhushan Fu; Shuhua Xi (Chemico-Biological Interactions, 2026)

Physics-based unified formulation for predicting clear-water equilibrium scour depth and scour threshold velocity around piles - Wen-Gang Qi; Biao Li; Shun-Yi Wang; Yong Wan; Pei-Qing Zhao; Fu-Ping Gao (Coastal Engineering, 2026)

Pathogenic and beneficial microbial communities determine the shelf life of stored 'Fengtangli' plums - Yu-Ru Wang; Tomislav Cernava; Shi-Xian Zeng; Hong Chen; Feng-Quan Liu; Zheng-Qing Fu; Tao Zhou; Yong Wang; Jia Liu (Postharvest Biology and Technology, 2025)

The earliest sponge spicule tufts from the Cambrian Lower Yanjiahe Formation, Three Gorges area, South China - Lei Zhang; Ying Wu; Fan Zhai; Chen-Zhang Duan; Shan-Shan Fu; Shan Chang; Yan Ye; Can Chen; Xia Wang; Xian-Guo Lang; Qing-Lai Feng; Marie-Béatrice Forel (Palaeoworld, 2025)

Rainfall process-related dissolved organic carbon wet deposition at the southern foot of Qinling Mountain: Implications for atmospheric carbon budget at the boundary area between north and south China - Jie Zeng; Guilin Han; Qixin Wu; Lihong Fu; Qing Ma; Jie Zhang; Xinyi He; Xin Ge (Journal of Hydrology, 2025)

Global inertial permeability for non-Darcian flow in porous media with different shape configurations - Fu-Shuo Gan; Jia-Qing Zhou; Liangqing Wang; Changdong Li; Xin-Yu Jiang; Yinbin Zhu (Journal of Hydrology, 2025)

Presence of a queen (Apis mellifera) reduces the sensitivity of worker bees to environmental risks - De Fang Niu; Qiu Lan Zheng; Bin Yuan; Xiao Ling Su; Cui Ping Zhang; Yuan Yuan Lu; Ping Liu; Fu Liang Hu; Huo Qing Zheng (Journal of Asia-Pacific Entomology, 2025)

Machine learning-enhanced meta-analysis unravels the global patterns of microplastic-heavy metal co-toxicity in terrestrial ecosystems - Hai-han Jiang; Tian-Hao Che; Qing Su; Bin Jin; Yan Lu; Han-Xi Zhou; Min-Jie Fu; Jing-Ya Zhou (Environmental Pollution, 2025)

Intrinsic kinetics study of microwave catalytic pyrolysis of cellulosic biomass using a novel microwave thermogravimetric analyzer - Qing An; Leon Fu; Xiaotao Bi (Chemical Engineering Journal, 2025)

Point-of-care testing of neuromyelitis optica spectrum disorder using a sonochemically enhanced bifunctional CdTe-ZIF-8 nanohybrids-labelled lateral flow immunoassay - Qing Fu; Manxia Wang; Jia Shu; Guangjun Xiao; Zhujun Ai; Xin Gao; Huan Cai; Yan Zhao; Xuhuai Fu; Zhizhong Li; Mengjie Zhang; Jinzhou Feng; et al. (Chemical Engineering Journal, 2025)

Characterization of a novel biosurfactant from Alcanivorax dieselolei and its mechanism for enhanced oil recovery in low-permeability reservoirs - Shuyuan Deng; Bo Wang; Ruixue Qu; Yuxiao Han; Cenqian Zhang; Chenyue Wang; Jian Fu; Shanshan Sun; Hao Dong; Gongze Cao; Qing You; Yuehui She; et al. (Chemical Engineering Journal, 2025)

Strain-engineered selenium vacancies in MoSe2 cocatalysts to redirect photocarrier trapping for efficient hydrogen evolution - Siyi Zhang; Ni Hu; Zhenfei Fu; Shilong Suo; Qing Han; Ziwu Han; Ziyue Zhang; Ruiling Zhang; Bing Jin; Zhenhua Zhang; Zhihong Lu; Pengfei Fang (Chemical Engineering Journal, 2025)

Homogeneous MgF2-engineered Na surface architecture enabling uniform ion deposition in ultra-stable sodium metal batteries - Xueming Su; Junjie Fu; Lin Luo; Xiaoquan Yang; Yue Li; Weijiang Hu; Qing Li; Qingye Li; Chencheng Sun; Jun Yang; Hongwei Gu (Chemical Engineering Journal, 2025)

Enhanced piezoelectric demulsification for high-efficiency separation of water-in-oil (W/O) emulsions based on biomimetic PVDF/liquid metal nanofiber membranes - Wen-Qiang Qiu; Jia-Qi Luo; Qing-Ke Luo; Yan-Ping Zhao; Zhi-Yu Xue; Jing-Song Tang; Hai-Feng Lu; Yi Zhang; Da-Wei Fu (Chemical Engineering Journal, 2025)

Selective Adsorption of Cyanide From Highly Concentrated Sulphate and Thiocyanate Wastewater - Xiaoge Wang; Binchuan Li; Daxue Fu; Yongfeng Chang; Shuang Cui; Kuiren Liu; Xiaocai He; Jianshe Chen; Qing Han (Water, Air, & Soil Pollution, 2025)

Genome-Wide Identification and Expression Analysis of β-Ketoacyl-CoA Synthase Family in Sugarcane (Saccharum spontaneum) - An-zi Li; Xin Peng; Yuan Huang; Zhao-fu Bi; Ming-jing Liao; Mu-qing Zhang; Sheng-hua Xiao (Tropical Plant Biology, 2025)

Transcriptome and physiological analysis revealed core genes that promote glutathione metabolism in blue honeysuckle in response to freezing stress - Yuxin Fan; Dandan Zang; Tianyi Wang; Zhihua Song; Na Li; Hongyan Cao; Tingting Du; Meng Qi; Yujie Fu; Qing Yang; Biying Dong; Dong Meng (Tree Genetics & Genomes, 2025)

Tandem kinase-NLR pairs grant wheat resistance to fungal diseases - Manman Zhang; Cheng Li; Daowen Wang; Fengquan Liu; Zheng Qing Fu (Science China Life Sciences, 2025)

Network pharmacology, molecular docking and experimental validation to elucidate the anti-ulcerative colitis mechanism of Rosa roxburghii Tratt. leaves - Ming-Liang Luo; Shuang Zhang; Qing-Yong Wang; Ling-Wei Fu; Li-Juan Xiang; Chang Lin; Xin Yin (Natural Product Research, 2025)

AI-identified peptides boost jasmonate-mediated natural resistance against citrus Huanglongbing - Zhibo Zhao; Shufeng Du; Daowen Wang; Yong Wang; Zheng Qing Fu (Science Bulletin, 2025)

Single-inductor multiple-output converter for hydrogen electrolyzer arrays in PV-HESS-PEM microgrid using deep neural network based model predictive control - Binbin Xun; Xinqiang Tang; Qing Fu; Benfei Wang (Process Safety and Environmental Protection, 2025)

RNA interference targeting cytochrome P450 cyp303a1 on the performance of Henosepilachna vigintioctopunctata - Kai-Yun Fu; Miao He; Lin Jin; Guo-Qing Li (Pesticide Biochemistry and Physiology, 2025)

Effect of apparent pore-fluid compressibility and degree of saturation with atmospheric pressure on wave-induced transient pore pressure response - Wen-Gang Qi; Pei-Qing Zhao; Li-Jing Yang; Mo-Zhen Zhou; Fu-Ping Gao; Dong-Sheng Jeng (Ocean Engineering, 2025)

Construction and structural characterization of carboxymethyl cellulose-based hydrogels from Rosa roxburghii Tratt pomace for oral drug delivery - Siyuan Zheng; Chao Li; Qing Chen; Hao Dong; Xiong Fu; Qiang Huang (Food Research International, 2025)

Molecular characteristics of halogenated disinfection byproducts elucidated by Fourier transform ion cyclotron resonance mass spectrometry - Yiming Feng; Yifan Qian; Cun Liu; Qing-Long Fu (Environmental Pollution, 2025)

Pretrain-finetune neural operator for multi-fidelity surrogate modeling of structural dynamic systems - Pei-Lin Li; Shi-Fu Liu; Yi-Qing Ni; Jian-Ming Ling; You-Wu Wang (Engineering Structures, 2025)

Geometric mismatch of chain lengths enhancing the electrocaloric effect in PVDF - Yibo Zhang; Shixian Zhang; Zhiwei Ye; Fukun Niu; Yuheng Fu; Hongmei Qin; Chuanxi Xiong; Quanling Yang; Qing Wang (Chemical Engineering Journal, 2025)

Cu nanowire arrays on electroless deposited cu foam for efficient electrocatalytic formaldehyde selective conversion to co-produce H2 and valuable chemicals - Chunyi Ye; Yang Yang; Shujing Chen; Chunhua Liu; Xiao-Qing Sun; Danni Liu; Jiujun Zhang; Jing-Li Luo; Xian-Zhu Fu (Chemical Engineering Journal, 2025)

Nearly 100% selective hydrolysis of pyrolytic sugar over sustainable carbon catalysts enables highly efficient production of bioethanol - Hong-li Ma; Ming-fu Li; Ying-chuan Zhang; Qing-hua Huang; Li-qun Jiang; Zhen Fang (Bioresource Technology, 2025)

Four new acylphloroglucinol glucoside derivatives from the leaves of Lysidice rhodostegia - Tian-Yuan Wu; Wei-Xuan Zheng; Xuan Zhou; Kai Zhao; Wei Wu; Li-Qin Zhan; Jin-Tao Fu; Qing Tang; Yu-Bo Zhang; Wen Li; Guo-Cai Wang (Natural Product Research, 2025)

The response of plant-derived lignin phenols accumulation to nutrient addition depends on soil depth in a subtropical plantation - Jin He; Dong Bu; Yuan-Huang Zeng; Shui-Bo Han; Wen-Qing Li; Fu-Sheng Chen; Ying-Ying Zong; Yu-Xin Huang; Yang Zhang; Xiang-Min Fang (Plant and Soil, 2025)

Phylogeography of a Small Mammal ( Blarinella quadraticauda ) Distributed Around the Sichuan Basin, Southwest China - Qing Liu; Yu Deng; Rong‐Hui Fan; Chang‐Kun Fu; Xu‐Ming Wang; Shao‐Ying Liu; Shun‐De Chen (Zoologica Scripta, 2025)
The rapid climatic fluctuations and geographical factors during the Quaternary glacial period, particularly in the Pleistocene epoch, play a pivotal role in shaping intraspecific genetic diversity. We conducted an investigation into the genetic structure and speciation mechanisms of a small mammal species, Asiatic Short‐Tailed Shrew ( Blarinella quadraticauda ), which is mainly distributed in the mountains surrounding the Sichuan Basin and its adjacent regions in southwest China. Extensive sampling was conducted across the region (180 Asiatic Short‐Tailed Shrews from 67 sites), followed by principal component analysis and discriminant analysis on complete skull data. Phylogenetic analyses were conducted using mitochondrial (Cytb) and nuclear (APOB and BRCA1) genes. Additionally, the potentially suitable distribution range under both current and historical climatic conditions was projected. Our results show that B. quadraticauda in the Sichuan Basin is divided into six major clades, which are largely morphologically similar, except for the clade from Baoxing, Sichuan, which exhibits a slightly larger size. Additionally, the species exhibits a nearly ring‐like distribution around the Sichuan Basin. Genetic exchange among populations in the northern and eastern regions of the basin appears to be limited, suggesting potential barriers to gene flow. Under the influence of the basin's lowlands, the rapid climate oscillation of the Quaternary glacial period and the uplift of the Tibetan Plateau, the species appears to have formed a ring distribution in the Sichuan Basin. Moreover, we have also updated the taxonomy and distribution range of B. quadraticauda .

Path analysis and curve fitting of morphometric traits and body weight of juvenile Aspiorhynchus laticeps - Huale Lu; Huimin Hao; Zhulan Nie; Jie Wei; Qing Xiao; Hongmei Fu; Yuren Gong; Min Wang (Journal of Fish Biology, 2025)
In this experiment, correlation analysis, path analysis, regression analysis and curve‐fitting methods were employed to investigate the relationships between the body weight (Y) and morphological variables (X1–X36) of juvenile Aspiorhynchus laticeps (common name: big‐head schizothoracin). These methods were used to identify the main morphological trait indices affecting body weight and further determine the optimal fitting models between four main morphological traits and body weight. The study found that 94% of the morphological traits of juvenile A. laticeps had a highly significant positive correlation with body weight ( p p > 0.05), while other morphological traits had a significant positive correlation ( p R 2 = 0.718), the optimal fitting model of mouth cleft height (X11) and body weight was a power function equation ln(Y) = −9.847 × (1/X11) + 3.065 ( R 2 = 0.560), the optimal fitting model of CI (X30) and body weight was a logarithmic function equation ln(Y) = −36.207 × (1/X30) + 4.308 ( R 2 = 0.881), and the optimal fitting model of the distance from the end of the dorsal fin base to the starting point of the ventral caudal fin (DF, X35) and body weight was a logarithmic function equation ln(Y) = −61.089 × (1/X35) + 3.811 ( R 2 = 0.728). The research results indicate that in the breeding selection of juvenile A. laticeps , CI (X30) should be taken as the main selective trait, supplemented by body width (X3), mouth cleft height (X11) and DF (X35) as references.

New sesquiterpenoids from the flowers of pentanema britannicum (L.) D.Gut.Larr - Zhen Pei; Yan-Nan Ji; Xin-Yue Zhang; Yu-Qing Xie; Yan Fu; Zhi-Yu Ni; Jian Su; Yu-Cheng Gu; Yi-Bing Wu (Natural Product Research, 2025)

The mechanisms of MTOCs maturation in human and mouse oocytes - Hao Gu; Ling Wu; Mingru Yin; Xingzhu Du; Jing Fu; Fangzhou Xu; Zhiqi Ye; Xuelin Zhang; Huixia Jing; Yuxi Luo; Wenzhi Li; Xiaoxi Sun; et al. (Science Bulletin, 2025)

Nitrogen-containing pollutant records in rainfall from the north-south boundary area in China: Compositions, variations, and sources - Xinyi He; Jie Zeng; Qixin Wu; Qing Ma; Jie Zhang; Lihong Fu; Xin Ge (Process Safety and Environmental Protection, 2025)

Two undescribed phytoecdysteroids from Dianthus superbus L. - Yi-Han Liu; Qing Zhang; Da-Zhi Zhang; Xu-Yang Fu; Wu-Yang Liu; Jun-Mian Tian (Phytochemistry Letters, 2025)

Three key steps complete the biosynthesis of phenylalanine-derived salicylic acid in diverse plant species - Kaihuai Li; Le Luo; Huan Chen; Daowen Wang; Fengquan Liu; Zheng Qing Fu (Molecular Plant, 2025)

Efficient activation of peracetic acid by Fe-doped g-C3N4 for selective degradation of emerging contaminants: Unraveling the role of reactive complex - Chun Cai; Jiarui Shi; Qing Liu; Qiqi Zhu; Qing Fu; Wei Wang; Xiaodi Duan (Journal of Hazardous Materials, 2025)

Acidity-gradient controlled conversion of byproduct gypsum into high-purity whiskers: A synergistic process for wastewater treatment and resource recovery - Binchuan Li; Yan Li; Zihao Wang; Jianshe Chen; Daxue Fu; Yongfeng Chang; Kuiren Liu; Yina Li; Qing Han (Journal of Environmental Chemical Engineering, 2025)

Influential mechanisms of light exposure on the reduction of V5+ by extracellular polymeric substances: Role of the reductive and nonreductive components - Wen Qing; Dan Zhou; Liyuan Fu; Tianxin Zhou; Haoran Xiong; Mengmeng Liang; Yi Huang; Jinshu Zhang; Yubin Li; Chengye Yang; Jingxian Qi (Journal of Environmental Chemical Engineering, 2025)

Inhibitory effects of Ag-Cu bimetallic nanoparticles using Camphora officinarum extracts on sulfate-reducing bacteria - Jian Fu; Yujie Hu; Qing Feng; Xiaonan Li; Fan Zhang; Shanshan Sun; Yuehui She (Journal of Environmental Chemical Engineering, 2025)

Simulation of the enhancement of mass transfer on removal behavior of CH3I in microchannel reactor - Qing He; Lei Zhang; Man Fu; Guorui Zhu (Journal of Environmental Chemical Engineering, 2025)

Canopy and understory nitrogen addition differentially regulate fine root decomposition in a temperate forest - Xiaowei Li; Chenlu Zhang; Beibei Zhang; Li Jiang; Chenhui Sun; Yulong Bai; Yifei Shi; Wei Zhang; Qing Ye; Junhua Yan; Juemin Fu; Wenzhi Du; et al. (Forest Ecology and Management, 2025)

Highly selective and sensitive detection of β-lactam antibiotics in food samples using a fluorescent turn-on probe based on metal-organic framework - Ran An; Rui-Xuan Li; Xin Shang; Chang-Qi Fu; En-Qing Gao; Qi Yue (Food Chemistry, 2025)

Synthesis of expanded microcrystalline graphite/Mn0.4Zn0.6Fe2O4 composites for electromagnetic wave absorption - Mingzhe Liu; Bo Wang; Yujiang Wang; Binchuan Li; Daxue Fu; Yongfeng Chang; Jianshe Chen; Kuiren Liu; Qing Han; Xudong Lu; Cean Guo; Shicheng Wei (Chemical Engineering Journal, 2025)

Astragaloside IV-PESV facilitates pyroptosis by enhancing palmitoylation of GSDMD protein mediated by ZDHHC1 - Xujun You; Honghan Li; Qixin Li; Qing Zhang; Yiguo Cao; Wei Fu; Bin Wang (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Chalcone derivatives containing 1,2,4-triazole and pyridine moiety: design, synthesis, and antiviral activity - Hui Xin; Jiao Tian; Tianyu Deng; Qing Zhou; Yuhong Wang; Hong Fu; Haotao Pu; Wei Xue (Molecular Diversity, 2025)

Linking two types of breccias to sediment-hosted stratiform copper (SSC) and iron oxide-copper-gold (IOCG) deposits in the Kangdian metallogenic belt, SW China - Xue-Qing Yin; Xin-Fu Zhao; Zhi-Kun Su; Hai-Tao Lin; Zhi-Min Zhu; Wen-Lei Song; Martin Yan Hei Li; Kui-Dong Zhao (Mineralium Deposita, 2025)

Correction to: Links between personality, metabolic rates, brain size, and spatial learning ability of goldfish (Carassius auratus) under two conditions of spatial learning - Wu-Xin Li; Shi-Jian Fu; Ling-Qing Zeng (Behavioral Ecology and Sociobiology, 2025)

Assessment of psychological resilience in adult patients with epilepsy: a cross-sectional study - Qing Fu; Yue Huang; De-Feng Liu (Acta Neurologica Belgica, 2025)

UWS-YOLO: Advancing Underwater Sonar Object Detection via Transfer Learning and Orthogonal-Snake Convolution Mechanisms - Liang Zhao; Xu Ren; Lulu Fu; Qing Yun; Jiarun Yang (Journal of Marine Science and Engineering, 2025)
Accurate and efficient detection of underwater targets in sonar imagery is critical for applications such as marine exploration, infrastructure inspection, and autonomous navigation. However, sonar-based object detection remains challenging due to low resolution, high noise, cluttered backgrounds, and the scarcity of annotated data. To address these issues, we propose UWS-YOLO, a novel detection framework specifically designed for underwater sonar images. The model integrates three key innovations: (1) a C2F-Ortho module that enhances multi-scale feature representation through orthogonal channel attention, improving sensitivity to small and low-contrast targets; (2) a DySnConv module that employs Dynamic Snake Convolution to adaptively capture elongated and irregular structures such as pipelines and cables; and (3) a cross-modal transfer learning strategy that pre-trains on large-scale optical underwater imagery before fine-tuning on sonar data, effectively mitigating overfitting and bridging the modality gap. Extensive evaluations on real-world sonar datasets demonstrate that UWS-YOLO achieves a mAP@0.5 of 87.1%, outperforming the YOLOv8n baseline by 3.5% and seven state-of-the-art detectors in accuracy while maintaining real-time performance at 158 FPS with only 8.8 GFLOPs. The framework exhibits strong generalization across datasets, robustness to noise, and computational efficiency on embedded devices, confirming its suitability for deployment in resource-constrained underwater environments.

Chemotaxonomically significant phytochemicals with α-glucosidase and tyrosinase inhibitory activities from Chinese endemic plant Ophiorrhiza hunanica - Qing Bu; Qi-Bin Yang; Can-Qi Liu; Zeng-Yue Ge; Xiao-Wen Liao; Lei Wu; Lin-Fu Liang (Natural Product Research, 2025)

Research on shipping carbon governance considering rent-seeking behavior: an evolutionary game analysis based on prospect theory - Qing Chen; Fang Chen; Bojun Gu; Peng Tian; Yufang Fu (Frontiers in Marine Science, 2025)
Accurate carbon emission data serve as the foundation for the effective functioning of carbon markets. However, strategic collusion driven by perceived utility values among market participants can systematically erode governance efficacy. In response to the vulnerability of shipping carbon governance systems caused by rent-seeking behavior, this study develops a tripartite evolutionary game model involving shipping companies, carbon verification agencies, and governments based on prospect theory. Using system dynamics modeling and numerical simulation, we validate the equilibrium constraints and analyze the impact of basic parameters and perceived value coefficient. The results indicate that shipping carbon governance evolves dynamically in stages across its lifecycle, driven by the formation of self-sustaining in shipping companies. Moreover, stakeholder decisions predominantly determined by cost-benefit structures, wherein ESGs’ green premiums effectively drive low-carbon transition, while the anticipated rent-seeking gains incentivize such collusion. Additionally, perceived coefficients exert differentiated moderating effects. Shipping companies’ transition decisions show negative correlations with the risk attitude and loss aversion coefficients, whereas carbon verification agencies and governments demonstrate overall positive correlations with these coefficients. Consequently, we propose a systematic governance framework to provide decision support for solving the rent-seeking dilemma and promoting a carbon governance in shipping industry.

Anti-inflammatory abietane-type diterpenoids from the roots of Salvia przewalskii - Yan-Fang Chen; Yu-Qing Lu; Wan-Yun Gao; Bo-Yi Fan; Fu-Cai Ren; Chuan-Pu Shen (Phytochemistry, 2025)

Sporopollenin-chitosan microspheres loaded with an endophytic fungus Talaromyces neorugulosus R-209 for promoting development and controlling root rot in pigeon pea - Jin-Xian Fu; Jiao Jiao; Qing-Yan Gai; Yu-Jie Fu; Mo-Nan Wen; Xiao-Qing Wang; Jing He (Journal of Plant Physiology, 2025)

Bisphenol A caused abnormal spermatogenesis of Eriocheir sinensis through es-ERR/es-KIF4A pathway with discussion of BPA substitutes - Yu Yang; Di Wu; Tian Lei; Hang-Yuan Zhao; Jun-Jie Yu; Lan-Min Wang; Ding-Xi Liu; Yan-Shuang Zhao; Jia-Hao Ni; Fu-Qing Tan; Wan-Xi Yang (Journal of Hazardous Materials, 2025)

Simulation and experimental study of potato slices during cooking - Hanyu Fu; Pei Yang; Penggeng Sun; Liuyang Ren; Jingshen Xu; Qing Liang; Zhaohui Zheng; Weijun Xie; Deyong Yang (International Journal of Gastronomy and Food Science, 2025)

Dynamic changes in metabolites during the manufacture of three distinct flavor types of Tieguanyin - Lin Zeng; Yan-Qing Fu; Jin-Long Liu; Yuan-Chao Li; Shui-lian Gao; Ying Gao; Fang Wang; Yong-Quan Xu (Food Chemistry, 2025)

Enzyme-assisted dynamic extraction as a promising method to produce high-quality fresh tea juice from summer tea leaves - Yuan-Chao Li; Yan-Qing Fu; Ying Gao; Jie-Qiong Wang; Shan Jin; Yanglong Liu; Jian-Xin Chen; Yong-Quan Xu (Food Chemistry, 2025)

Dual-defect engineering strategy induced polarization loss in trimetallic MOFs/MXene-derived nanocomposites for broadening microwave absorption bandwidth - Yuanzhao Hou; Binchuan Li; Kuiren Liu; Jianshe Chen; Yongfeng Chang; Bo Wang; Shicheng Wei; Xiaocai He; Da Li; Chul B. Park; Daxue Fu; Qing Han (Chemical Engineering Journal, 2025)

Combined space cooling/heating and domestic hot water supply driven by data center waste heat: Complementary energy conservation, economic capacity optimization and generic analysis framework - Jun Bai; Xiaohui Wu; Xiaoyuan Chen; Zhiying Zhang; Lin Fu; Chunxiao Zhao; Ke Qing; Qiaoyu Luo; Shirong Gong; Boyang Shen (Building and Environment, 2025)

Accurate detection and high throughput profiling of unknown PFAS transformation products for elucidating degradation pathways - Bei Zhang; Jibao Liu; Shanshan Qing; Thilini Maheshika Herath; Huan Zhao; Supaporn Klabklaydee; Qing-Long Fu; Eunsang Kwon; Nozomi Takeuchi; Douyan Wang; Takao Namihira; Toshihiro Isobe; et al. (Water Research, 2025)

Whole-genome resequencing-based assessment of genomic diversity and selection signatures in Rhipicephalus microplus from Shaanxi, China - Yi-yao Mou; FU-wen Wang; YU-kun Kang; Ya-qing Li; YU-ying Yang; Tian-yuan Liu; Chu-zhao Lei; Qing Lin (Veterinary Parasitology, 2025)

Dynamic regulation of rice immunity by a canonical protein complex - Xingyu Zhang; Yu Wang; Xuemin Zhou; Daowen Wang; Hongyuan Zheng; Zheng Qing Fu (Science Bulletin, 2025)

The RING-finger ubiquitin E3 ligase RFEL1 targets wheat NPR3 for degradation to confer broad-spectrum resistance against biotrophic fungal pathogens - Liuhui Qiao; Kunpu Zhang; Jinyan Li; Ziming Zhang; Xiao Sun; Huiyun Liu; Ziyue Li; Nannan Ni; Ximei Ma; Jianhui Zhao; Guangwei Li; Xiaohuan Jin; et al. (Molecular Plant, 2025)

Complete genome sequence of Alteromonas sp. OM2203, a marine bacterium degrading Ulva prolifera polysaccharides - Ming-Chen Wang; Zhi-Qing Wang; Jia-Rong Liu; Na Wang; Zhen-Kun Li; Fei-Fei Li; Yu-Han Sang; Hui-Hui Fu (Marine Genomics, 2025)

Enhanced sulfamethoxazole (SMX) degradation by Shewanella oneidensis MR-1 via a microbially driven Fenton reaction - Qing-Jiahui Fan; Wei Li; Gen-Ji Yao; Zu-Hao Wang; Han Fu; Yong-Di Liu; Bruce E. Rittmann (Journal of Water Process Engineering, 2025)

Improved identification of chlorinated disinfection byproducts by the sequential elution and absorption mode - Rong Qin; Yiming Feng; Shasha Zhuo; Qing-Long Fu (Journal of Hazardous Materials, 2025)

Weakening plasticulture boosts maize productivity while improving environmental benefits in drying east African Plateau - Fu-Jian Mei; Qing-Hui Wen; Yang Wang; Alex Ndolo Munyasya; Sylvia Ngaira Indoshi; Wesly Kiprotich Cheruiyot; Wei Wang; David Mwehia Mburu; Aggrey Bernard Nyende; Levis Kavagi; You-Cai Xiong (Journal of Cleaner Production, 2025)

scSAGRN: Inferring gene regulatory networks from single-cell multi-omics using spatial association - Qing Ren; Mengdi Nan; Yuhan Fu; Xiang Chen; Yibing Ma; Yongle Shi; Jie Gao (BioSystems, 2025)

Hepatotoxic effects of exposure to different concentrations of Dibutyl phthalate (DBP) in Schizothorax prenanti: Insights from a multi-omics analysis - Luo Lei; Wuga Sha; Qing Liu; Shidong Liu; Yinhua Zhou; Rundong Li; Yuting Duan; Suxing Fu; Hejiao Li; Rongrong Liao; Linzhen Li; Rongzhu Zhou; et al. (Aquatic Toxicology, 2025)

Droplet-vitrification for cassava shoot tip cryopreservation: protocol optimization and histological observation for rapid shoot tip recovery - Min-Rui Wang; Xiu-Qing Miao; Yun-Liu Fu; Lang-Xin Chen; Xiao-Bing Wang; Qing-Quan Yang; Li Xu; Zhiying Li (Plant Cell, Tissue and Organ Culture (PCTOC), 2025)

Exploring AI-enhanced NMR dereplication analysis for complex mixtures and its potential use in adulterant detection - Xiao-Nan Du; You-Wen Chen; Qing Wang; Hui-Ying Yang; Yong Lu; Xian-Fu Wu (Phytochemistry Reviews, 2025)

Karyotype and evolution trend analysis of seven diploid accessions and their autotetraploid lines of Tartary buckwheat native to China - Li-kun Lian; Pei Zhang; Xiao-fen Wu; Yi-zhong Zhang; Qing-fu Chen (Genetic Resources and Crop Evolution, 2025)

Inhibitory effects of flavonoids and alkaloids from the traditional antihyperglycemic herb Polygonatum kingianum var. grandifolium on α-glucosidase activity - Qing-Dong Ma; Xu-Juan Fu; Xiao-Qin Xiong; Dong-Mei Liu; Zhuo-Jun Li; Wei Gong; Dong-Qin Guo; Dong-Yang Yi (Natural Product Research, 2025)

Two new megastigmane glycosides from the leaves of Nicotiana tabacum and their anti-inflammatory activities - Peng-fei Yang; Wei Wu; Hang-hang Han; Qing-fu Wang; Lei Li; Ze-ning Wang; Duo-bin Mao; Zhi-fei Chen (Natural Product Research, 2025)

A new approach to color correction and equalization for generating mars global color image mosaics from Tianwen-1 MoRIC images - Xin Ren; Xiaoxia Zhang; Wangli Chen; Wei Yan; Xingguo Zeng; Xu Tan; Xingye Gao; Qiang Fu; Lin Guo; Qing Zhang; Zhaopeng Chen; Guobin Yu; et al. (ISPRS Journal of Photogrammetry and Remote Sensing, 2025)

Identifying seasonal sources and processes controlling nitrate in a typical reservoir-type headwater watershed of Eastern China using stable isotopes - Mengyao Ding; Huawu Wu; Haixia Zhang; Qing Zhu; Ruiyu Lei; Kaiwen Li; Hongxiang Fan; Jing Li; Congsheng Fu (Agriculture, Ecosystems & Environment, 2025)

Physical model tests on the lateral cyclic behaviour of monopile in marine clay - Kai-Fu Liu; Yu-Xiao Li; Wei-Qiang Feng; Yue-Dong Xu; Zhi-Qing Zhang (Ocean Engineering, 2025)

Qualitatively elucidating the molecular characteristics of precursors for saturated halogenated disinfection byproducts in chlorinated urban eutrophic lake water by ultrahigh-resolution mass spectrometry - Shixi Wu; Qing-Long Fu; Manabu Fujii; Jibao Liu; Ahmed Elreedy; Xin Yang; Pingqing Fu; Yanxin Wang (Journal of Hazardous Materials, 2025)

Dynamic interactions of titanium dioxide nano-pollutants with a lung surfactant model: A nonlinear interfacial rheology study - Farzaneh Hajirasouliha; Daniela Placha; Yong-Qing Fu; Dominika Zabiegaj (Journal of Hazardous Materials, 2025)

Encapsulated benzoic acid alleviated LPS-induced intestinal damage via NRF2 activation - Yanyan Zhang; Tianjiao Wang; Qing He; Mahmoud M. Abouelfetouh; Qin Fu; Siming Yao; Shiqiang Ju; Zhenlei Zhou; Qiao Li (Food Bioscience, 2025)

Climate suitability determines optimal yielding of dryland maize: A validation on timely sowing as an ancient wisdom - Jing Wang; Ling Zhao; Meng Hao; Ning Wang; Qing-Hui Wen; Fu-Jian Mei; Aziz Khan; Bao-Zhong Wang; Xiao-Lin Zhang; Wei Wang; Chang-Lang Yang; Fei Mo; et al. (Field Crops Research, 2025)

Key role of recycled terrigenous sediments in generating continental arc magmatism in the West Qinling orogen, China - Li-Tao Ma; Li-Qun Dai; Hao Liang; Ye-Dan Hu; Qing-Cheng Yang; Zi-Fu Zhao; Guo-Chao Sun (Chemical Geology, 2025)

Links between personality, metabolic rates, brain size, and spatial learning ability of goldfish (Carassius auratus) under two conditions of spatial learning - Wu-Xin Li; Shi-Jian Fu; Ling-Qing Zeng (Behavioral Ecology and Sociobiology, 2025)

Deciphering the effective substances of mangrove plant Acanthus ilicifolius Linn. against liver injury - Qing Zhao; Shu-Yue Song; Han Fang; Yao-Yao Zheng; Meng-Qi Zhang; Xia Ren; Ya-Hui Zhang; Xiu-Mei Fu; Xin Li; Chang-Yun Wang (Natural Product Research, 2025)

Eco-driving control strategy for plug-in hybrid vehicle platoon with time-delay phenomenon compensation - Shengru Chen; Ronghui Zhang; Qing Fu; Yuchuan Gu; Jing Zhao; Nengchao Lyu; Lei Zhang (Process Safety and Environmental Protection, 2025)

An endophytic fungus Dichotomopilus funicola J-219 for the control of pigeon pea root rot caused by Rhizoctonia solani and its role in regulating the secondary metabolic defense response - Jie Gao; Jin-Xian Fu; Jiao Jiao; Qing-Yan Gai; Zi-Yi Zhang; Xiao-Qing Wang; Yu-Jie Fu (Physiological and Molecular Plant Pathology, 2025)

Multi-method data-driven prediction for maximum scour depth of pile foundations in clay - Qing-Kai Song; Wen-Gang Qi; Ning Wang; Fu-Ping Gao (Ocean Engineering, 2025)

Chemodiversity of soil dissolved organic matter complementally improved by stepwise elution and electrospray ionization modes - Shasha Zhuo; Rong Qin; Qing-Long Fu (Organic Geochemistry, 2025)

Propagation of plant immunity via interactions between PRIMER and bystander cells - Hongyuan Zheng; Yu Wang; Xuemin Zhou; Daowen Wang; Shi Xiao; Zheng Qing Fu (Molecular Plant, 2025)

Removal of arsenic from water by silver nanoparticles and Fe-Ce mixed oxide supported on polymeric anion exchanger - Li Li; Su-juan Yu; Rong-gang Zheng; Qing-cun Li; Rui Liu; Jing-fu Liu (Journal of Environmental Sciences, 2025)

Facile and scalable synthesis of bio-based adsorbents from tannin for economical uranium extraction from seawater - Xingyu Fu; Minsi Shi; Dingyang Chen; Zixu Ren; Qing Bai; Rui Zhao (Desalination, 2025)

Co-culture of Cajanus cajan (Linn.) Millsp. cell suspension cultures with an endophytic fungus for the enhanced production of pharmacologically active cajaninstilbene acid - Jin-Xian Fu; Jiao Jiao; Qing-Yan Gai; Yu-Jie Fu; Xiao-Qing Wang; Mo-Nan Wen; Jing He (Plant Cell, Tissue and Organ Culture (PCTOC), 2025)

Avian influenza A(H5N6) virus detected during live-poultry market surveillance linked to a human infection in Changsha, China, from 2020 to 2023 - Zheng Huang; Rusheng Zhang; Dong Yao; Huiyuan Fu; Lingzhi Li; Shan Xiao; Xinhua Ou; Mingzhong Xu; Qing-Bin Lu; Xuewen Yang (Archives of Virology, 2025)

Transillumination imaging for detection of stress cracks in maize kernels using modified YOLOv8 after pruning and knowledge distillation - Jingshen Xu; Shuyu Yang; Qing Liang; Zhaohui Zheng; Liuyang Ren; Hanyu Fu; Pei Yang; Weijun Xie; Deyong Yang (Computers and Electronics in Agriculture, 2025)

Microbiota-dependent and -independent autoimmunity in plants - Lijing Liu; Dev Patel; Olivia Cyburt; Daowen Wang; Zheng Qing Fu (Trends in Plant Science, 2025)

Numerical study on wave–wind coupling effects on hydrodynamics and light capture performance of offshore multi-body floating photovoltaic system - Jia Fu; Yun-Peng Zhao; Guang-Chen Jia; Chao Ma; Jia-Qing Shu; Yan-Qian Sun (Ocean Engineering, 2025)

Genomic analysis of Vibrio sp. D3 reveals its role in marine sulfur cycling - Fei-Fei Li; Zhen-Kun Li; Ming-Chen Wang; Jia-Rong Liu; Na Wang; Zhi-Qing Wang; Yu-Zhong Zhang; Hui-Hui Fu (Marine Genomics, 2025)

Enhanced nonradical oxidation of thiocyanate by nano γ-Fe2O3 and Fe3C-modified 2D hierarchical porous carbon nanosheets - Yang Yang; Jianshe Chen; Daxue Fu; Yongfeng Chang; Kuiren Liu; Shuang Cui; Yina Li; Binchuan Li; Shicheng Wei; Da Li; Qing Han (Journal of Environmental Chemical Engineering, 2025)

Flexible surface acoustic wave technology for enhancing transdermal drug delivery - Jikai Zhang; Duygu Bahar; Hui Ling Ong; Peter Arnold; Meng Zhang; Yunhong Jiang; Ran Tao; Luke Haworth; Xin Yang; Chelsea Brain; Mohammad Rahmati; Hamdi Torun; et al. (Drug Delivery and Translational Research, 2025)
Transdermal drug delivery provides therapeutic benefits over enteric or injection delivery because its transdermal routes provide more consistent concentrations of drug and avoid issues of drugs affecting kidneys and liver functions. Many technologies have been evaluated to enhance drug delivery through the relatively impervious epidermal layer of the skin. However, precise delivery of large hydrophilic molecules is still a great challenge even though microneedles or other energized (such as electrical, thermal, or ultrasonic) patches have been used, which are often difficult to be integrated into small wearable devices. This study developed a flexible surface acoustic wave (SAW) patch platform to facilitate transdermal delivery of macromolecules with fluorescein isothiocyanates up to 2000 kDa. Two surrogates of human skin were used to evaluate SAW based energized devices, i.e., delivering dextran through agarose gels and across stratum corneum of pig skin into the epidermis. Results showed that the 2000 kDa fluorescent molecules have been delivered up to 1.1 mm in agarose gel, and the fluorescent molecules from 4 to 2000 kDa have been delivered up to 100 µm and 25 µm in porcine skin tissue, respectively. Mechanical agitation, localised streaming, and acousto-thermal effect generated on the skin surface were identified as the main mechanisms for promoting drug transdermal transportation, although micro/nanoscale acoustic cavitation induced by SAWs could also have its contribution. SAW enhanced transdermal drug delivery is dependent on the combined effects of wave frequency and intensity, duration of applied acoustic waves, temperature, and drug molecules molecular weights. Graphical Abstract Graphical Abstract: Flexible surface acoustic wave technology for enhancing transdermal drug delivery

Screening of Spinal Muscular Atrophy Carriers and Prenatal Diagnosis in Pregnant Women in Yancheng, China - Huilin Sun; Jianli Zheng; Qing’e Zhang; Feifei Ying; Yadong Fu; Yongjuan Guan; Jing Wu; Yueyun Zhou; Jingjing Dong; Mengjun Xu; Fangfang Yang; Ning An; et al. (Biochemical Genetics, 2025)

Assessment of stigma among patients living with Parkinson’s disease: an exploratory study - Yue Huang; Qing Fu; De-feng Liu (Acta Neurologica Belgica, 2025)

Anti-BPH lignans from Urtica triangularis subsp. pinnatifida (Hand.-Mazz.) C.J.Chen - Qing Fu; Dongliang Xiao; Nan Jiang; Dunzhu Luosang; Yangji Cidan; Yufei Xi; Hai Yan; Xinyi Zhang; Baomin Feng; Xuan Lu (Natural Product Research, 2025)

Molecular composition difference of electron donating moieties between natural organic matter and effluent organic matter probed by chlorine dioxide - Quan Gao; Yanheng Pan; Yangjian Zhou; Jianglin Peng; Qingqing Kong; Yanhui Cheng; Qing-Long Fu; Xin Yang (Water Research, 2025)

Altered precipitation affects soil enzyme activity related to nitrogen and phosphorous but not carbon cycling: A meta-analysis - Xiaowei Liu; Qing Bai; Ke Liang; Mengting Pei; Ji Chen; Biao Zhu; Qiang Yu; Changhui Peng; Fu Xing; Liang Guo (Journal of Environmental Management, 2025)

The association between anthropogenic heat and parent-report symptoms of childhood attention deficit hyperactivity disorder in China: A novel perspective reflecting climate change - Tao Yu; Yue Wen; Pei-Pei Dong; Ming-Kun Sun; Samantha E. Qian; Mario Schootman; Michael G. Vaughn; Shu-Li Xu; He-Hai Huang; Feng-Wen Shan; Shi-Fu Zhu; Jing-Yao Wang; et al. (International Journal of Hygiene and Environmental Health, 2025)

Seismic performance of precast bridge columns with new grouted corrugated duct connections - Yin Shen; Yi Wang; Chenxi Fu; Qing Zhou (Engineering Structures, 2025)

Research on improving the quality of groundwater self-monitoring via Blockchain technology - Haixiang Li; Dongxue Fu; Meiyue Yang; Sijie Lin; Song Zongzhong; Wei Jiang Liu; Qing Hu (Environmental Impact Assessment Review, 2025)

Room-temperature CO2-to-carbon conversion facilitated by copper-gallium liquid metal - Xiao Chen; Jiacheng Liu; Qing Wang; Mengmeng Fu; Yunlong Li; Jialun He; Wenjun Zhan; Litian Liu; Danfeng Jiang; Yingguo Li; Chao Yu (Chemical Engineering Journal, 2025)

Identification of Potential Causal Genes for Neurodegenerative Diseases by Mitochondria-Related Genome-Wide Mendelian Randomization - Kang-Fu Yin; Ting Chen; Xiao-Jing Gu; Zheng Jiang; Wei-Ming Su; Qing-Qing Duan; Xiang-Jin Wen; Bei Cao; Ju-Rong Li; Li-Yi Chi; Yong-Ping Chen (Molecular Neurobiology, 2025)

Transmedia seepage characteristics of slope–concrete stabilizing piles interface systems in cold regions - Xue Feng; Boxin Wang; Qing Wang; Huie Chen; Lanting Fu (Journal of Mountain Science, 2025)

Straw incorporating in shallow soil layer improves field productivity by impacting soil hydrothermal conditions and maize reproductive allocation in semiarid east African Plateau - Sylvia Ngaira Indoshi; Wesly Kiprotich Cheruiyot; Muhammad Maqsood Ur Rehman; Fu-Jian Mei; Qing-Hui Wen; Alex Ndolo Munyasya; Kiprotich Koskei; David Mwehia Mburu; Aggrey Bernard Nyende; Levis Kavagi; Delphine Nyanchera Gisacho; Eliyas Feyisa Sori; et al. (Soil and Tillage Research, 2025)

Buried interface engineering towards stable zinc anodes for high-performance aqueous zinc-ion batteries - Qing Wen; Hao Fu; Chao Sun; Rude Cui; Hezhang Chen; Ruihan Ji; Linbo Tang; Lingjun Li; Jiexi Wang; Qing Wu; Jiafeng Zhang; Xiahui Zhang; et al. (Science Bulletin, 2025)

A new diterpenoid alkaloid from the Aconitum scaposum - Cheng-En Fu; Gui-Fang Li; Guo-Qing Sun; Shuai Huang; Lin Chen; Xian-Li Zhou (Phytochemistry Letters, 2025)

Mechanistic impact of Gracilaria bailinae extracts on photosynthesis and metabolism in Phaeodactylum tricornutum - Li-Gong Zou; Fu-Fang Wen; Xiao Zhang; Gang Li; Qing Wang; Hong-Ye Li; Yu-Feng Yang (Marine Environmental Research, 2025)

Enhanced electron transport through hydrogen bonds and Ag nanoparticles in the PCN-222/Ag/COF core–shell photocatalyst for efficient oxytetracycline degradation - Bing-Bing Lu; Jia-Chang Lu; Qing-Yun Zhao; Rui Wang; Ze-Lin Chen; Ji-Qiang Guan; Hao Liu; Ying Fu; Fei Ye (Journal of Cleaner Production, 2025)

Dynamic classification and attention mechanism-based bidirectional long short-term memory network for daily runoff prediction in Aksu River basin, Northwest China - Qing Wei; Ju Yang; Fangbing Fu; Lianqing Xue (Journal of Environmental Management, 2025)

Selective adsorption and photodegradation of potentially hazardous salicylic acid by a novel magnetic surface molecularly imprinted photocatalyst (SMIP-Fe0@b-TiO2/CQDs) - Ying Liu; Jiao Jiao; Qing-Yan Gai; Yu-Jie Fu; Yuan Wang (Journal of Environmental Chemical Engineering, 2025)

The rapid fermentation of Euphausia superba sauce and revealing of the relationship between key flavor compounds and core microorganisms - Wenhui Qu; Lihao Wang; Qing Kong; Ruoshu Li; Weijia Liu; Zhanfei Fu; Yunqi Wen; Changhu Xue (Food Research International, 2025)

Amyloid fibrils for β-carotene delivery – Influence of self-assembled structures on binding and in vitro release behavior - Congying Chen; Haifeng Wang; Qing Wang; Mengting Wang; David W. Everett; Min Huang; Yun Zhai; Teng Li; Yuying Fu (Food Chemistry, 2025)

Automatic recognition of debris rock lithology based on unsupervised semantic segmentation - Shengda Qin; Qing Wang; Qihong Zeng; Maolin Ye; Anqi Fu; Guanzhou Chen (Computers & Geosciences, 2025)

Dual Hydrogen-Producing Formaldehyde-Water fuel cell for pollutant treatment and valuable chemical Co-generation - Yang Yang; Jianwen Liu; Munir Ahmad; Xiao-Qing Sun; Chunhua Liu; Shujing Chen; Jiujun Zhang; Jing-Li Luo; Xian-Zhu Fu (Chemical Engineering Journal, 2025)

A case study from a critical stopover site in the East Asian-Australasian Flyway provides lessons for optimal high-tide roost management to support shorebird conservation - Jia Guo; Waner Liang; Yan Zhou; Yifei Jia; Hongyan Yang; Lili Sun; Qing Chen; Ting Fu; Sicheng Ren; Wenkui Jiang; Guangchun Lei; Li Wen (Biological Conservation, 2025)

Effects of dietary hydroxy-cinnamic acid derivatives on growth, muscle, and intestinal parameters of Tilapia (Oreochromis niloticus) - Qing Li; Min Fu; Shengqin Zhu; Juan Liu; Yanqing Li; Zhiyong Xue; Zhigang Zhou; Lijuan Yu (Fish Physiology and Biochemistry, 2025)

Chemodiversity of coastal seawater dissolved organic matter shaped by wastewater treatment plant effluent in Tokyo Bay, Japan - Yanhui Cheng; Jibao Liu; Manabu Fujii; Qing-Long Fu (Applied Geochemistry, 2025)

Impact of in–situ bioelectric field on biogas production, membrane fouling and microbial community in an anaerobic membrane bioreactor under sulfadiazine stress - Haojie Huang; Yutong Sun; Qing Du; Fu Gao; Zi Song; Zhiwen Wang; Suyun Chang; Xinbo Zhang; Wenshan Guo; Huu Hao Ngo (Chemical Engineering Journal, 2025)

Ground ozone rise during the 2022 shanghai lockdown caused by the unfavorable emission reduction ratio of nitrogen oxides and volatile organic compounds - Qian Wang; Yuewu Li; Fangqian Zhong; Wanqi Wu; Hongliang Zhang; Rong Wang; Yusen Duan; Qingyan Fu; Qing Li; Lin Wang; Shaocai Yu; Abdewahid Mellouki; et al. (Atmospheric Environment, 2025)

Separation of the ionospheric and thermospheric contributions in the data from the Triple Ionosophere PhotoMeter onboard the Feng-Yun 3E satellite - Fang Jiang; Tian Mao; Jin-Song Wang; Xiu-Qing Hu; Xiao-Xin Zhang; Liping Fu; Nan Jia; Tianfang Wang (Science China Earth Sciences, 2025)

Comparison of molecular testing methods for diagnosing non-tuberculous mycobacterial infections - Leilei Wang; Yu Chen; Qingqing Wang; Jue Pan; Rong Bao; Wenting Jin; Yumeng Yao; Tingting Fang; Na Li; Sichun Luan; Xiaoyu Yin; Le Qin; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2025)

Ultrasound-Targeted β-Catenin Gene Therapy Improves the Cardiac Function in Mice After Myocardial Infarction - Lei Yang; Tong Gao; Yu Huang; Pei-he Wang; Xin-hao Han; Jie Wu; Lei Huang; Qing-en Da; Kun-fu Ouyang; Zhen Han; Hai Tian; Lu Sun (Cardiovascular Toxicology, 2025)

Holocene paleoenvironment of the Nihewan Basin, China, inferred from high-resolution luminescence dating and a multiproxy analysis of gully sediments - Qing-Hao Ma; Yu-Jie Guo; Hua-Rui Lei; Yu-He Shen; Jia-Jing Wang; Ya Liu; Zhen-Yu Zhou; Jia-Fu Zhang (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

H2O2 sulfenylates CHE to activate systemic salicylic acid synthesis and ignite systemic acquired resistance - Kaihuai Li; Cheng Li; Daowen Wang; Fengquan Liu; Zheng Qing Fu (Molecular Plant, 2024)

PBAT biodegradable microplastics enhanced organic matter decomposition capacity and CO2 emission in soils with and without straw residue - Sha Chang; Chao Chen; Qing-Long Fu; Aoyu Zhou; Zhuyao Hua; Fengxiao Zhu; Shiyin Li; Huan He (Journal of Hazardous Materials, 2024)

Synthesis of lipophilic vitamin C and evaluation of its antioxidant performance in sunflower seed oil frying - Min Fu; Juan Liu; Qing Li; Shengqin Zhu; Zhiyong Xue; Lijuan Yu; Zhigang Zhou (Food Chemistry, 2024)

Shell structure impacts Camellia oleifera fruit splitting during dehydration - Pei Yang; Hanyu Fu; Penggeng Sun; Liuyang Ren; Zhaohui Zheng; Jingshen Xu; Lanlan Lv; Qing Liang; Deyong Yang (Food and Bioproducts Processing, 2024)

Corrigendum to “Ladder type covalent organic frameworks constructed with natural units for the oxygen and carbon dioxide reduction reactions” [Chem. Eng. J. 488 (2024) 150812] - Minghao Liu; Shuai Yang; Yubin Fu; Xiubei Yang; Xuewen Li; Jun He; Qing Xu; Gaofeng Zeng (Chemical Engineering Journal, 2024)

Highly stable zinc anodes enabled by a dual-function additive of in-situ film formation and electrostatic shielding - Rui-han Ji; Hao Fu; Qing Wen; Pei-Yao Li; Pei Yang; Yu-Jing Chen; He-zhang Chen; Jia-feng Zhang; Ling-jun Li; Jie-xi Wang; Qing Wu; Xia-hui Zhang; et al. (Chemical Engineering Journal, 2024)

Optimal operation of CCHP system with duality operation strategy considering hydrogen trading and carbon capture - Zhi-Feng Liu; Ya-He Huang; Qing Kang; Ze-Qi Li; Jing Lu; Rui-Zheng Gu; Xing-Fu Luo; Xiao-Rui Chen; You-Yuan Liu; Yu Tang; Liang Guo (Sustainable Cities and Society, 2024)

Degradation of thiosulfate ions in sodium aluminate solution photocatalyzed by Co-TiO2@ZIF-8 - Jingyi Hao; Binchuan Li; Jing Dai; Daxue Fu; Yongfeng Chang; Jianshe Chen; Na Xu; Kuiren Liu; Qing Han (Minerals Engineering, 2024)

Corrigendum to “Spatial heterogeneity of ecosystem service bundles and the driving factors in the Beijing-Tianjin-Hebei region” [J. Clean. Prod. 479 (2024) 144006] - Qing Li; Dan Li; Jinfeng Wang; Sheng Wang; Rende Wang; Gang Fu; Yixiao Yuan; Zhenhua Zheng (Journal of Cleaner Production, 2024)

Spatial heterogeneity of ecosystem service bundles and the driving factors in the Beijing-Tianjin-Hebei region - Qing Li; Dan Li; Jinfeng Wang; Sheng Wang; Rende Wang; Gang Fu; Yixiao Yuan; Zhenhua Zheng (Journal of Cleaner Production, 2024)

A comparative study on stabilizing and releasing thymol by pre-formed V-type starch and β-cyclodextrin - Qing Gao; Jiabao Zheng; Paul Van der Meeren; Bin Zhang; Xiong Fu; Qiang Huang (Food Hydrocolloids, 2024)

Molecular characterization, spatio-temporal expression patterns of crtc2 gene and its immune roles in yellow catfish (Pelteobagrus fulvidraco) - Wan-Hong Zeng; Zheng-Yong Wen; Xiu-Ying Wei; Yu He; Luo Zhou; Peng Hu; Qing-Chao Shi; Chuan-Jie Qin; Jun Wang; Rui Li; Xiao-Ying Jing; Wei Hu; et al. (Fish & Shellfish Immunology, 2024)

Thermophysical properties and energy-saving efficiency of phase change microcapsule foamed cement composite insulation materials - Lingyong Ma; Xinyue Zhao; Enmin Fu; Qing Li; Wei Jiang; Lidi Huang; Yongyi Zhang; Zhipeng Ju (Energy and Buildings, 2024)

A Credibility Monitoring Approach and Software Monitoring System for VHF Data Exchange System Data Link Based on a Combined Detection Method - Xiaoye Wang; Leyun Fu; Weichen Wang; Qing Hu (Journal of Marine Science and Engineering, 2024)
Due to VDES’s higher data transmission speed and complex communication protocols, vulnerabilities within its data link infrastructure are more pronounced. To ensure the reliability of VDES data transmission, this manuscript proposes a credibility monitoring approach based on the combined detection method of radio interference detection and spoofing source identification and localization, focusing on key data link vulnerabilities outlined in the IALA G1181 VDES VDL Integrity Guide. Automated monitoring is achieved through VDES data link monitoring software (VDES(AIS 2.0)), which is based on a three-tier architecture and a Client/Server (C/S) model. The software validates monitoring techniques and software against various interference scenarios. Visualization of monitoring results, alarm notifications, and relevant data through the front-end interface enhances understanding of VDES data link credibility. This framework supports effective surveillance and detection of vulnerabilities, such as radio interference and spoofing sources.

Insight into the mechanism of alkali-thermal pretreatment of food-waste solid residue through fluorescence spectroscopy coupled with parallel factor analysis - Tianru Wang; Jing He; Tisen Xiao; Junwei He; Xiangjing Fu; Qing Liu (Chemosphere, 2024)

Arsenic activated GLUT1-mTORC1/HIF-1α-PKM2 positive feedback networks promote proliferation and migration of bladder epithelial cells - Zhushan Fu; Meiqi Deng; Qing Zhou; Sihao Li; Weijue Liu; Siyan Cao; Lei Zhang; Yu Deng; Shuhua Xi (Science of The Total Environment, 2024)

Female urinary incontinence in China after 15 years’ efforts: Results from large-scale nationwide surveys - Jiming Zhu; Haiyu Pang; Peicheng Wang; Yanhua Chen; Huihui Li; Qing Liu; Luwen Wang; Hangmei Jin; Liyan Gong; Jingyan Xie; Ting Lai; Aiyang Li; et al. (Science Bulletin, 2024)

Innovative dodecane-hexadecane/expanded graphite composite phase change material for sub-zero cold storage applications - Zicong Zhou; Songping Mo; Qing Li; Kai Fu; Lisi Jia; Ying Chen (International Journal of Refrigeration, 2024)

Experimental investigation of the matching boundary and optimization strategy of a variable geometry turbocharged direct-injected hydrogen engine - Feng-yu Lai; Bai-gang Sun; Zhi-fu Zhang; Shi-wei Zhang; Kang-da Wang; Xue-ming Ju; Qing-he Luo; Ling-zhi Bao; Felix Leach (Fuel, 2024)

Atomically L12 ordered (PtHf)x(NiTi)100-x/CNT as bifunctional catalysts for hydrogen evolution reaction and methanol oxidation reaction with high activity and durability - Yue Fu; Fudi Wang; Chuandong Qing; Yuyuan Zhang; Mingkai Li; Xinghui Cao; Shen Gong; Liuxiong Luo; Zhou Li (Chemical Engineering Journal, 2024)

Extracellular vesicles in pulmonary infection: From pathophysiology to theranostic technologies - Xu Wang; Mai-Qing Shi; Yang Wang; Hao Zhou; Ke Peng; Jun Wang; Shi-Kun Sun; Xu-Rui Shen; Jia-Jia Wang; Zhi Zhao; Xian-Guang Ding; Fu-Hai Ji (Chemical Engineering Journal, 2024)

Mn-periodate complex in situ formed at Mn-N coordinate site in Mn-doped g-C3N5 for efficient and rapid water purification - Shicheng Liu; Sitong Liu; Wenzhong Wang; Chen Zhang; Lijuan Wang; Yujie Liang; Junli Fu; Qing Zhou (Chemical Engineering Journal, 2024)

A deep learning model incorporating frequency domain information for ultra multi-step air pollutant forecasting: A case study of Shanghai - Hai-chao Huang; Hong-di He; Qing-yan Fu; Jun Pan; Zhong-ren Peng (Atmospheric Pollution Research, 2024)

Enhanced production of health-promoting phenolic compounds using a novel endophytic fungus Talaromyces neorugulosus R-209 isolated from pigeon pea in a natural habitat by l-phenylalanine feeding - Jin-Xian Fu; Jiao Jiao; Qing-Yan Gai; Yu-Jie Fu; Jie Gao; Zi-Yi Zhang; Yuan Wang; Xiao-Qing Wang (World Journal of Microbiology and Biotechnology, 2024)

China’s urban green growth from 2000 to 2020 is influenced by legacy effects - Hai-Li Zhang; Hao Xiu; Mir Muhammad Nizamani; Qing Zhou; Kaijun Long; Yunfan Quan; Tingting Fu; Qinghui Sun (Urban Ecosystems, 2024)

Bi-allelic missense variants in MEI4 cause preimplantation embryonic arrest and female infertility - Zhiqi Pan; Weijie Wang; Ling Wu; Zhongyuan Yao; Wenjing Wang; Yao Chen; Hao Gu; Jie Dong; Jian Mu; Zhihua Zhang; Jing Fu; Qiaoli Li; et al. (Human Genetics, 2024)

Prevalence of antibiotic resistance genes, heavy metal, and bacterial community composition in sea sediments influenced by Eriocheir sinensis breeding aquaculture - Hui Fu; Wei Sun; Yawei Cao; Qing Li; Xiaotong Wang; Zijie Zhou; Qian Meng; Tingyi Luo; Wei Gu; Qingguo Meng (Environmental Science and Pollution Research, 2024)

Fortifying nematode resistance through susceptibility gene inactivation - Huan Wang; Ziyue Li; Daowen Wang; Zheng Qing Fu (Trends in Plant Science, 2024)

Interpenetrating LiB/Li3BN2 phases enabling stable composite lithium metal anode - Piao Qing; Shaozhen Huang; Tuoya Naren; Quan Li; Haifeng Huang; Kecheng Long; Zhijian Liu; Lin Mei; Fu Sun; Weifeng Wei; Yu Zhang; Jianmin Ma; et al. (Science Bulletin, 2024)

Dissolved oxygen fluctuation alters dissolved organic carbon stability and can accumulate resistant fraction - Yu-Qing Li; Fu-Tao Fang; Cong Zeng; Zhuo-Yi Zhu (Marine Chemistry, 2024)

The hippo-YAP1/HIF-1α pathway mediates arsenic-induced renal fibrosis - Wei Di; Yan Li; Lei Zhang; Qing Zhou; Zhushan Fu; Shuhua Xi (Environmental Research, 2024)

Stable aryl-armed dihydrophenazines-based radicals - Lu Liu; Yuxuan Li; Haichang Fu; Xuecheng Guo; Qing Wan; Weijun Li; Ben Zhong Tang; Zhiming Wang (Chemical Engineering Journal, 2024)

Asymmetrical changes of electron-donating and electron-accepting capacities of natural organic matter during its interaction with Fe oxyhydroxides - Yiran Liu; Weijun Zhao; Peng Zhang; Qing-long Fu; Chenglong Yu; Songhu Yuan (Chemical Geology, 2024)

Triggering Receptor Expressed on Myeloid Cells 2 Alleviated Sevoflurane-Induced Developmental Neurotoxicity via Microglial Pruning of Dendritic Spines in the CA1 Region of the Hippocampus - Li Deng; Shao-Yong Song; Wei-Ming Zhao; Xiao-Wen Meng; Hong Liu; Qing Zheng; Ke Peng; Fu-Hai Ji (Neuroscience Bulletin, 2024)

Discovery and Exploration of Lipid-Modifying Drug Targets for ALS by Mendelian Randomization - Zheng Jiang; Xiao-Jing Gu; Wei-Ming Su; Qing-Qing Duan; Kang-Fu Yin; Yan-Lin Ren; Yi Wang; Bei Cao; Yong-Ping Chen (Molecular Neurobiology, 2024)

Antibiotics ingestion altered the composition of gut microbes and affected the development and reproduction of the fall armyworm - Yan Fu; Luo-Yan Zhang; Qing-Yi Zhao; Da-Ying Fu; Hong Yu; Jin Xu; Song Yang (Journal of Pest Science, 2024)

Physiological and behavioral responses to social isolation and starvation in a social fish - Dan-Dan Xu; Chun-Hua Wang; Jin-Qiu Bi; Huan Luo; Shi-Jian Fu; Bin Li; Ling-Qing Zeng (Applied Animal Behaviour Science, 2024)

Increasing tree diversity reduces spatial heterogeneity of soil organic carbon and promotes carbon storage in subtropical forests - Muhammed Mustapha Ibrahim; Yongbiao Lin; Zhifeng Guo; Conghui Guo; Xingquan Rao; Suping Liu; Shenglei Fu; Qing Ye; Enqing Hou (Agriculture, Ecosystems & Environment, 2024)

An AIS Base Station Credibility Monitoring Method Based on Service Radius Detection Patterns in Complex Sea Surface Environments - Xiaoye Wang; Yalan Wang; Leyun Fu; Qing Hu (Journal of Marine Science and Engineering, 2024)
The Automatic Identification System (AIS) utilizes base stations to manage vessel traffic and disseminate waterway information. These stations broadcast maritime safety data to vessels within their service radius using VHF signals. However, the emergence of “spoofing base stations” poses a significant threat to maritime safety. These impostors mimic legitimate AIS base stations by appropriating their Maritime Mobile Service Identity (MMSI) information, interacting with vessels, potentially leading to erroneous decisions, or guiding vessels into hazardous areas. Therefore, ensuring the credibility of AIS base stations is critical for safe vessel navigation. It is essential to distinguish between genuine AIS base stations and “spoofing base stations” to achieve this goal. One criterion for identifying AIS spoofing involves detecting signals beyond the expected service radius of AIS base stations. This paper proposes a method to monitor the credibility of AIS base stations through a service radius detection pattern. Furthermore, the method analyzes the impact of hydrological and meteorological factors on AIS signal propagation in complex sea surface environments. By integrating empirical data, it accurately describes the mathematical relationship and calculates the service radius of AIS base station signals. Analyzing vessel position coordinates, decoding base station position messages, and computing distances between vessels and AIS base stations allows for matching with the AIS base station’s designated service radius and propagation distance. This approach enables precise identification of AIS spoofing base stations, thereby facilitating robust monitoring of AIS base station credibility. The research outcomes provide a foundational framework for developing high-credibility AIS base station services within integrated maritime navigation and information systems.

Advanced strategies for conversing and fixing sulfur during waste resins oxidation through Ca/Zn oxides enhanced Na2CO3-K2CO3 system - Xin Liu; Yong-De Yan; Yun Xue; Yang-Hai Zheng; Jing-Ping Wang; Qing-Guo Zhang; Yue-Lin Wang; Fu-Qiu Ma (Process Safety and Environmental Protection, 2024)

Sodium nitroprusside (SNP) generated nitric oxide delays senescence of cowpea (Vigna unguiculata (L.) Walp) - Chunmei Bai; Fan Zhang; Demei Meng; Christopher B. Watkins; Lili Ma; Anzhen Fu; Zhaoze Sang; Susu Guo; Hongwei Wang; Qing Wang; Jinhua Zuo; Yanyan Zheng (Postharvest Biology and Technology, 2024)

Cevanine-type steroidal alkaloids from the bulbs of Fritillaria cirrhosa D. Don - Hui-wen Dong; Shu-hui Wang; Tse Wai Ming; Shao-bing Fu; Yun-hu Zhang; Jia-wei Li; Qing-ying Zhang; Peng-fei Tu; Hong Liang (Phytochemistry, 2024)

Degradation behaviors of Nabumetone and its metabolite during UV/monochloramine process: Experimental and theoretical study - Xiang Tu; Yunsong Bai; Qing Fu; Sheng Chang; Kunfeng Zhang; Yang Pan; Ruiyang Xiao; Yifu Fu; Qi Zhang (Journal of Environmental Sciences, 2024)

Dynamic changes of key metabolites in Longjing green tea during processing revealed by widely targeted metabolomic profiling and sensory experiments - Lin Zeng; Yan-Qing Fu; Ying Gao; Fang Wang; Shuang Liang; Jun-Feng Yin; Marie-Laure Fauconnier; Lijing Ke; Yong-Quan Xu (Food Chemistry, 2024)

Assessing the Long-Term performance of an integrated microbial fuel Cell-Anaerobic membrane bioreactor for swine wastewater treatment - Haojie Huang; Xinbo Zhang; Qing Du; Fu Gao; Zhiwen Wang; Guangxue Wu; Wenshan Guo; Huu Hao Ngo (Chemical Engineering Journal, 2024)

Individual and group behavioral responses to nutritional state and context in a social fish - Ling-Qing Zeng; Hong Ling; Shi-Jian Fu; De-Yong Pu; Shaun S. Killen (Behavioural Processes, 2024)

High dimensional proteomic mapping of bone marrow immune characteristics in immune thrombocytopenia - Feng-Qi Liu; Qing-Yuan Qu; Ying Lei; Qi Chen; Yu-Xiu Chen; Meng-Lin Li; Xue-Yan Sun; Ye-Jun Wu; Qiu-Sha Huang; Hai-Xia Fu; Yuan Kong; Yue-Ying Li; et al. (Science China Life Sciences, 2024)

Relay intercropping boosts soybean recovery growth and delays nodule senescence to achieve yield advantages - Ping Chen; Benchuan Zheng; Huan Yang; Qing Du; Zhidan Fu; Kai Luo; Yilin Li; Ping Lin; Xihong Peng; Tian Pu; Yushan Wu; Xiaochun Wang; et al. (Agriculture, Ecosystems & Environment, 2024)

Molecular mechanism of a coastal cyanobacterium Synechococcus sp. PCC 7002 adapting to changing phosphate concentrations - Qiao-Wei Sun; Yu Gao; Jordan Wang; Fei-xue Fu; Cheng-Wen Yong; Shuang-Qing Li; Hai-Long Huang; Wei-Zhong Chen; Xin-Wei Wang; Hai-Bo Jiang (Marine Life Science & Technology, 2024)
Phosphorus concentration on the surface of seawater varies greatly with different environments, especially in coastal. The molecular mechanism by which cyanobacteria adapt to fluctuating phosphorus bioavailability is still unclear. In this study, transcriptomes and gene knockouts were used to investigate the adaptive molecular mechanism of a model coastal cyanobacterium Synechococcus sp. PCC 7002 during periods of phosphorus starvation and phosphorus recovery (adding sufficient phosphorus after phosphorus starvation). The findings indicated that phosphorus deficiency affected the photosynthesis, ribosome synthesis, and bacterial motility pathways, which recommenced after phosphorus was resupplied. Even more, most of the metabolic pathways of cyanobacteria were enhanced after phosphorus recovery compared to the control which was kept in continuous phosphorus replete conditions. Based on transcriptome, 54 genes potentially related to phosphorus-deficiency adaptation were selected and knocked out individually or in combination. It was found that five mutants showed weak growth phenotype under phosphorus deficiency, indicating the importance of the genes ( A0076 , A0549-50 , A1094 , A1320 , A1895 ) in the adaptation of phosphorus deficiency. Three mutants were found to grow better than the wild type under phosphorus deficiency, suggesting that the products of these genes ( A0079 , A0340 , A2284–86 ) might influence the adaptation to phosphorus deficiency. Bioinformatics analysis revealed that cyanobacteria exposed to highly fluctuating phosphorus concentrations have more sophisticated phosphorus acquisition strategies. These results elucidated that Synechococcus sp. PCC 7002 have variable phosphorus response mechanisms to adapt to fluctuating phosphorus concentration, providing a novel perspective of how cyanobacteria may respond to the complex and dynamic environments.

Exploring the synergistic benefits of insoluble dietary fiber and bound phenolics: Unveiling the role of bound phenolics in enhancing bioactivities of insoluble dietary fiber - Siyuan Zheng; Yue Zhang; Qing Chen; Xiong Fu; Qiang Huang; Bin Zhang; Hao Dong; Chao Li (Trends in Food Science & Technology, 2024)

A 76-m per pixel global color image dataset and map of Mars by Tianwen-1 - Jianjun Liu; Xin Ren; Wei Yan; Wangli Chen; Xingguo Zeng; Xiaoxia Zhang; Xu Tan; Xingye Gao; Qiang Fu; Dingxin Liu; Lin Guo; Qing Zhang; et al. (Science Bulletin, 2024)

Interactions between intestinal microbiota and metabolites in zebrafish larvae exposed to polystyrene nanoplastics: Implications for intestinal health and glycolipid metabolism - Biran Zhu; Xianglin Chen; Taotao Zhang; Qianqian Zhang; Kaiyu Fu; Jianghuan Hua; Mengyuan Zhang; Qing Qi; Binbin Zhao; Min Zhao; Lihua Yang; Bingsheng Zhou (Journal of Hazardous Materials, 2024)

Intestinal metabolite xylulose inhibits colorectal cancer by inducing apoptosis through the MAPK signalling pathway - Qing Hu; Qiao Zheng; Xinhao Du; Ziyi Yang; Qian Tian; Lanfan Liang; Xinyu Zhao; Hang Bai; Yanqin Liu; Ming Zhao; Xiangsheng Fu (Toxicology and Applied Pharmacology, 2024)

The delaying effect of Clausena lansium extract on pear ring rot is related to its antifungal activity and induced disease resistance - Wen-Wu Song; Xiao-Xiang Fu; Duan-Tao Cao; Xiao-Gui Liang; Su-Ling Xiao; Min-Xuan Yuan; Ying-Jin Huang; Qing-Hong Zhou; Hong-Yi Wei; Jun-Wen Wang; Wen-Wen Peng (Postharvest Biology and Technology, 2024)

Syn- and post-collisional mafic igneous rocks from the East Kunlun Orogenic Belt: Implications for recycling of subducting continental crust during the Silurian-Devonian - Li-Tao Ma; Guo-Chao Sun; Li-Qun Dai; Zi-Fu Zhao; Ye-Dan Hu; Qing-Cheng Yang; Lei Qin; Bing Gong (Lithos, 2024)

Construction of AgI/PCN-224 Z-scheme heterojunction for efficient photocatalytic degradation of tetracycline hydrochloride: Pathways, mechanism and theoretical calculations - Jia-Chang Lu; Xue-Lu Bai; Qing-Yun Zhao; Bing-Bing Lu; Ying Fu (Journal of Cleaner Production, 2024)

Enteral nutrition in the management of acute pancreatitis: Modulates gut microbiome and alleviates inflammation - Fang-Yuan Yang; Yi-Jing Cai; Xiao-Ying Niu; Shun-Fu Wang; Yu-Qi Wang; Sabola Eluby Esmie; Rui-Cong Chen; Sheng-Jie Dai; Hong-Ru Kong; Hong-Wei Sun; Ke-Qing Shi (Food Bioscience, 2024)

Preparation, structural characterization and rheological properties of a novel fucose-containing exopolysaccharide from Clavibacter michiganensis - Mengshi Xiao; Luying Tang; Xiaodan Fu; Xinmiao Ren; Jiayuan Bi; Jia Wang; Dongyu Li; Qing Kong; Haijin Mou; Changliang Zhu (Food Hydrocolloids, 2024)

Mo-Mg isotopes trace the role of serpentinite in generating arc magmatism - Qing-Chen Yang; Wei Fang; Li-Qun Dai; Zi-Fu Zhao; Guo-Chao Sun; Bing Gong (Chemical Geology, 2024)

The R2R3-MYB transcription factor ZeMYB32 negatively regulates anthocyanin biosynthesis in Zinnia elegans - Lingli Jiang; Jiahong Chen; Jieyu Qian; Menghan Xu; Hongsheng Qing; Hefeng Cheng; Jianxin Fu; Chao Zhang (Plant Molecular Biology, 2024)

Source-Specific Ecological Risk of Atmospheric PM2.5-Bound Metals and Implications for Air Pollution Control: A Regional Perspective from China - Weiwei Lin; Hedi Zhang; Yuming Lai; Shuling Zhuang; Qiannan Wei; Shaojie Fu; Dejian Mai; Luan Yuan; Qing Wei; Dingli Yue; Qiansheng Hu (Exposure and Health, 2024)

Heavy metals in centralized drinking water sources of the Yangtze River: A comprehensive study from a basin-wide perspective - Kunfeng Zhang; Sheng Chang; Xiang Tu; Enrui Wang; Yanling Yu; Jianli Liu; Lu Wang; Qing Fu (Journal of Hazardous Materials, 2024)

ZnFe2O4 nanosheets as an electron transport bridge and a hole mediator enhance solar-driven unbiased hydrogen generation of ZnO-based nanorod arrays photoanode - Tao Jiang; Jinsen Fu; Yujie Liang; Junli Fu; Lijuan Wang; Qing Zhou; Wenzhong Wang (Fuel, 2024)

Synthesis of biological nanocomposite fluids and enhanced crude oil recovery - Yulong Liu; Jian Fu; Hao Zeng; Ruixue Qu; Qing Feng; Xiaonan Li; Fan Zhang; Yuehui She (Fuel, 2024)

Ladder type covalent organic frameworks constructed with natural units for the oxygen and carbon dioxide reduction reactions - Minghao Liu; Shuai Yang; Yubin Fu; Xiubei Yang; Xuewen Li; Jun He; Qing Xu; Gaofeng Zeng (Chemical Engineering Journal, 2024)

Green manure substitution for potassium fertilizer promotes agro-ecosystem multifunctionality via triggering interactions among soil, plant and rhizosphere microbiome - Qing Zeng; Mei Yin; Li-Bo Fu; Brajesh K. Singh; Si-Yi Liu; Hua Chen; An-Hui Ge; Li-Li Han; Li-Mei Zhang (Plant and Soil, 2024)

Impact of a clustered rainfall-induced geo-hydrological disaster on densely populated gully villages in Fuyang District, Hangzhou City, Zhejiang Province, China on 22 July 2023 - Fawu Wang; Bo Zhang; Qing Lü; Hao Ma; Ye Chen; Zijin Fu; Jianyi Wu (Landslides, 2024)

Causes of episodic movement of the Baijiabao landslide based on multiple-time scale analysis - Zhiyong Fu; Dian-Qing Li; Shun Wang; Limin Zhang; Wenqi Du (Landslides, 2024)

Experimental and modeling study of adsorption behavior of CH3I over microchannel reactors - Qing He; Lei Zhang; Peize Han; Man Fu; Guorui Zhu (Process Safety and Environmental Protection, 2024)

Distinct phosphorylation optimizes pathogen-induced PA and ROS bursts - Kaihuai Li; Ruize Zhang; Yong Wang; Fengquan Liu; Zheng Qing Fu (Molecular Plant, 2024)

Synergistic effects of aluminum doping and amino functionalization to enhance adsorption capacity of ultrathin-nanosheet-assembled calcium silicate hydrate architectures for effective removal of Pb2+ and Cu2+ from aqueous solution - Yujin Xing; Shicheng Liu; Wenzhong Wang; Yujie Liang; Junli Fu; Qing Zhou; Lijuan Wang; Shimeng Huang (Journal of Environmental Chemical Engineering, 2024)

Self-assembled oxygen vacancies modified hierarchical hollow tubular Bi2WO6/In2O3 Z-scheme heterojunction for optimized photocatalytic degradation of norfloxacin - Xin Wang; Chuangyun Guo; Xinru Hu; Yifei Xu; Cheng Zhang; Jiamin Wei; Jushi Weng; Yilan Liu; Lianshe Fu; Qing Wang; Tinghai Yang (Journal of Environmental Chemical Engineering, 2024)

The initial magma–fluid evolution of the Laochang porphyry molybdenum deposit in Lancang, Yunnan, SW China: Insights from the in-situ analysis of mica and titanite - Ying-Ying Zhang; Tai-Yi Luo; Yun-Fei Fan; Han-Sheng Long; Yong Yang; Jin-Biao Yang; Fu-Qing Meng (Journal of Asian Earth Sciences, 2024)

Robust silica-graphene oxide nanocomposite membrane for separating NaCl salt from seawater under atmospheric pressure - Shirun Chen; Wenge Chen; Ruxin Yuan; Hui Zhang; Ahmed Elmarakbi; Yong-Qing Fu (Desalination, 2024)

Hybrid LBM and machine learning algorithms for permeability prediction of porous media: A comparative study - Qing Kang; Kai-Qi Li; Jin-Long Fu; Yong Liu (Computers and Geotechnics, 2024)

Effect of Regional Brain Activity Following Repeat Transcranial Magnetic Stimulation in SCA3: A Secondary Analysis of a Randomized Clinical Trial - Xia Liu; Lin Zhang; Hao-Lin Xu; Xia-Hua Liu; Arif Sikandar; Meng-Cheng Li; Xiao-Yue Xia; Zi-Qiang Huang; Na-Ping Chen; Yu-Qing Tu; Jian-Ping Hu; Shi-Rui Gan; et al. (The Cerebellum, 2024)

Stabilization and release of thymol in pre-formed V-type starch: A comparative study with traditional method - Qing Gao; Jiabao Zheng; Paul Van der Meeren; Bin Zhang; Xiong Fu; Qiang Huang (Carbohydrate Polymers, 2024)

Contrasting range changes of Bergenia (Saxifragaceae) species under future climate change in the Himalaya and Hengduan Mountains Region - Li Qiu; Qing-Li Fu; Hans Jacquemyn; Kevin S. Burgess; Jia-Jing Cheng; Zhi-Qiong Mo; Xiao-Dong Tang; Bo-Yun Yang; Shao-Lin Tan (Theoretical and Applied Climatology, 2024)

Genetic architecture of ecological divergence between Oryza rufipogon and Oryza nivara - Qing‐Lin Meng; Cheng‐Gen Qiang; Ji‐Long Li; Mu‐Fan Geng; Ning‐Ning Ren; Zhe Cai; Mei‐Xia Wang; Zi‐Hui Jiao; Fu‐Min Zhang; Xian‐Jun Song; Song Ge (Molecular Ecology, 2024)
Ecological divergence due to habitat difference plays a prominent role in the formation of new species, but the genetic architecture during ecological speciation and the mechanism underlying phenotypic divergence remain less understood. Two wild ancestors of rice ( Oryza rufipogon and Oryza nivara ) are a progenitor‐derivative species pair with ecological divergence and provide a unique system for studying ecological adaptation/speciation. Here, we constructed a high‐resolution linkage map and conducted a quantitative trait locus (QTL) analysis of 19 phenotypic traits using an F 2 population generated from a cross between the two Oryza species. We identified 113 QTLs associated with interspecific divergence of 16 quantitative traits, with effect sizes ranging from 1.61% to 34.1% in terms of the percentage of variation explained (PVE). The distribution of effect sizes of QTLs followed a negative exponential, suggesting that a few genes of large effect and many genes of small effect were responsible for the phenotypic divergence. We observed 18 clusters of QTLs (QTL hotspots) on 11 chromosomes, significantly more than that expected by chance, demonstrating the importance of coinheritance of loci/genes in ecological adaptation/speciation. Analysis of effect direction and v ‐test statistics revealed that interspecific differentiation of most traits was driven by divergent natural selection, supporting the argument that ecological adaptation/speciation would proceed rapidly under coordinated selection on multiple traits. Our findings provide new insights into the understanding of genetic architecture of ecological adaptation and speciation in plants and help effective manipulation of specific genes or gene cluster in rice breeding.

Multi-scale failure mechanisms of hydraulic engineering exposed to seasonally frozen salinization environment: Integrating SBAS-InSAR and mechanical experiments - Zhaoxi Wang; Chen Cao; Qingbo Yu; Qing Wang; Cencen Niu; Jiejie Shen; Kuanxing Zhu; Jing Liu; Mengxia Han; Huicheng Fu; Xun Sun; Weitong Xia; et al. (Science of The Total Environment, 2024)

Lanostane triterpenoids from the fruiting bodies of Ganoderma amboinense - Li Yang; Guan-Hai Dong; Qing-Yun Ma; Qing-Yi Xie; Jiao-Cen Guo; Jia-Ju Lu; You-Gen Wu; Hao-Fu Dai; You-Xing Zhao (Phytochemistry, 2024)

Homoerythrina-type alkaloids with neuroprotective activity from the branches of Cephalotaxus hainanensis Li - Hao Yan; Hao Wang; Peng-Wei Chen; Li Yang; Hui-Qin Chen; Fei Wu; Pei Wang; Hao-Fu Dai; Xiao-Long Huang; Shuang-Qing Zhou; Wen-Li Mei (Phytochemistry Letters, 2024)

Two new monoterpenoids from the roots of Paeonia lactiflora and their neuroprotective activities - Bo Fu; Jin-Ling Zhang; Xin Meng; Jia-Tong Wu; Yan Liu; Yu-Qing Wang; Yi-Qiang Zhang; Juan Pan; Wei Guan; Rui-Feng Fan; Anam Naseem; Hai-Xue Kuang; et al. (Phytochemistry Letters, 2024)

Causes of low mercury levels in fish from the Three Gorges Reservoir, China - Yulei Zhou; Qing Xie; Yongmin Wang; Hongjian Lü; Mei Fu; Dingyong Wang; Jiajia Li (Journal of Hazardous Materials, 2024)

Plastic protective nets: A significant but neglected “reservoir” for priority chemicals as revealed by composition analysis - Wenjing Han; Zhongyu Wang; Qing Xie; Xi Chen; Lihao Su; Huaijun Xie; Jingwen Chen; Zhiqiang Fu (Journal of Hazardous Materials, 2024)

Molar ratio of (-)-epicatechin and (-)-epigallocatechin gallate determined their enzymatic oxidation products and color characteristics - Li Lian; Yuqing Cui; Mingchun Wen; Daniel Granato; Yong-Quan Xu; Yan-Qing Fu; Zongde Jiang; Jiaping Ke; Xiaochun Wan; Liang Zhang (Food Bioscience, 2024)

Phosphorus-containing active esters modified dicyclopentadiene epoxy resins with simultaneously improved flame retardancy, thermal stability, and dielectric properties - Zhenye Fu; Zirui Ma; Jiuhong Liu; Chunhui Li; Chuanmei Liu; Qidong Wang; Liang Song; Qing Yu; Guiqing Cheng; Yuxi Han; Hailong Liu; Zhongwei Wang (Chemical Engineering Journal, 2024)

Manganese doped hollow cobalt oxide catalysts for highly efficient oxygen evolution in wide pH range - Jing-Yi Xie; Fu-Li Wang; Xue-Jun Zhai; Xin Li; Yu-Sheng Zhang; Ruo-Yao Fan; Ren-Qing Lv; Yong-Ming Chai; Bin Dong (Chemical Engineering Journal, 2024)

Ultrathin RhCu bimetallenes for the selective electro-oxidation of glycerol - Qing-Ling Hong; Yue Zhao; Xuan Ai; Yu Ding; Fu-Min Li; Pei Chen; Pu-Jun Jin; Yu Chen (Chemical Engineering Journal, 2024)

Human Bone Marrow Derived-Mesenchymal Stem Cells Treatment for Autoimmune Premature Ovarian Insufficiency - Wen-Qing Ma; Ai-Ping Zhuo; Yuan-Ling Xiao; Meng Gao; Yu-Tao Yang; Li-Chao Tang; Yan-Hong Wu; Dan Tian; Xia-Fei Fu (Stem Cell Reviews and Reports, 2024)

Rheumatoid arthritis is a protective factor against Alzheimer’s disease: a bidirectional two-sample Mendelian randomization study - Guo-Shuai Li; Yong-Ze Yang; Guo-Rong Ma; Peng-Fei Li; Qing-Hao Cheng; An-Ren Zhang; Zhuang-Zhuang Zhang; Fu-Kang Zhang; Xin Yang; Hua Fan; Hong-Zhang Guo (Inflammopharmacology, 2024)

Petrogenesis and tectonic implications of the Silurian adakitic granitoids in the eastern segment of the Qilian Orogenic Belt, Northwest China - Jiao-Long Zhao; Xiao-Jun Huang; Pei-Qing Hu; Zhen-Xi Yang; Ying Fan; Er-Teng Wang; Fu-Bo Yang; Jing-Yu Zhang (Acta Geochimica, 2024)

Distribution of Suitable Habitats for Soft Corals (Alcyonacea) Based on Machine Learning - Minxing Dong; Jichao Yang; Yushan Fu; Tengfei Fu; Qing Zhao; Xuelei Zhang; Qinzeng Xu; Wenquan Zhang (Journal of Marine Science and Engineering, 2024)
The soft coral order Alcyonacea is a common coral found in the deep sea and plays a crucial role in the deep-sea ecosystem. This study aims to predict the distribution of Alcyonacea in the western Pacific Ocean using four machine learning-based species distribution models. The performance of these models is also evaluated. The results indicate a high consistency among the prediction results of the different models. The soft coral order is primarily distributed in the Thousand Islands Basin, Japan Trench, and Thousand Islands Trench. Water depth and silicate content are identified as important environmental factors influencing the distribution of Alcyonacea. The RF, Maxent, and XGBoost models demonstrate high accuracies, with the RF model exhibiting the highest prediction accuracy. However, the Maxent model outperforms the other three models in data processing. Developing a high-resolution, high-accuracy, and high-precision habitat suitability model for soft corals can provide a scientific basis and reference for China’s exploration and research in the deep sea field and aid in the planning of protected areas in the high seas.

Exogenous stimulation-induced biosynthesis of volatile compounds: Aroma formation of oolong tea at postharvest stage - Lin Zeng; Shan Jin; Yan-Qun Xu; Daniel Granato; Yan-Qing Fu; Wei-Jiang Sun; Jun-Feng Yin; Yong-Quan Xu (Critical Reviews in Food Science and Nutrition, 2024)

Effector-triggered and self-regulated plant resistance to insects - Di Wu; Kang Lei; Daowen Wang; Zheng Qing Fu (Trends in Plant Science, 2024)

TT-10 may attenuate ibuprofen-induced ovarian injury in mice by activating COX2-PGE2 and inhibiting Hippo pathway - Hongling Zeng; Qing Wang; Zhenmin Hu; Daying Guo; Zhengli Yan; Hu Fu; Yongfei Zhu (Reproductive Toxicology, 2024)

The joint action of biochar and plant roots on U-stressed soil remediation: Insights from bacteriomics and metabolomics - Nan Li; Yilin Wang; Li Zhou; Dengjiang Fu; Tao Chen; Xiaoming Chen; Qing Wang; Wenkun Zhu (Journal of Hazardous Materials, 2024)

An intelligent dual stimuli-responsive Pickering emulsion for highly efficiently producing waste frying oil-based biodiesel - Jia-Liang Guo; Qing-Qing Sun; Zhong-Qiu Liu; Feng-Xiang Wang; Tingjun Fu; Yujing Liu; Anguo Ying (Journal of Cleaner Production, 2024)

Dimensionally-controlled interlayer spaces of covalent organic frameworks for the oxygen evolution reaction - Minghao Liu; Yubin Fu; Shuai Bi; Shuai Yang; Xiubei Yang; Xuewen Li; George Zheng Chen; Jun He; Qing Xu; Gaofeng Zeng (Chemical Engineering Journal, 2024)

A Numerical Study of Moisture and Ionic Transport in Unsaturated Concrete by Considering Multi-ions Coupling Effect - Zhaozheng Meng; Yufei Zhang; Wei-kang Chen; Chuan-qing Fu; Qing Xiang Xiong; Cheng-lin Zhang; Qing-feng Liu (Transport in Porous Media, 2024)

Recent Developments and Knowledge in Intelligent and Safe Marine Navigation - Mingyang Zhang; Xinyu Zhang; Shanshan Fu; Lei Dai; Qing Yu (Journal of Marine Science and Engineering, 2023)
Marine navigation is the lifeblood of international trade and the global economy, facilitating over 80% of worldwide commerce [...]

Chlorpyrifos induces placental oxidative stress and barrier dysfunction by inducing mitochondrial apoptosis through the ERK/MAPK signaling pathway: In vitro and in vivo studies - Jun Bai; Siwei Deng; Huiyang Fu; Qing Yang; Fazheng Ren; Shenming Zeng; Zhaohui Chen; Ying Yang; Zhenlong Wu (Science of The Total Environment, 2023)

Diverse indole-diterpenoids with protein tyrosine phosphatase 1B inhibitory activities from the marine coral-derived fungus Aspergillus sp. ZF-104 - Fei Zhang; Li Yang; Qing-Yi Xie; Jiao-Cen Guo; Qing-Yun Ma; Lu-Ting Dai; Li-Man Zhou; Hao-Fu Dai; Fan-Dong Kong; Du-Qiang Luo; You-Xing Zhao (Phytochemistry, 2023)

Reduction of excessive unfolded protein response by 4-phenylbutyric acid may mitigate procymidone-induced testicular damage in mice by changing the levels of circRNA Scar and circZc3h4 - Bingyan Xin; Qing Wang; Xuning Wang; Fan Li; Mingxin Bai; Hu Fu; Zhengli Yan; Yongfei Zhu; Xin Huang (Pesticide Biochemistry and Physiology, 2023)

Launching, perceiving, and diminishing of airborne signals - Mikayla Carty; Ruize Zhang; Ziyue Li; Daowen Wang; Zheng Qing Fu (Molecular Plant, 2023)

Bioprocessing of pigeon pea roots by a novel endophytic fungus Penicillium rubens for the improvement of genistein yield using semi-solid-state fermentation with water - Xiao-Jia He; Jiao Jiao; Qing-Yan Gai; Jin-Xian Fu; Yu-Jie Fu; Zi-Yi Zhang; Jie Gao (Innovative Food Science & Emerging Technologies, 2023)

Integration of Sentinel–1 and Landsat–8 data for identifying deformation risk of hydraulic engineering in seasonally frozen salinization regions - Zhaoxi Wang; Chen Cao; Qingbo Yu; Xin Xu; Qing Wang; Cencen Niu; Jiejie Shen; Mengxia Han; Huicheng Fu; Kuanxing Zhu; Jing Liu; Weitong Xia; et al. (CATENA, 2023)

Rising from the dead: the power of genome editing - Hongyuan Zheng; Junyao Zhao; Daowen Wang; Zheng Qing Fu (Science China Life Sciences, 2023)

Andrographolide inhibits the activation of spinal microglia and ameliorates mechanical allodynia - Dan Wang; Yongjian Zheng; Junjing Xie; Wenwen Yu; Zhongteng Lu; Wenping Zhang; Yanling Hu; Jianyuan Fu; Qing Sheng; Zhengbing Lv (Metabolic Brain Disease, 2023)

Characterization of halogenated organic compounds by the Fourier transform ion cyclotron resonance mass spectrometry: A critical review - Shixi Wu; Manabu Fujii; Xin Yang; Qing-Long Fu (Water Research, 2023)

Lanostane triterpenoids with anti-proliferative and PTP1B/α-glucosidase inhibitory activities from the fruiting bodies of Ganoderma calidophilum - Li Yang; Ting-Ting Zhang; Qing-Yun Ma; Qing-Yi Xie; Jiao-Cen Guo; Jia-Ju Lu; Zhi-Fang Yu; Hao-Fu Dai; You-Xing Zhao (Phytochemistry, 2023)

Performance of a recirculated biogas-sparging anaerobic membrane bioreactor system for treating synthetic swine wastewater containing sulfadiazine antibiotic - Xinbo Zhang; Haojie Huang; Qing Du; Fu Gao; Zhiwen Wang; Guangxue Wu; Wenshan Guo; Huu Hao Ngo (Chemical Engineering Journal, 2023)

High efficient alkaline hydrogen evolution catalyzed by W2COx-Ru composite system containing bridged oxygen - Yu Dai; Hong Chuan Fu; Xiao Hui Chen; Qing Zhang; Ting Li; Nian Bing Li; Hong Qun Luo (Chemical Engineering Journal, 2023)

Insights into the roles of DOM in humification during sludge composting: Comprehensive chemoinformatic analysis using FT-ICR mass spectrometry - Jibao Liu; Ning Wang; Manabu Fujii; Zhen Bao; Jinyi Wei; Zhineng Hao; Qing-long Fu; Rongjun Gao; Jingfu Liu; Yuansong Wei (Chemical Engineering Journal, 2023)

Fucoxanthin from marine microalgae: A promising bioactive compound for industrial production and food application - Han Sun; Shufang Yang; Weiyang Zhao; Qing Kong; Changliang Zhu; Xiaodan Fu; Fang Zhang; Zhemin Liu; Yuming Zhan; Haijin Mou; Yongjin He (Critical Reviews in Food Science and Nutrition, 2023)

Current advances in the detection and removal of organic arsenic by metal-organic frameworks - Wen-Qing Ding; Lazhar Labiadh; Lei Xu; Xiao-Ying Li; Chen Chen; Ming-Lai Fu; Baoling Yuan (Chemosphere, 2023)

Development and testing of a ground recognition system for tractor field operations - Chang-kai Wen; Hong-wei Wang; Chang-hai Luo; Wei-qiang Fu; Qing-zhen Zhu; Yan-xin Yin; Zhi-jun Meng (Computers and Electronics in Agriculture, 2023)

Cyclic response of unsaturated weathered red mudstone under various conditions of initial static shear stress and moisture content - Haihong Yu; Jing Ye; Haiying Fu; Yuwei Zhong; Ran Yuan; Yulan Qing; Qionglin Li (Soil Dynamics and Earthquake Engineering, 2023)

Multi-omics analysis reveals the mechanism of calcium-reduced quality deterioration in mechanically injured green pepper fruit - Lili Ma; Yanyan Zheng; Zhaoze Sang; Yonghong Ge; Chunmei Bai; Anzhen Fu; Qing Wang; Christopher B. Watkins; Jinhua Zuo (Postharvest Biology and Technology, 2023)

The conversion of organic sulfur and strontium into inorganic compounds during the molten salt oxidation of mixed resin - Xin Liu; Yong-De Yan; Yang-Hai Zheng; Wen-Da Xu; Yun Xue; Jing-Ping Wang; Qing-Guo Zhang; Yue-Lin Wang; Fu-Qiu Ma (Journal of Environmental Chemical Engineering, 2023)

The youngest lunar zircon reveals an extremely fractionated nature of Chang’e-5 basalt - Qin Zhou; Yu Liu; Saihong Yang; Qiu-Li Li; Yi Chen; Guangliang Zhang; Hongbo Zhang; Bin Liu; Dawei Liu; Jianjun Liu; Fu-Yuan Wu; Xian-Hua Li; et al. (Geochimica et Cosmochimica Acta, 2023)

Carbon source shaped microbial ecology, metabolism and performance in denitrification systems - Yuan Pan; Rui-Zhe Sun; Yan Wang; Guan-Lin Chen; Ying-Ying Fu; Han-Qing Yu (Water Research, 2023)

Influence of acid rain climate environment on deterioration of shear strength parameters of natural residual expansive soil - Jin Chang; Yong-Fu Xu; Jie Xiao; Lei Wang; Jian-Qing Jiang; Jian-Xiong Guo (Transportation Geotechnics, 2023)

Hg bioaccumulation in the aquatic food web from tributaries of the Three Gorges Reservoir, China and potential consumption advisories - Xueheng Wang; Qing Xie; Yongmin Wang; Hongjian Lü; Mei Fu; Dingyong Wang; Jiajia Li (Journal of Hazardous Materials, 2023)

Application of cationic membrane electrolysis on the recovery of copper from thiosulfate solutions - Binchuan Li; Rongxuan Zhou; Jianshe Chen; Daxue Fu; Kuiren Liu; Mingxin Li; Wubin Li; Qing Han (Journal of Cleaner Production, 2023)

Selective enrichment and extraction of well-catalyzed perovskites on melting-microwave heating process from blast furnace slag - Jun Xie; Qing Ye; Fu Yang; Gongming Qian; Haijun Zhang (Journal of Cleaner Production, 2023)

Structural characterization of a novel fucosylated trisaccharide prepared from bacterial exopolysaccharides and evaluation of its prebiotic activity - Mengshi Xiao; Xinmiao Ren; Jiaying Cheng; Xiaodan Fu; Rong Li; Changliang Zhu; Qing Kong; Haijin Mou (Food Chemistry, 2023)

A global inertial permeability for fluid flow in rock fractures: Criterion and significance - Jia-Qing Zhou; Fu-Shuo Gan; Changdong Li; Huiming Tang (Engineering Geology, 2023)

Performance and mechanism of calcium peroxide reducing H2S production from sludge anaerobic fermentation - Yunhao Xu; Qizi Fu; Wenming Wang; Fan Yang; Xuemei Li; Fengming Song; Yanguang Qing; Ziqi Lin; Weiqi Long; Dongbo Wang (Chemical Engineering Journal, 2023)

mTORC1/rpS6 and mTORC2/PKC regulate spermatogenesis through Arp3-mediated actin microfilament organization in Eriocheir sinensis - Zhen-Fang Li; Hong-Yu Qi; Jia-Ming Wang; Zhan Zhao; Fu-Qing Tan; Wan-Xi Yang (Cell and Tissue Research, 2023)

Two lanostane triterpenoids with α -glucosidase inhibitory activity from the fruiting bodies of Ganoderma weberianum - De Xian Kong; Qing Yun Ma; Li Yang; Qing Yi Xie; Chun Ying Deng; Hao Fu Dai; Yan Hua; You Xing Zhao (Natural Product Research, 2023)

Two new bibenzyls from Pleione grandiflora (Rolfe) Rolfe and their antioxidant activity - Wei Li; Jia-Rui Fu; Li-Jun Zheng; Lin Ni; Jun-Qing Liu; Jun-Wen Zhai; Zhuang Zhou; Sha-Sha Wu (Natural Product Research, 2023)

Organic carbon preservation in wetlands: Iron oxide protection vs. thermodynamic limitation - Fu-Sheng Sun; Chao Ma; Guang-Hui Yu; Yakov Kuzyakov; Yun-Chao Lang; Ping-Qing Fu; Li-Jun Guo; Hui Henry Teng; Cong-Qiang Liu (Water Research, 2023)

Efficient lipid synthesis of Chlorella pyrenoidosa promoted under heavy metals from electric arc furnace slag - Qing Yu; Tian-Ji Liu; Ya-Nan Zeng; Yi-Tong Wang; Jun-Guo Li; Yu-Ran Wang; Le-Le Kang; Rui Ji; Fu-Ping Wang; Xiao-Man Wang; Bao Liu; Shuang Cai; et al. (Journal of Cleaner Production, 2023)

Urinary Amino-PAHs in relation to diesel engine emissions and urinary mutagenicity - Junfeng (Jim) Zhang; Yuxin Zheng; Roel Vermeulen; Xing (Lucy) Liu; Yufei Dai; Wei Hu; Linchen He; Yan Lin; Dianzhi Ren; Huawei Duan; Yong Niu; Jun Xu; et al. (International Journal of Hygiene and Environmental Health, 2023)

TiO2 nanoparticles affect spermatogenesis and adhesion junctions via the ROS-mediated mTOR signalling pathway in Eriocheir sinensis testes - Lan-Min Wang; Ke Jia; Zhen-Fang Li; Hong-Yu Qi; Ding-Xi Liu; Ya-Jing Liang; Shuang-Li Hao; Fu-Qing Tan; Wan-Xi Yang (Environmental Pollution, 2023)

Weighted low-discrepancy samplings: A novel method for slope system reliability analysis - Tao Wang; Jian Ji; Guoyang Fu; Qing Lü (Computers and Geotechnics, 2023)

3D-printed stretchable sensor based on double network PHI/PEDOT:PSS hydrogel annealed with cosolvent of H2O and DMSO - Xiu-Yan Cheng; Shu-Qiang Peng; Li-Xin Wu; Qing-fu Sun (Chemical Engineering Journal, 2023)

AIWW: a new nutrition-screening tool for the oncologic population - Yi-Zhong Ge; Zhen-Ming Fu; Qi Zhang; Meng-Meng Song; Guo-Tian Ruan; Xi Zhang; Xiao-Wei Zhang; Xiang-Rui Li; Kang-Ping Zhang; Meng Tang; Xiao-Yue Liu; Ming Yang; et al. (Science China Life Sciences, 2023)

Microecological health assessment of water environment and sediment based on metagenomics: a case study of Guixi River in Chongqing, China - Xia Su; Fu-qing Xu; Shang-jie Chen; Fang Gou; Yun-chun Shi; Zhi-lin Xing; Ren-qing Peng; Ying-ying Deng; Ten Zhang; Juan Xiong; Tian-tao Zhao (Environmental Monitoring and Assessment, 2023)

Effect of humic acid-modified attapulgite on polycyclic aromatic hydrocarbon adsorption and release from paddy soil into the overlying water in a rice-crab coculture paddy ecosystem and the underlying process - Nan Sun; Jin Liu; Bo-Wei Qi; Li-Li Lu; Hui-Ling Du; Shuang Li; Chang-Qing Li; Si-Wen Jiang; Zi-Jian Wang; An-Pei Yang; Guang-Lei Zhu; Tian-Yi Wang; et al. (Chemosphere, 2023)

TT-10 may elevate YAP and repair mouse uterine damage resulting from the inhibition effect of ibuprofen on COX2-PGE2 and YAP - Qing Wang; Bingyan Xin; Xuning Wang; Fan Li; Hu Fu; Zhengli Yan; Yongfei Zhu (Toxicology Letters, 2023)

Bioactivated and selective: A promising new family of nematicides with a novel mode of action - Liyuan You; Di Wu; Ruize Zhang; Daowen Wang; Zheng Qing Fu (Molecular Plant, 2023)

Polyacrylonitrile fiber with light-driven intelligent reversible and switchable wettability as an environmental benign solid base for biodiesel production - Huan-Xing Zhou; Qing-Qing Sun; Zhong-Qiu Liu; Jie-Wen Duan; Tingjun Fu; Yujing Liu; Anguo Ying (Journal of Cleaner Production, 2023)

BCE-Net: Reliable building footprints change extraction based on historical map and up-to-date images using contrastive learning - Cheng Liao; Han Hu; Xuekun Yuan; Haifeng Li; Chao Liu; Chunyang Liu; Gui Fu; Yulin Ding; Qing Zhu (ISPRS Journal of Photogrammetry and Remote Sensing, 2023)

Combined effects of light pollution and vegetation height on behavior and body weight in a nocturnal rodent - Ling-Ying Shuai; Li-Qing Wang; Yang Xia; Jin-Yu Xia; Kang Hong; Ya-Nan Wu; Xin-Yi Tian; Fu-Shun Zhang (Environmental Pollution, 2023)

Methane distribution and sea-to-air methane flux in the Dongsha area of the South China Sea - Cuiling Xu; Zhilei Sun; Qing Li; Xianrong Zhang; Xilin Zhang; Bin Zhai; Qiang Fu; Yuhai Sun; Wei Geng; Hong Cao; Ye Chen; Nengyou Wu (Continental Shelf Research, 2023)

Modulating the interfacial built-in electric field in oxygen vacancies-enriched Ru/MxOy@C (M = V, Nb, Ta) ordered macroporous heterojunctions for electrocatalytic hydrogen production - Xiao Hui Chen; Hong Chuan Fu; Xiao Lin Li; Ting Li; Qing Zhang; Zi Qing Li; Yuan Hao Luo; Jing Lei Lei; Nian Bing Li; Hong Qun Luo (Chemical Engineering Journal, 2023)

The PIWI-specific insertion module helps load longer piRNAs for translational activation essential for male fertility - Xin Wang; Di-Hang Lin; Yue Yan; An-Hui Wang; Jiaoyang Liao; Qian Meng; Wen-Qing Yang; Heng Zuo; Min-Min Hua; Fengjuan Zhang; Hongwen Zhu; Hu Zhou; et al. (Science China Life Sciences, 2023)

Correlation Analysis of Molecularly-Defined Cortical Interneuron Populations with Morpho-Electric Properties in Layer V of Mouse Neocortex - Jun-Wei Cao; Xiao-Yi Mao; Liang Zhu; Zhi-Shuo Zhou; Shao-Na Jiang; Lin-Yun Liu; Shu-Qing Zhang; Yinghui Fu; Wen-Dong Xu; Yong-Chun Yu (Neuroscience Bulletin, 2023)

Bone Marrow Mesenchymal Stem Cell-Derived Exosomal KLF4 Alleviated Ischemic Stroke Through Inhibiting N6-Methyladenosine Modification Level of Drp1 by Targeting lncRNA-ZFAS1 - Qing-Song Wang; Rong-Jun Xiao; Jun Peng; Zheng-Tao Yu; Jun-Qi Fu; Ying Xia (Molecular Neurobiology, 2023)

Retraction Note: Two New Coordination Polymers: Selective Detection of Cu(II) Ion and Treatment Activity on Inner Ear Damage - Jing Liu; Wan-Dong She; Fu-Sen Wang; Qing Zhou (Journal of Fluorescence, 2023)

QTL mapping and identification of candidate genes for cold tolerance at the germination stage in wild rice - Ying-Hua Pan; Bao-Xuan Nong; Lei Chen; Xing-Hai Yang; Xiu-Zhong Xia; Zong-Qiong Zhang; Dong-Jin Qing; Ju Gao; Cheng-Cui Huang; Dan-Ting Li; Guo-Fu Deng (Genes & Genomics, 2023)

Polydopamine-modification of a magnetic composite constructed from citric acid–cross-linked cyclodextrin and graphene oxide for dye removal from waters - Qing-Di Hu; Hong-Liu Jiang; Kwok-Ho Lam; Zhi-Peng Hu; Zhi-Jie Liu; Hua-Ying Wang; Yong-Yu Yang; Omirserik Baigenzhenov; Ahmad Hosseini-Bandegharaei; Fu-An He (Environmental Science and Pollution Research, 2023)

Long-term cadmium exposure induces chronic obstructive pulmonary disease-like lung lesions in a mouse model - Wen-Jing Wang; Kun Peng; Xue Lu; Yan-Yan Zhu; Zhao Li; Qing-Hua Qian; Ya-Xin Yao; Lin Fu; Yan Wang; Yi-Chao Huang; Hui Zhao; Hua Wang; et al. (Science of The Total Environment, 2023)

Isolation and structure determination of superbcyclin A, a cyclic nonapeptide from Dianthus superbus - Qing Zhang; Jing-Hui Yang; Yu-Lan Du; Xu-Yang Fu; Wu-Yang Liu; Yi-Qin Zeng; Shu-Hui Liu; Jun-Mian Tian; Jin-Ming Gao (Phytochemistry Letters, 2023)

Two new α-pyrone derivatives from sponge-derived fungus Curvularia sp. ZYX-Z-4 - Qing-Hui Yan; Li Yang; Qing-Yun Ma; Qing-Yi Xie; Hao-Fu Dai; Ying Fu; You-Xing Zhao (Phytochemistry Letters, 2023)

Removal of iodide anions in water by silver nanoparticles supported on polystyrene anion exchanger - Li Li; Su-Juan Yu; Rong-Gang Zheng; Peng Li; Qing-Cun Li; Jing-Fu Liu (Journal of Environmental Sciences, 2023)

Effects of dietary oat supplementation on carcass traits, muscle metabolites, amino acid profiles, and its association with meat quality of Small-tail Han sheep - Li-wei Wang; Shao-feng Su; Jie Zhao; Xiao-long He; Shao-yin Fu; Biao Wang; Yun-fei Wang; Da-qing Wang; Na-na Yun; Xin Chen; Damien P Belobrajdic; Terigele; et al. (Food Chemistry, 2023)

Gestational cadmium exposure disrupts fetal liver development via repressing estrogen biosynthesis in placental trophoblasts - Yi-Ting Fu; Jin Zhang; Wei-Bo Liu; Yu-Feng Zhang; Shuang Zhang; Lu-Lu Tan; Qing Lin; Kong-Wen Ou-Yang; Yong-Wei Xiong; Wei Chang; Hao Li; Jun-Ying Yu; et al. (Food and Chemical Toxicology, 2023)

Blue LED light promoting the growth, accumulation of high-value isoflavonoids and astragalosides, antioxidant response, and biosynthesis gene expression in Astragalus membranaceus (Fisch.) Bunge hairy root cultures - Qing-Yan Gai; Xue Feng; Jiao Jiao; Xiao-Jie Xu; Jin-Xian Fu; Xiao-Jia He; Yu-Jie Fu (Plant Cell, Tissue and Organ Culture (PCTOC), 2023)

OrMKK3 Influences Morphology and Grain Size in Rice - Ying Hua Pan; Li Jun Gao; Yun Tao Liang; Yan Zhao; Hai Fu Liang; Wei Wei Chen; Xing Hai Yang; Dong Jin Qing; Ju Gao; Hao Wu; Juan Huang; Wei Yong Zhou; et al. (Journal of Plant Biology, 2023)

Response of Salmonella enterica serovar Typhimurium to alginate oligosaccharides fermented with fecal inoculum: integrated transcriptomic and metabolomic analyses - Jiaying Cheng; Mengshi Xiao; Xinmiao Ren; Francesco Secundo; Ying Yu; Shihao Nan; Weimiao Chen; Changliang Zhu; Qing Kong; Youtao Huang; Xiaodan Fu; Haijin Mou (Marine Life Science & Technology, 2023)
Alginate oligosaccharides (AOS), extracted from marine brown algae, are a common functional feed additive; however, it remains unclear whether they modulate the gut microbiota and microbial metabolites. The response of Salmonella enterica serovar Typhimurium, a common poultry pathogen, to AOS fermented with chicken fecal inocula was investigated using metabolomic and transcriptomic analyses. Single-strain cultivation tests showed that AOS did not directly inhibit the growth of S . Typhimurium. However, when AOS were fermented by chicken fecal microbiota, the supernatant of fermented AOS (F-AOS) exhibited remarkable antibacterial activity against S . Typhimurium, decreasing the abundance ratio of S . Typhimurium in the fecal microbiota from 18.94 to 2.94%. Transcriptomic analyses showed that the 855 differentially expressed genes induced by F-AOS were mainly enriched in porphyrin and chlorophyll metabolism, oxidative phosphorylation, and Salmonella infection-related pathways. RT-qPCR confirmed that F-AOS downregulated key genes involved in flagellar assembly and the type III secretory system of S . Typhimurium, indicating metabolites in F-AOS can influence the growth and metabolism of S . Typhimurium. Metabolomic analyses showed that 205 microbial metabolites were significantly altered in F-AOS. Among them, the increase in indolelactic acid and 3-indolepropionic acid levels were further confirmed using HPLC. This study provides a new perspective for the application of AOS as a feed additive against pathogenic intestinal bacteria.

Anthraquinones with potential antiproliferative activities from the fruits of Morinda citrifolia - Zhang-Yang Shen; Ying-Ying Zhao; Ze-Hua Qiao; Zhen Xie; Ruo-Qing Guan; Ze-Yu Liu; Yan-Ping Liu; Guang-Ying Chen; Yan-Hui Fu (Natural Product Research, 2023)

Heavy metals in influent and effluent from 146 drinking water treatment plants across China: Occurrence, explanatory factors, probabilistic health risk, and removal efficiency - Kunfeng Zhang; Sheng Chang; Qi Zhang; Yunsong Bai; Enrui Wang; Moli Zhang; Qing Fu; Liangliang Wei; Yanling Yu (Journal of Hazardous Materials, 2023)

Fluid evolution and ore genesis of the A'gui Cu deposit in southern Great Xing'an Range, Northeast China: Evidence from fluid inclusion and C–H–O–S–Pb isotopes - Xue Wang; Ke-yong Wang; Li-juan Fu; Qing-ying Zhao; Qing-fei Sun; Chao Zhang (Geochemistry, 2023)

Physicochemical and functional properties of chitosan-based edible film incorporated with Sargassum pallidum polysaccharide nanoparticles - Ke Zhang; Qing Chen; Jie Xiao; Lijun You; Siming Zhu; Chao Li; Xiong Fu (Food Hydrocolloids, 2023)

Soil nitrogen transformation in different land use and implications for karst soil nitrogen loss controlling - Zhong-Jun Wang; Fu-Jun Yue; Li-Li Xue; Yu-Chun Wang; Cai-Qing Qin; Jie Zeng; Hu Ding; Yu-Cong Fu; Si-Liang Li (CATENA, 2023)

Downscaling algorithms for annual TRMM data based on climatic and orographic variables over the Qinling Mountains, China - Qing Meng; Ranjan Sarukkalige; Guobin Fu; Guan Wang; Wenhao Jia; Zhuang Liu; Hongying Bai; Xiaobang Peng; Shanhong Zhang (Theoretical and Applied Climatology, 2023)

Biomarkers of aging - Hainan Bao; Jiani Cao; Mengting Chen; Min Chen; Wei Chen; Xiao Chen; Yanhao Chen; Yu Chen; Yutian Chen; Zhiyang Chen; Jagadish K. Chhetri; Yingjie Ding; et al. (Science China Life Sciences, 2023)

Are the altitudinal patterns of plant diversity derived from field surveys consistent with those from empirical integrated methods? - Qing-hua Zhan; Zhi-hao Fu; Ya-dong Zhou; Xue Yan; Qing-feng Wang (Journal of Mountain Science, 2023)

Triassic granitoids in the East Kunlun Orogenic Belt, Northwestern China: magmatic source and implications for geodynamic evolution - Zhi-He Xu; Wei Xin; Xiao-Dong Zhou; Qing-Lin Xu; Fu-Wen Li; Zhao-Jun Song (International Geology Review, 2023)

Knockdown of Sly-miR160a using short tandem target mimic (STTM) enhanced expression of auxin signaling genes and delayed postharvest ripening of tomato fruit - Francine Ngaffo Mekontso; Shuhui Wu; Ruizuo Fu; Wen Li; Lanhuan Meng; Qing Wang; Jiangkuo Li; Hongmiao Song; Xiangbin Xu (Postharvest Biology and Technology, 2023)

Two new indole alkaloids isolated from a mangrove-derived fungus Colletotrichum sp. HD-1 - Dan He; Qing-Yun Ma; Li Yang; Qing-Yi Xie; Hong-Juan Zhu; Hao-Fu Dai; You-Gen Wu; Dong-Mei Yang; You-Xing Zhao (Phytochemistry Letters, 2023)

Valorization of manganese residue to construct amorphous MnO2/α-Fe2O3@geopolymer Z-scheme heterojunction for efficient Cr(VI) reduction and ciprofloxacin degradation - Xiunan Cai; Qingling Liu; Qing Yang; Fuzheng Fu; Yanjuan Zhang; Tao Gan; Huayu Hu; Zuqiang Huang (Journal of Cleaner Production, 2023)

The mobility and fate of Cr during aging of ferrihydrite and ferrihydrite organominerals - Yao Zhao; Alba Otero-Fariña; Ke-Qing Xiao; Oliver W. Moore; Steven A. Banwart; Fu-Jun Ma; Qing-Bao Gu; Caroline L. Peacock (Geochimica et Cosmochimica Acta, 2023)

Modulation of non-covalent wet adhesion and cohesion via proximally immobilized non-lysine pair structure - Pengxu Wang; Qing Liu; Wenliang Fu; Chao Zhang; Guiling Cai; Weiwei Xing; Hongliang Dai; Hongya Geng; Donggang Xu (Chemical Engineering Journal, 2023)

Spinal MCP-1 Contributes to Central Post-stroke Pain by Inducing Central Sensitization in Rats - Fei Yang; Jun-Jie Jing; Si-Yin Fu; Xiu-Zhu Su; Yu-Ling Zhong; Dong-Sheng Chen; Xiao-Zhi Wu; Yi-Qing Zou (Molecular Neurobiology, 2023)

PTSA-catalyzed selective synthesis and antibacterial evaluation of 1,2-disubstituted benzimidazoles - Jiaxu Fu; Yuandong Yue; Kejun Liu; Shuang Wang; Yiliang Zhang; Qing Su; Qiang Gu; Feng Lin; Yumin Zhang (Molecular Diversity, 2023)

A new phase of treasure hunting in plant genebanks - Guangwei Li; Zhiyong Wang; Yuxuan Meng; Zheng Qing Fu; Daowen Wang; Kunpu Zhang (Molecular Plant, 2023)

Discovery of natural polyphenols from the wild vegetable Suaeda salsa L. with potential cardioprotective functions - Kuo Xu; Xinhai Cui; Xia Ren; Jie Meng; Xianjun Fu; Qing Xia (Food Chemistry, 2023)

Molecular encapsulation of cinnamaldehyde in V-type starch: The role of solvent and temperature - Qing Gao; Yanan Sun; Ruolan He; Jiabao Zheng; Bin Zhang; Chin Ping Tan; Xiong Fu; Qiang Huang (Food Hydrocolloids, 2023)

A hybrid deep learning model for regional O3 and NO2 concentrations prediction based on spatiotemporal dependencies in air quality monitoring network - Cui-lin Wu; Hong-di He; Rui-feng Song; Xing-hang Zhu; Zhong-ren Peng; Qing-yan Fu; Jun Pan (Environmental Pollution, 2023)

rTFPI Protects Cardiomyocytes from Hypoxia/Reoxygenation Injury through Inhibiting Autophagy and the Class III PI3K/Beclin-1 Pathway - Runan Yan; Wei Gao; Wenjia Chen; Yue Liu; Li Shen; Yue Dai; Rui Xu; Qing Chang; Yu Fu; Yong Zhao (Cell Biochemistry and Biophysics, 2023)

Selenium Deficiency Caused Fibrosis as an Oxidative Stress-induced Inflammatory Injury in the Lungs of Mice - Yu-xin Fu; Yi-bo Wang; Qing-wei Bu; Meng-yao Guo (Biological Trace Element Research, 2023)

Hydraulic determinants of drought-induced tree mortality and changes in tree abundance between two tropical forests with different water availability - Yong-Qiang Wang; Hui-Qing Song; Ya-Jun Chen; Pei-Li Fu; Jiao-Lin Zhang; Kun-Fang Cao; Shi-Dan Zhu (Agricultural and Forest Meteorology, 2023)

The MocR family transcriptional regulator DnfR has multiple binding sites and regulates Dirammox gene transcription in Alcaligenes faecalis JQ135 - Si‐Qiong Xu; Xiao Wang; Lu Xu; Ke‐Xin Wang; Yin‐Hu Jiang; Fu‐Yin Zhang; Qing Hong; Jian He; Shuang‐Jiang Liu; Ji‐Guo Qiu (Environmental Microbiology, 2023)
Microbial ammonia oxidation is vital to the nitrogen cycle. A biological process, called Dirammox ( dir ect amm onia ox idation, NH 3 →NH 2 OH→N 2 ), has been recently identified in Alcaligenes ammonioxydans and Alcaligenes faecalis . However, its transcriptional regulatory mechanism has not yet been fully elucidated. The present study characterized a new MocR‐like transcription factor DnfR that is involved in the Dirammox process in A. faecalis strain JQ135. The entire dnf cluster was composed of 10 genes and transcribed as five transcriptional units, that is, dnfIH , dnfR , dnfG , dnfABCDE and dnfF . DnfR activates the transcription of dnfIH , dnfG and dnfABCDE genes, and represses its own transcription. The intact 1506‐bp dnfR gene was required for activation of Dirammox. Electrophoretic mobility shift assays and DNase I footprinting analyses showed that DnfR has one binding site in the dnfH ‐ dnfR intergenic region and two binding sites in the dnfG ‐ dnfA intergenic region. Three binding sites of DnfR shared a 6‐bp repeated conserved sequence 5′‐GGTCTG‐N 17 ‐GGTCTG‐3′ which was essential for the transcription of downstream target genes. Cysteine and glutamate act as possible effectors of DnfR to activate the transcription of transcriptional units of dnfG and dnfABCDE , respectively. This study provided new insights in the transcriptional regulation mechanism of Dirammox by DnfR in A. faecalis JQ135.

Comprehensive understanding of DOM reactivity in anaerobic fermentation of persulfate-pretreated sewage sludge via FT-ICR mass spectrometry and reactomics analysis - Jibao Liu; Chenlu Wang; Zhineng Hao; Gen Kondo; Manabu Fujii; Qing-Long Fu; Yuansong Wei (Water Research, 2023)

Ag-Fe3O4 nanozyme with peroxidase-like activity for colorimetric detection of sulfide ions and dye degradation - Yong Wang; Yue Ding; Yiyun Tan; Xiaohui Liu; Lixian Fu; Weixia Qing (Journal of Environmental Chemical Engineering, 2023)

Highly efficient harvesting of vibration energy for complex wastewater purification using Bi5Ti3FeO15 with controlled oxygen vacancies - Ying Zheng; Xinyan Wu; Yongcheng Zhang; Yanqiang Li; Weiquan Shao; Jie Fu; Qing Lin; Jinshan Tan; Shouwu Gao; Wanneng Ye; Haitao Huang (Chemical Engineering Journal, 2023)

CRISPR-based DNA methylation editing of NNT rescues the cisplatin resistance of lung cancer cells by reducing autophagy - Chi Xu; Shuyun Jiang; Xingyu Ma; Zeyong Jiang; Youguang Pan; Xiang Li; Liying Zhang; Hao Zhou; Shen Chen; Xiumei Xing; Liping Chen; Wenfan Fu; et al. (Archives of Toxicology, 2023)

Water microecology is affected by seasons but not sediments: A spatiotemporal dynamics survey of bacterial community composition in Lake Changshou—The largest artificial lake in southwest China - Ai-ling Chen; Fu-qing Xu; Xia Su; Fu-pan Zhang; Wan-chao Tian; Shang-jie Chen; Fang Gou; Zhi-lin Xing; Jin-xin Xiang; Juan Li; Tian-tao Zhao (Marine Pollution Bulletin, 2023)

The growth-regulating factor PdbGRF1 positively regulates the salt stress response in Populus davidiana × P. bolleana - Zhong-Yuan Liu; Ya-Ting Han; Chun-Yao Wang; Xiao-Jin Lei; Yuan-Yuan Wang; Wen-Fang Dong; Qing-Jun Xie; Yu-Jie Fu; Cai-Qiu Gao (Plant Science, 2023)

Learn then match: A fast coarse-to-fine depth image-based indoor localization framework for dark environments via deep learning and keypoint-based geometry alignment - Qing Li; Rui Cao; Jiasong Zhu; Hao Fu; Baoding Zhou; Xu Fang; Sen Jia; Shenman Zhang; Kanglin Liu; Qingquan Li (ISPRS Journal of Photogrammetry and Remote Sensing, 2023)

Four-armed host-defense peptidomimetics-augmented vanadium carbide MXene-based microneedle array for efficient photo-excited bacteria-killing - Xiaoqian Feng; Dongyi Xian; Jintao Fu; Rui Luo; Wenhao Wang; Yuwei Zheng; Qing He; Zhan Ouyang; Shaobin Fang; Wancong Zhang; Daojun Liu; Shijie Tang; et al. (Chemical Engineering Journal, 2023)

Novel ionic complex with flame retardancy and ultrastrong toughening effect on epoxy resin - Gaobo Lou; Qingqing Rao; Qing Li; Zhicheng Bai; Xingwei He; Youhua Xiao; Jinfeng Dai; Shenyuan Fu; Shengxiang Yang (Chemical Engineering Journal, 2023)

Near-infrared I/II emission and absorption carbon dots via constructing localized excited/charge transfer state for multiphoton imaging and photothermal therapy - Wen-Bo Zhao; Dan-Dan Chen; Kai-Kai Liu; Yong Wang; Rui Zhou; Shi-Yu Song; Fu-Kui Li; Lai-Zhi Sui; Qing Lou; Lin Hou; Chong-Xin Shan (Chemical Engineering Journal, 2023)

Dysregulation of Circulatory Levels of lncRNAs in Parkinson’s Disease - Ting Huang; Jin-Ying Zhao; Rong-Rong Pan; Teng Jiang; Xin-Xin Fu; Qing Huang; Xi-Xi Wang; Peng-Yu Gong; You-Yong Tian; Ying-Dong Zhang (Molecular Neurobiology, 2023)

Identification of suitable reference genes for quantitative gene expression analysis in clam Cyclina sinensis under salinity stress and Vibrio infection - Fengjuan Jiang; Qingyao Wang; Jingjing Du; Fu Lü; Qing Nie; Weihong Zhao (Journal of Oceanology and Limnology, 2023)

Cymbopogom Citratus Essential Oils: A Promising Source of Antifungals Against Panax Notoginseng-Associated Pathogenic Fungi - Jing Yang; Tian T. Li; Ying Y. Huo; Heng Y. Huang; Qing H. Meng; Fu R. Xu; Xian Dong (Current Microbiology, 2023)

Social isolation does not alter the relationship between flexibility in metabolic rate and growth in grass carp (Ctenopharyngodon idella) under changing food availability - Chun-Yan Sun; Shi-Jian Fu; Ling-Qing Zeng (Journal of Comparative Physiology B, 2023)

Effects of oxygen content on gaseous and solid products during molten salt oxidation of cation exchange resins - Yun Xue; Yue-Lin Wang; Yang-Hai Zheng; Yu-Sheng Yang; Wen-Da Xu; Yong-De Yan; Ran Zhao; Qing-Guo Zhang; Xin Liu; Fu-Qiu Ma; Mi-Lin Zhang (Environmental Science and Pollution Research, 2022)

Highly efficient removal of hexavalent chromium by magnetic Fe–C composite from reed straw and electric furnace dust waste - Fu-Ping Wang; Ya-Nan Zeng; Yi-Tong Wang; Jun-Guo Li; Xi Zhang; Ai-Min Ji; Le-Le Kang; Rui Ji; Qing Yu; Di Gao; Xiao-Man Wang; Zhen Fang (Environmental Science and Pollution Research, 2022)

The landscape of aging - Yusheng Cai; Wei Song; Jiaming Li; Ying Jing; Chuqian Liang; Liyuan Zhang; Xia Zhang; Wenhui Zhang; Beibei Liu; Yongpan An; Jingyi Li; Baixue Tang; et al. (Science China Life Sciences, 2022)

Inhibition of Microglial NLRP3 with MCC950 Attenuates Microglial Morphology and NLRP3/Caspase-1/IL-1β Signaling In Stress-induced Mice - Qing Liu; Man-Man Zhang; Min-Xia Guo; Qiu-Ping Zhang; Na-Zhi Li; Jie Cheng; Shi-Le Wang; Guang-Hui Xu; Cheng-Fu Li; Ji-Xiao Zhu; Li-Tao Yi (Journal of Neuroimmune Pharmacology, 2022)

Failure mode and genesis of bare dispersive soil slope in the cold dry region: insights from Southwest Songnen Plain, China - Yan Han; Qing Wang; Cencen Niu; Huicheng Fu; Jing Liu; Mengxia Han; Sen Lin; Muhammad Ammar (Bulletin of Engineering Geology and the Environment, 2022)

Four sesquiterpenoids from the vegetable raw material Schisandra chinensis (Turcz.) Baill.: leaves and stems - Yong-Cheng Yang; Lu-Qi Liu; Kun-Jun Wang; Xue-Qing Zhang; San-Peng Fan; Xiao-Xu Gao; An-Hua Wang; Jing-Ming Jia; Chun-Wang Fu (Natural Product Research, 2022)

Evolution mechanism and deformation stability analysis of rock slope block toppling for early warnings - Jian-qiao Mu; Tian-tao Li; Xiang-jun Pei; Run-qiu Huang; Fu-an Lan; Xue-qing Zou (Natural Hazards, 2022)

Genome analysis and 2’-fucosyllactose utilization characteristics of a new Akkermansia muciniphila strain isolated from mice feces - Wei Gao; Mengshi Xiao; Ziqiang Gu; Xiaodan Fu; Xinmiao Ren; Ying Yu; Zhemin Liu; Changliang Zhu; Qing Kong; Haijin Mou (Molecular Genetics and Genomics, 2022)

The association between hearing threshold and urinary personal care and consumer product metabolites in middle-aged and elderly people from the USA - Yan-Peng Fu; Wen-Yu Chen; Li-Qing Guo; Ya-Qiong Zhu; Jia-Sheng Yuan; Yue-Hui Liu (Environmental Science and Pollution Research, 2022)

Analysis and estimation of nonpoint source pollution under different land use in Anjiagou watershed, Gansu, China - Yanting Hu; Zisheng Xing; Fu Zhang; Qing Tian; Nasem Badreldin; Jinmei Zhao (Environmental Science and Pollution Research, 2022)

Genistein Alleviates Oxidative Stress and Inflammation in the Hypothalamic Paraventricular Nucleus by Activating the Sirt1/Nrf2 Pathway in High Salt-Induced Hypertension - Li-Gang Niu; Na Sun; Kai-Li Liu; Qing Su; Jie Qi; Li-Yan Fu; Guo-Rui Xin; Yu-Ming Kang (Cardiovascular Toxicology, 2022)

mTORC1/C2 regulate spermatogenesis in Eriocheir sinensis via alterations in the actin filament network and cell junctions - Zhen-Fang Li; Shuang-Li Hao; Lan-Min Wang; Hong-Yu Qi; Jia-Ming Wang; Fu-Qing Tan; Wan-Xi Yang (Cell and Tissue Research, 2022)

The recombinant subunit vaccine encapsulated by alginate‐chitosan microsphere enhances the immune effect against Micropterus salmoides rhabdovirus - Fei‐Fan Xu; Fu‐Yi Jiang; Guo‐Qing Zhou; Jun‐Yao Xia; Fei Yang; Bin Zhu (Journal of Fish Diseases, 2022)
The disease caused by Micropterus salmoides rhabdovirus (MSRV) has brought substantial economic losses to the largemouth bass aquaculture industry in China. Vaccination was considered as a potential way to prevent and control this disease. As a kind of sustained and controlled release system, alginate and chitosan microspheres (SA‐CS) are widely used in the development of oral vaccination for fish. Here, we prepared a king of alginate‐chitosan composite microsphere to encapsulate the second segment of MSRV glycoprotein (G2 protein) and then evaluated the immune effect of the microsphere vaccine on largemouth bass. Largemouth bass were vaccinated via intragastric immunization by different treatments (PBS, SA‐CS, G2 and SA‐CS‐G2). The results showed that a stronger immune response including serum antibody levels, immune‐related physiological indexes (acid phosphatase, alkaline phosphatase, superoxide dismutase and total antioxidant capacity) and the expression of immune‐related gene ( IgM、IL‐8、IL‐1β、CD4、TGF‐β、TNF‐α ) can be induced obviously with SA‐CS‐G2 groups compared with G2 groups when fish were vaccinated. Furthermore, fish were injected with a lethal dose of MSRV after immunization for 28 days, and the highest relative percentage survival (54.8%) was observed in SA‐CS‐G2 group (40 μg per fish), which is significantly higher than that of G2 group (25.8%). This study showed that alginate‐chitosan microspheres as the vaccine carrier can effectively improve the immune effect of oral vaccination and induce better immune protection effect against MSRV infection.

Cytokine storm and targeted therapy in hemophagocytic lymphohistiocytosis - Han-qi Zhang; Si-Wei Yang; Yi-Cheng Fu; Ming-Cong Chen; Cheng-Hao Yang; Ming-Hua Yang; Xiao-Dan Liu; Qing-Nan He; Hua Jiang; Ming-Yi Zhao (Immunologic Research, 2022)

Wheat genomic study for genetic improvement of traits in China - Jun Xiao; Bao Liu; Yingyin Yao; Zifeng Guo; Haiyan Jia; Lingrang Kong; Aimin Zhang; Wujun Ma; Zhongfu Ni; Shengbao Xu; Fei Lu; Yuannian Jiao; et al. (Science China Life Sciences, 2022)

Identification and validation of suitable reference genes for quantitative real-time PCR studies in Adiantum reniforme var. sinense - Qi Fu; Lin Xiang; Kai-ge Zhao; Long-qing Chen (Journal of Plant Biochemistry and Biotechnology, 2022)

Catalytic effect of cesium on the oxidation behavior of cation exchange resins in Li2CO3-Na2CO3-K2CO3 melt - Yang-Hai Zheng; Yong-De Yan; Yun Xue; Yue-Lin Wang; Xin Liu; Wan-Sheng Mi; Qing-Guo Zhang; Yu Li; Fu-Qiu Ma; Mi-Lin Zhang; Zhi-Hao Gan; Kai Zhu (Environmental Science and Pollution Research, 2022)

Neuroprotection of Oral Edaravone on Middle Cerebral Artery Occlusion in Rats - Li-Qin Zhao; Ankit Parikh; Yun-Xia Xiong; Qing-Yan Ye; Ying-Guo; Xin-Fu Zhou; Hai-Yun Luo (Neurotoxicity Research, 2022)

Spatiotemporal variation in nitrogen and phosphorus levels and microbial community in the upstream water transport channel to the Douhe Reservoir - Yueting Fan; Qing Fu; Shusong Zhang; Moli Zhang; Sheng Chang; Shaoyan Zhao; Minling Wang (Environmental Science and Pollution Research, 2022)

Effects of postnatal exposure to tetrabromobisphenol A on testis development in mice and early key events - Yuanyuan Li; Mengqi Dong; Yiming Xiong; Qing Chang; Xuanyue Chen; Xufeng Fu; Xinghong Li; Zhanfen Qin (Archives of Toxicology, 2022)

Deformation characteristics and thresholds of the Tanjiawan landslide in the Three Gorges Reservoir Area, China - Fu-ling Zhang; Mao-lin Deng; Qing-lin Yi; Shu-qiang Lu; Wei-jun Zheng; Hai-feng Huang; Xing Zhu (Journal of Mountain Science, 2022)

Rapid onset hazards, fault-controlled landslides and multi-method emergency decision-making - Fu-yun Guo; Xing-min Meng; Tian-jun Qi; Tom Dijkstra; Jarsve Kristine Thorkildsen; Dong-xia Yue; Guan Chen; Yi Zhang; Xiao-dong Dou; Peng-qing Shi (Journal of Mountain Science, 2022)

The altered functional modular organization in systemic lupus erythematosus: an independent component analysis study - Zheng-Ye Cao; Na Wang; Hua Wei; Jie-Ting Jia; Hong-Ying Zhang; Song-An Shang; Qing-Qiang Zhu; Xian-Fu Luo; Jing-Tao Wu (Brain Imaging and Behavior, 2022)

Six phenanthrenes from the roots of Cymbidium faberi Rolfe. and their biological activities - Shuang-shuang Lv; Yu Fu; Jun Chen; Yuan Jiao; Sui-qing Chen (Natural Product Research, 2022)

The effect of preoperative statin treatment on acute kidney injury in elderly patients undergoing valve replacement surgery - Bing-qi Fu; Xue-biao Wei; Zedazhong Su; Ying-wen Lin; Zu-hui Ke; Tong Tan; Ji-yan Chen; Shou-hong Wang; Dan-qing Yu (European Journal of Clinical Pharmacology, 2022)

Description of different cracking processes affecting dispersive saline soil slopes subjected to the effects of frost and consequences for the stability of low slopes - Mengxia Han; Qing Wang; Yan Han; Huicheng Fu; Jiejie Shen; Yaowu Liu (Bulletin of Engineering Geology and the Environment, 2022)

New monoterpenoids from the stigmas of Crocus sativus - Qing-Wei Fang; Wen-Wei Fu; Jin-Ling Yang; Yue Lu; Jiang-Cheng Chen; Pei-Ying Wu; Xue Zhang; Hong-Xi Xu (Journal of Natural Medicines, 2022)

Recent advances in tissue stem cells - Xin Fu; Qiang He; Yu Tao; Mengdi Wang; Wei Wang; Yalong Wang; Qing Cissy Yu; Fang Zhang; Xiaoyu Zhang; Ye-Guang Chen; Dong Gao; Ping Hu; et al. (Science China Life Sciences, 2021)

A novel BRET based genetic coded biosensor for apoptosis detection at deep tissue level in live animal - Yueling Zhang; Juan Hu; Meijuan Yu; Zhirong Wang; Hucheng Qing; Huheng Fu; Liudi Yuan; Fei Li; Sheng Zhao (Apoptosis, 2021)

Molecular identification and phylogenetic analysis of fungal pathogens isolated from diseased fish in Xinjiang, China - Yan‐Zhen Zhang; Qing‐Dian Han; Long‐Wei Fu; Yong‐Xing Wang; Zhi‐Hai Sui; Yun‐Guo Liu (Journal of Fish Biology, 2021)
The outbreaks of fungal diseases in cultured fish have been severe in recent years, which is harmful to the healthy and sustainable development of fish farming. In this study, an investigation was conducted for significant fungal infections of 12 species of fish in four regions in Xinjiang, China, to understand the distribution of local fish fungal pathogens. Twenty‐six fungal strains with pathogenicity were isolated, and the challenge experiment showed that eight strains from Changji area had high infection rate to fish eggs. Based on internal transcribed spacer sequence data and molecular analysis, the 26 strains were classified into nine different species of six fungal genera. Phylogenetic analysis showed that all strains were divided into two clades, namely Cluster 1 (contains only the genus Mucor ) and Cluster 2 (consists of five small branches), and the distribution of strains from the same region was scattered in two clusters. There is no strict host selectivity for these fungi to infect fish. Mucor sp. are the main fungal pathogen of fish in these four regions, whereas Hypophthalmichthys molitrix and Carassius auratus are two types of fish that were susceptible to pathogen. In addition, the environmental adaptability experiments showed that eight highly pathogenic strains have different adaptability to the environment, and their optimum temperature and pH were 25°C and 7.0, respectively, whereas the concentration of NaCl was negatively correlated with the growth of strains. Therefore, these results indicated that the coinfection of multiple fungal pathogens in a culture region should be considered in the future study.

Environmental contamination with SARS‐CoV ‐2 in COVID ‐19 hospitals in Wuhan, China, 2020 - Wei Liu; Dingchen Li; Chaojie Yang; Fangyan Chen; Ruizhong Jia; Leili Jia; Xinyi Xia; Shanhong Fan; Qing Tan; Yuehua Ke; Yong Chen; Haifeng Li; et al. (Environmental Microbiology, 2021)
Summary Coronavirus disease 2019 (COVID‐19) pandemic has caused high number of infections and deaths of healthcare workers globally. Distribution and possible transmission route of SARS‐CoV‐2 in hospital environment should be clarified. We herein collected 431 environmental (391 surface and 40 air) samples in the intensive care unit (ICU) and general wards (GWs) of three hospitals in Wuhan, China from February 21 to March 4, 2020, and detected SARS‐CoV‐2 RNA by real‐time quantitative PCR. The viral positive rate in the contaminated areas was 17.8% (28/157), whereas there was no virus detected in the clean areas. Higher positive rate (22/59, 37.3%) was found in ICU than that in GWs (3/63, 4.8%). The surfaces of computer keyboards and mouse in the ICU were the most contaminated (8/10, 80.0%), followed by the ground (6/9, 66.7%) and outer glove (2/5, 40.0%). From 17 air samples in the contaminated areas, only one sample collected at a distance of around 30 cm from the patient was positive. Enhanced surface disinfection and hand hygiene effectively decontaminated the virus from the environment. This finding might help understand the transmission route and contamination risk of SARS‐CoV‐2 and evaluate the effectiveness of infection prevention and control measures in healthcare facilities.

Genome-wide analysis and characterization of R2R3-MYB family in pigeon pea (Cajanus cajan) and their functional identification in phenylpropanoids biosynthesis - Jie Yang; Su Zhang; Hongquan Li; Litao Wang; Ying Liu; Lili Niu; Qing Yang; Dong Meng; Yujie Fu (Planta, 2021)

Responses of leaf litter decomposability to nitrogen and phosphorus additions are associated with cell wall carbohydrate composition in a subtropical plantation - Xiang-Min Fang; Xiu-Lan Zhang; Ying-Ying Zong; Wen-Qing Li; Jian-Jun Li; Li-Ping Guo; Huimin Wang; Fu-Sheng Chen (Plant and Soil, 2021)

Evaluation of the prognostic ability of serum uric acid for elderly acute coronary syndrome patients with diabetes mellitus: a prospective cohort study - Yang Jiao; Jihang Wang; Xia Yang; Mingzhi Shen; Hao Xue; Jun Guo; Wei Dong; Yundai Chen; Qing Xi; Zhenhong Fu (Journal of Zhejiang University-SCIENCE B, 2021)

Dynamics of antibiotic resistance and its association with bacterial community in a drinking water treatment plant and the residential area - Fu-Yi Huang; Qing-Lin Chen; Xian Zhang; Roy Neilson; Jian-Qiang Su; Shu-Yi-Dan Zhou (Environmental Science and Pollution Research, 2021)

RETRACTED ARTICLE: Two New Coordination Polymers: Selective Detection of Cu(II) Ion and Treatment Activity on Inner Ear Damage - Jing Liu; Wan-Dong She; Fu-Sen Wang; Qing Zhou (Journal of Fluorescence, 2021)

Molecular identification and characterization of ‘Candidatus Phytoplasma asteris’-related strain associated with pepper (Capsicum annuum L.) yellow crinkle disease in China - Shao-shuai Yu; Qing-hua Tang; Deng-qiang Fu; Rui-ling Zhao; Wei-wei Song; Wei Yan; Wei-quan Qin (Journal of General Plant Pathology, 2021)

Landslide distribution and sliding mode control along the Anninghe fault zone at the eastern edge of the Tibetan Plateau - Hong-fu Zhou; Bin Liu; Fei Ye; Wen-xi Fu; Wen-qing Tang; Ya-dong Qin; Tian Fang (Journal of Mountain Science, 2021)

Analysis on water use efficiency of Populus euphratica forest ecosystem in arid area - Lianqing Xue; Fangbing Fu; Xinfang Chen; Yuanhong Liu; Qiang Han; Shumin Liao; Qing Wei (Theoretical and Applied Climatology, 2021)

The contrasting relationships of relative humidity with influenza A and B in a humid subtropical region - Qian Wu; Jun He; Wen-Yan Zhang; Ke-Fu Zhao; Jing Jin; Jun-Ling Yu; Qing-Qing Chen; Sai Hou; Meng Zhu; Zhiwei Xu; Hai-Feng Pan (Environmental Science and Pollution Research, 2021)

Can China’s pollution reduction mandates improve transboundary water pollution? - Qingyu Wang; Qing Ma; Jinge Fu (Environmental Science and Pollution Research, 2021)

Isolation and characterization of ent -pimarane diterpenoids from Sigesbeckia pubescens - Jianbin Wang; Kehui Xie; Qing Wang; Wenchao Li; Hongzheng Fu (Natural Product Research, 2021)

Serological evidence of bovine viral diarrhea virus and peste des petits ruminants virus infection in alpacas (Vicugna pacos) in Shanxi Province, northern China - Qing Liu; Lu Liu; Yu-Kai Meng; Chen Wang; Yu Gao; Fu-Guo Zheng; Hai-Li Ma (Tropical Animal Health and Production, 2021)

A mitochondria-localized pentatricopeptide repeat protein is required to restore hau cytoplasmic male sterility in Brassica napus - Huadong Wang; Qing Xiao; Chao Wei; Hui Chen; Xiaohan Chen; Cheng Dai; Jing Wen; Chaozhi Ma; Jinxing Tu; Tingdong Fu; Jinxiong Shen; Bin Yi (Theoretical and Applied Genetics, 2021)

Annual and seasonal precipitation trends and their attributions in the Qinling Mountains, a climate transitional zone in China - Qing Meng; Hongying Bai; Ranjan Sarukkalige; Guobin Fu; Wenhao Jia; Chenhua Zhang (Theoretical and Applied Climatology, 2021)

Correction to: Central Blockade of E-Prostanoid 3 Receptor Ameliorated Hypertension Partially by Attenuating Oxidative Stress and Inflammation in the Hypothalamic Paraventricular Nucleus of Spontaneously Hypertensive Rats - Fang-Fang Wang; Juan Bai; Xiao-Jing Yu; Xiao-Lian Shi; Jin-Jun Liu; Kai-Li Liu; Li-Yan Fu; Qing Su; Hong-Bao Li; Kai B. Kang; Qiu-Yue Yi; Shu-Qiu Wang; et al. (Cardiovascular Toxicology, 2021)

Central Blockade of E-Prostanoid 3 Receptor Ameliorated Hypertension Partially by Attenuating Oxidative Stress and Inflammation in the Hypothalamic Paraventricular Nucleus of Spontaneously Hypertensive Rats - Fang-Fang Wang; Juan Ba; Xiao-Jing Yu; Xiao-Lian Shi; Jin-Jun Liu; Kai-Li Liu; Li-Yan Fu; Qing Su; Hong-Bao Li; Kai B. Kang; Qiu-Yue Yi; Shu-Qiu Wang; et al. (Cardiovascular Toxicology, 2021)

Bisabolane sesquiterpenes from Clausena sanki with their potential anti-inflammatory activities - Shi Hu; Yan-Lei Ma; Jia-Ming Guo; Qing Wen; Gui Yan; Shuo Yang; Yan-Hui Fu; Yan-Ping Liu (Natural Product Research, 2020)

Correction to: Involvement of proBDNF in Monocytes/Macrophages with Gastrointestinal Disorders in Depressive Mice - Yun-Qing Yu; Yan-Ling Zhang; Zhe Wang; Yu Liu; Hui Li; Chang-Qi Li; Xin-Fu Zhou; Zhao-Lan Hu; Ru-Ping Dai (Neurotoxicity Research, 2020)

Involvement of proBDNF in Monocytes/Macrophages with Gastrointestinal Disorders in Depressive Mice - Yun-Qing Yu; Yan-Ling Zhang; Zhe Wang; Yu Liu; Hui Li; Xin-Fu Zhou; Zhao-Lan Hu; Ru-Ping Dai (Neurotoxicity Research, 2020)

Comparative transcriptome analysis of gynoecious and monoecious inflorescences reveals regulators involved in male flower development in the woody perennial plant Jatropha curcas - Mei-Li Zhao; Mao-Sheng Chen; Jun Ni; Chuan-Jia Xu; Qing Yang; Zeng-Fu Xu (Plant Reproduction, 2020)

Divergence in flowering time is a major component contributing to reproductive isolation between two wild rice species (Oryza rufipogon and O. nivara) - Xun Xu; Qing-Lin Meng; Mu-Fan Geng; Ning-Ning Ren; Lian Zhou; Yu-Su Du; Zhe Cai; Mei-Xia Wang; Xin Wang; Xiu-Hua Wang; Jing-Dan Han; Shuai Jiang; et al. (Science China Life Sciences, 2020)

Reexamining the Necessity of Adding Water Curtain Borehole with Improved Understanding of Water Sealing Criterion - Qi-Hua Zhang; Qing-Bing Liu; Guo-Fu He (Rock Mechanics and Rock Engineering, 2020)

KIF3A regulates the Wnt/β-catenin pathway via transporting β-catenin during spermatogenesis in Eriocheir sinensis - Ya-Jing Liang; Jia-Hao Ni; Lan-Min Wang; Fu-Qing Tan; Wan-Xi Yang (Cell and Tissue Research, 2020)

Variations in vegetation dynamics and its cause in national key ecological function zones in China - Jiaqiang Du; Shifeng Fang; Zhilu Sheng; Jinhua Wu; Zhanjun Quan; Qing Fu (Environmental Science and Pollution Research, 2020)

Bioactive Eudesmane sesquiterpenes from Artabotrys hongkongensis Hance - Qing Wen; Yan-Ping Liu; Gui Yan; Shuo Yang; Shi Hu; Jing Hua; Wen-Qing Yin; Guang-Ying Chen; Yan-Hui Fu (Natural Product Research, 2020)

Microwave-assisted efficient synthesis of 3-substituted bis-isoxazole ether bearing 2-chloro-3-pyridyl via 1,3-dipolar cycloaddition - Ran Zheng; Fan Feng; Zhihui Zhang; Jiaxu Fu; Qing Su; Yumin Zhang; Qiang Gu (Molecular Diversity, 2020)

Synthesis and biological effects of naphthalene-chalcone derivatives - Qing-Hao Jin; Hong-Hai Chen; Wen-Bo Chen; Zhi-Yang Fu; Li-Ping Guan; Hai-Ying Jiang (Medicinal Chemistry Research, 2020)

Bacteriostatic effect of lipopeptides from Bacillus subtilis N-2 on Pseudomonas putida using soybean meal by solid-state fermentation - Meng Li; Haijin Mou; Qing Kong; Tan Zhang; Xiaodan Fu (Marine Life Science & Technology, 2020)

Microporous intermittent aeration vertical flow constructed wetlands for eutrophic water improvement - Qing Wu; Jingjing Xiao; Lijuan Fu; Mengxing Ma; Sen Peng (Environmental Science and Pollution Research, 2020)

Transcriptome profiling reveals cytokinin promoted callus regeneration in Brassica juncea - Hongchen Lu; Ping Xu; Kaining Hu; Qing Xiao; Jing Wen; Bin Yi; Chaozhi Ma; Jinxing Tu; Tingdong Fu; Jinxiong Shen (Plant Cell, Tissue and Organ Culture (PCTOC), 2020)

Brain-Wide Shape Reconstruction of a Traced Neuron Using the Convex Image Segmentation Method - Shiwei Li; Tingwei Quan; Hang Zhou; Qing Huang; Tao Guan; Yijun Chen; Cheng Xu; Hongtao Kang; Anan Li; Ling Fu; Qingming Luo; Hui Gong; et al. (Neuroinformatics, 2020)

Species richness and biodiversity significance of alpine micro-waterbody systems in Gaoligong Mountain, Northwest Yunnan, China - Shuo-Ran Liu; Davide Fornacca; Dao-De Yang; Lu Tan; Xian-Fu Li; Guo-Peng Ren; Jun Sun; Xiao-Yang He; Wen-Shu Yang; Qing-Hua Cai; Wen Xiao (Journal of Mountain Science, 2020)

Reservoir characteristics, pore structure, and main controlling factors of oolitic shoal reservoir in Feixianguan Formation: a case study from eastern Kaijiang-Liangping Trough - Yifan Gu; Yuqiang Jiang; Hairuo Qing; Liang Feng; Linjie Feng; Yonghong Fu; Chan Jiang (Arabian Journal of Geosciences, 2020)

Temporal and Spatial Dynamics of Astroglial Reaction and Immune Response in Cuprizone-Induced Demyelination - Jun An; Jun-Jun Yin; Yan He; Ruo-Xuan Sui; Qiang Miao; Qing Wang; Jie-Zhong Yu; Jing-Wen Yu; Fu-Dong Shi; Cun-Gen Ma; Bao-Guo Xiao (Neurotoxicity Research, 2020)

Inhibition of chemotherapy-related breast tumor EMT by application of redox-sensitive siRNA delivery system CSO-ss-SA/siRNA along with doxorubicin treatment - Xuan Liu; Xue-qing Zhou; Xu-wei Shang; Li Wang; Yi Li; Hong Yuan; Fu-qiang Hu (Journal of Zhejiang University-SCIENCE B, 2020)

Soil fungal community is more sensitive to nitrogen deposition than increased rainfall in a mixed deciduous forest of China - Aihua Zhao; Lei Liu; Baodong Chen; Wei Fu; Wei Xie; Tianle Xu; Wei Zhang; Qing Ye; Haiyan Feng; Shenglei Fu (Soil Ecology Letters, 2020)

Spatiotemporal changes in vegetation coverage and its causes in China since the Chinese economic reform - Jiaqiang Du; Zhanjun Quan; Shifeng Fang; Chengcheng Liu; Jinhua Wu; Qing Fu (Environmental Science and Pollution Research, 2020)

Differences in root surface adsorption, root uptake, subcellular distribution, and chemical forms of Cd between low- and high-Cd-accumulating wheat cultivars - Ya-Tao Xiao; Zhen-Jie Du; Carlos-A Busso; Xue-Bin Qi; Hai-Qing Wu; Wei Guo; Da-Fu Wu (Environmental Science and Pollution Research, 2020)

The response of reference evapotranspiration to climate change in Xinjiang, China: Historical changes, driving forces, and future projections - Qing Dong; Weiguang Wang; Quanxi Shao; Wanqiu Xing; Yimin Ding; Jianyu Fu (International Journal of Climatology, 2020)
Reference evapotranspiration (ET 0 ), which is an indicator of atmospheric evaporation demand over a hypothetical reference surface, is expected to alter along with global climate change. In this study, the changes and driving forces of historical ET 0 and its future projections in Xinjiang, China, were comprehensively conducted. The trend analysis revealed that regional ET 0 decreased significantly at a rate of −4.1 mm/year 2 during 1961–1993 and increased at a rate of 3.4 mm/year 2 during 1994–2010. To explore the possible causes, the contributions of major climatic variables to the ET 0 trends were derived based on the differential equation method. During 1961–1993, the decreasing trend of ET 0 was primarily ascribed to the wind speed. The integrated negative effect from the decrease in wind speed ( U ) and increase in relative humidity ( RH ) was more significant than the positive effect from the increase in air temperature ( T ), resulting in the decrease in ET 0 . During 1994–2010, combined with increasing T and decreasing RH , the increase in U offset the effect of the net radiation ( R n ) decrease and led to an increase in ET 0 . Future ET 0 projections over three periods (2010–2039, 2040–2069, and 2070–2099, which are named as 2020s, 2050s, and 2080s, respectively) were conducted based on the general circulation models under two representative concentration pathways scenarios (RCP4.5 and RCP8.5). A continuous increasing trend in ET 0 was demonstrated in the 21st century. The increase in ET 0 will increase the irrigated water resource consumption and bring new challenge to water resource management in this area.

Carbazole alkaloids from Clausena emarginata with their potential antiproliferative activities - Yan-Hui Fu; Yan-Lei Ma; Gui Yan; Qing Wen; Shi Hu; Zhi-Hua Jiang; Jin-Ying Tang; Yan-Ping Liu (Natural Product Research, 2019)

Characteristics and Prognosis of Talaromyces marneffei Infection in Non-HIV-Infected Children in Southern China - Jing Guo; Bing-Kun Li; Tian-Min Li; Fang-Lin Wei; Yu-Jiao Fu; Yan-Qing Zheng; Kai-Su Pan; Chun-Yang Huang; Cun-Wei Cao (Mycopathologia, 2019)

Rare variants in FANCA induce premature ovarian insufficiency - Xi Yang; Xiaojin Zhang; Jiao Jiao; Feng Zhang; Yuncheng Pan; Qiqi Wang; Qing Chen; Baozhu Cai; Shuyan Tang; Zixue Zhou; Siyuan Chen; Hao Yin; et al. (Human Genetics, 2019)
Premature ovarian insufficiency (POI) is a major cause of reduced female fertility and affects approximately 1% women under 40 years of age. Recent advances emphasize the genetic heterogeneity of POI. Fanconi anemia (FA) genes, traditionally known for their essential roles in DNA repair and cytogenetic instability, have been demonstrated to be involved in meiosis and germ cell development. Here, we conducted whole-exome sequencing (WES) in 50 Han Chinese female patients with POI. Rare missense variants were identified in FANCA ( Fanconi anemia complementation group A ): c.1772G > A (p.R591Q) and c.3887A > G (p.E1296G). Both variants are heterozygous in the patients and very rare in the human population. In vitro functional studies further demonstrated that these two missense variants of FANCA exhibited reduced protein expression levels compared with the wild type, suggesting the partial loss of function. Moreover, mono-ubiquitination levels of FANCD2 upon mitomycin C stimulation were significantly reduced in cells overexpressing FANCA variants. Furthermore, a loss-of-function mutation of Fanca was generated in C57BL/6 mice for in vivo functional assay. Consistently, heterozygous mutated female mice ( Fanca + / − ) showed reduced fertility and declined numbers of follicles with aging when compared with the wild-type female mice. Collectively, our results suggest that heterozygous pathogenic variants in FANCA are implicated in non-syndromic POI in Han Chinese women, provide new insights into the molecular mechanisms of POI and highlight the contribution of FANCA variants in female subfertility.

Upregulation of proBDNF in the Mesenteric Lymph Nodes in Septic Mice - Zhe Wang; Jia-Li Wu; Feng Zhong; Yu Liu; Yun-Qing Yu; Jing-Jing Sun; Shuang Wang; Hui Li; Xin-Fu Zhou; Zhao-Lan Hu; Ru-Ping Dai (Neurotoxicity Research, 2019)

Panax notoginsenoside Rb1 Restores the Neurotrophic Imbalance Following Photothrombotic Stroke in Rats - Chun-Yan Yang; Jian-Yu Yang; Yun-Xia Xiong; Xue-Feng Zhuang; Hui Su; Sheng Hu; Jia-Qing Ma; Xin-Fu Zhou; Hai-Yun Luo; Jun Sun (Neurotoxicity Research, 2019)

Furanocoumarins with potential antiproliferative activities from Clausena lenis - Yan-Ping Liu; Qing Wen; Shi Hu; Yan-Lei Ma; Zhi-Hua Jiang; Jin-Ying Tang; Yan-Hui Fu; Shen-Xiang Qiu (Natural Product Research, 2019)

Erratum to: Rapid generation of genetic diversity by multiplex CRISPR/Cas9 genome editing in rice - Lan Shen; Yufeng Hua; Yaping Fu; Jian Li; Qing Liu; Xiaozhen Jiao; Gaowei Xin; Junjie Wang; Xingchun Wang; Changjie Yan; Kejian Wang (Science China Life Sciences, 2019)

Genome-wide identification and characterization of UGT family in pigeonpea (Cajanus cajan) and expression analysis in abiotic stress - Zhihua Song; Lili Niu; Qing Yang; Biying Dong; Litao Wang; Mingzhu Dong; Xiaohong Fan; Yue Jian; Dong Meng; Yujie Fu (Trees, 2019)

Identification of rare variants in cardiac sodium channel β4-subunit gene SCN4B associated with ventricular tachycardia - Qin Yang; Hongbo Xiong; Chengqi Xu; Yuan Huang; Xin Tu; Gang Wu; Fenfen Fu; Zhijie Wang; Longfei Wang; Yuanyuan Zhao; Sisi Li; Yufeng Huang; et al. (Molecular Genetics and Genomics, 2019)

The Inhibitory Effects of Nitrogen Deposition on Asymbiotic Nitrogen Fixation are Divergent Between a Tropical and a Temperate Forest - Mianhai Zheng; Wei Zhang; Yiqi Luo; Shiqiang Wan; Shenglei Fu; Senhao Wang; Nan Liu; Qing Ye; Junhua Yan; Bi Zou; Chengliang Fang; Yuxi Ju; et al. (Ecosystems, 2019)

Population Genetics of Calotropis gigantea, a Medicinal and Fiber Resource Plant, as Inferred from Microsatellite Marker Variation in two Native Countries - Md. Rabiul Islam; Zhi-Zhong Li; Andrew W. Gichira; Mohammad Nur Alam; Peng-Cheng Fu; Guang-Wan Hu; Qing-Feng Wang; Ling-Yun Chen (Biochemical Genetics, 2019)

Two new echinocystic acid derivatives catalyzed by filamentous fungus Gliocladium roseum CGMCC 3.3657 - Shao-Bin Fu; Xu Feng; Qing-Feng Meng; Qing Cai; Di-An Sun (Natural Product Research, 2019)

Nondigestible carbohydrates, butyrate, and butyrate-producing bacteria - Xiaodan Fu; Zhemin Liu; Changliang Zhu; Haijin Mou; Qing Kong (Critical Reviews in Food Science and Nutrition, 2019)

Effects of periodical drying and non-drying on nutrient content and desiccation tolerance of an intertidal Pyropia yezoensis strain subject to farming conditions - Wen Jun Wang; Xiao Lei Li; Teng Qing Sun; Zhou Rui Liang; Fu Li Liu; Xiu Tao Sun; Fei Jiu Wang (Journal of Applied Phycology, 2019)

The China Multi-Model Ensemble Prediction System and Its Application to Flood-Season Prediction in 2018 - Hong-Li Ren; Yujie Wu; Qing Bao; Jiehua Ma; Changzheng Liu; Jianghua Wan; Qiaoping Li; Xiaofei Wu; Ying Liu; Ben Tian; Joshua-Xiouhua Fu; Jianqi Sun (Journal of Meteorological Research, 2019)

Correction to: Elicitation of Isatis tinctoria L. hairy root cultures by salicylic acid and methyl jasmonate for the enhanced production of pharmacologically active alkaloids and flavonoids - Qing-Yan Gai; Jiao Jiao; Xin Wang; Yu-Ping Zang; Li-Li Niu; Yu-Jie Fu (Plant Cell, Tissue and Organ Culture (PCTOC), 2019)

A Highly Selective Fluorescence “Turn on” and Absorbance-Ratiometric Detection of Al3+ in Totally H2O and its Application in Test Paper - Xue-Jiao Sun; Yu-Qing Ma; Hong Fu; Zhi-Yong Xing; Zhi-Gang Sun; Yue Shen; Jin-Long Li (Journal of Fluorescence, 2019)

Influences of soil moisture and salt content on loess shear strength in the Xining Basin, northeastern Qinghai-Tibet Plateau - Jiang-tao Fu; Xia-song Hu; Xi-lai Li; Dong-mei Yu; Ya-bin Liu; You-Qing Yang; Zhao-xin Qi; Shu-xia Li (Journal of Mountain Science, 2019)

Cinnamaldehyde inhibit Escherichia coli associated with membrane disruption and oxidative damage - Tian-Fu He; Lang-Hong Wang; De-bao Niu; Qing-hui Wen; Xin-An Zeng (Archives of Microbiology, 2019)

Structurally diverse diterpenoids from Trigonostemon howii - Yan-Ping Liu; Qing Wen; Shi Hu; Yan-Lei Ma; Zhi-Hua Jiang; Jin-Ying Tang; Yan-Hui Fu (Natural Product Research, 2019)

Elicitation of Isatis tinctoria L. hairy root cultures by salicylic acid and methyl jasmonate for the enhanced production of pharmacologically active alkaloids and flavonoids - Qing-Yan Gai; Jiao Jiao; Xin Wang; Yu-Ping Zang; Li-Li Niu; Yu-Jie Fu (Plant Cell, Tissue and Organ Culture (PCTOC), 2019)

Construction of Boolean logic gates based on dual-vector circuits of multiple gene regulatory elements - Zhao Wei; Wenliang Fu; Qing Liu; Haoran Jing; Chen Jin; Yao Chen; Wenrong Xia; Xiaoming Zhu; Donggang Xu (Molecular Genetics and Genomics, 2019)

Dexamethasone protects the glycocalyx on the kidney microvascular endothelium during severe acute pancreatitis - Wen-qiao Yu; Shao-yang Zhang; Shui-qiao Fu; Qing-hui Fu; Wei-na Lu; Jian Zhang; Zhong-yan Liang; Yun Zhang; Ting-bo Liang (Journal of Zhejiang University-SCIENCE B, 2019)

Novel mutations in ZP1, ZP2, and ZP3 cause female infertility due to abnormal zona pellucida formation - Zhou Zhou; Caixia Ni; Ling Wu; Biaobang Chen; Yao Xu; Zhihua Zhang; Jian Mu; Bin Li; Zheng Yan; Jing Fu; Wenjing Wang; Lin Zhao; et al. (Human Genetics, 2019)

Interethnic scaling of fraction unbound of a drug in plasma and volume of distribution: an analysis of extrapolation from Caucasians to Chinese - Guo Yu; Hong-Hao Zhou; Qing-Shan Zheng; Guo-Fu Li (European Journal of Clinical Pharmacology, 2019)

Physiological responses of the freshwater N 2 ‐fixing cyanobacterium Raphidiopsis raciborskii to Fe and N availabilities - Qing‐Long Fu; Anna C. Y. Yeung; Manabu Fujii; Brett A. Neilan; T. David Waite (Environmental Microbiology, 2019)
Summary The cyanobacterium Raphidiopsis raciborskii is of environmental and social concern in view of its toxicity, bloom‐forming characteristics and increasingly widespread occurrence. However, while availability of macronutrients and micronutrients such as N and Fe are critically important for the growth and metabolism of this organism, the physiological response of toxic and non‐toxic strains of R. raciborskii to varying Fe and N availabilities remains unclear. By determining physiological parameters as a function of Fe and N availability, we demonstrate that R. raciborskii growth and N 2 ‐fixing activity are facilitated at higher Fe availability under N 2 ‐limited conditions with faster growth of the CS‐506 (cylindrospermopsin‐producing) strain compared with that of CS‐509 (the non‐toxic) strain. Radiolabelled Fe uptake assays indicated that R. raciborskii acclimated under Fe‐limited conditions acquires Fe at significantly higher rates than under Fe replete conditions, principally via unchelated Fe(II) generated as a result of photoreduction of complexed Fe(III). While N 2 ‐fixation of both strains occurred during both day and night, the CS‐506 strain overall exhibited higher N 2 ‐fixing and Fe uptake rates than the CS‐509 strain under N‐deficient and Fe‐limited conditions. The findings of this study highlight that Fe availability is of significance for the ecological advantage of CS‐506 over CS‐509 in N‐deficient freshwaters.

Microsatellite records for volume 11, issue 1 - Da-Qing Chen; Zaijie Dong; Min Fang; Jianjun Fu; Xiang-Yang Jia; Bingjie Jiang; Jingmiao Li; Qingqing Li; Suhui Liao; Ping Liu; Yulin Liu; Guocheng Shu; et al. (Conservation Genetics Resources, 2019)

Blockade of Endogenous Angiotensin-(1–7) in Hypothalamic Paraventricular Nucleus Attenuates High Salt-Induced Sympathoexcitation and Hypertension - Xiao-Jing Yu; Yu-Wang Miao; Hong-Bao Li; Qing Su; Kai-Li Liu; Li-Yan Fu; Yi-Kang Hou; Xiao-Lian Shi; Ying Li; Jian-Jun Mu; Wen-Sheng Chen; Wei Cui; et al. (Neuroscience Bulletin, 2019)

Integrative genomic analysis predicts novel functional enhancer-SNPs for bone mineral density - Chuan Qiu; Hui Shen; Xiaoying Fu; Chao Xu; Qing Tian; Hongwen Deng (Human Genetics, 2019)

Identification a novel clinical biomarker in early diagnosis of human non-small cell lung cancer - Yanxia Jin; Yajun Yang; Yanting Su; Xiangdong Ye; Wei Liu; Qing Yang; Jie Wang; Xiangning Fu; Yongsheng Gong; Hui Sun (Glycoconjugate Journal, 2019)

Profiling of indole metabolic pathway in thermo-sensitive Bainong male sterile line in wheat (Triticum aestivum L.) - Qing Su; Jing Yang; Qing Yun Fu; Fei Yun Jia; Suo Ping Li; Yong Li; You Yong Li (Physiology and Molecular Biology of Plants, 2019)

A Genome-Wide Association Study of α-Synuclein Levels in Cerebrospinal Fluid - Xiao-ling Zhong; Jie-Qiong Li; Li Sun; Ya-Qing Li; Hui-Fu Wang; Xi-Peng Cao; Chen-Chen Tan; Ling Wang; Lan Tan; Jin-Tai Yu (Neurotoxicity Research, 2019)

Study on synthesis and biological effects of a series of 3,4-dihydroisoquinoline-2(1H)-carboxamide derivatives - Zhi-Yang Fu; Qing-Hao Jin; Ya-Nan Xia; Hai-Ying Jiang; Li-Ping Guan (Medicinal Chemistry Research, 2019)

Determination of dietary nitrite in patients with esophageal pre-cancerous lesion and normal people: a duplicate diet study - Ting Zhang; Da Pan; Ming Su; Ling-Meng Fu; Cai-Yun Miao; Qing-Yang Yan; Jing Wang; Li-Gang Yang; Shao-Kang Wang; Gui-Ju Sun (Food Additives & Contaminants: Part A, 2018)

Nramp5 expression and functionality likely explain higher cadmium uptake in rice than in wheat and maize - Fu-Qing Sui; Jia-Dong Chang; Zhong Tang; Wen-Ju Liu; Xin-Yuan Huang; Fang-Jie Zhao (Plant and Soil, 2018)

Two thymol derivatives from the flower buds of Lonicera japonica and their antibacterial activity - Jing Yang; Yong-Chao Li; Xiu-Ren Zhou; Xin-Juan Xu; Qing-Yun Fu; Chang-Zhong Liu (Natural Product Research, 2018)

Novel thioredoxin reductase inhibitor butaselen inhibits tumorigenesis by down-regulating programmed death-ligand 1 expression - Qiao Zou; Yi-fan Chen; Xiao-qing Zheng; Suo-fu Ye; Bin-yuan Xu; Yu-xi Liu; Hui-hui Zeng (Journal of Zhejiang University-SCIENCE B, 2018)

Active earth pressure on translating rigid retaining structures considering soil arching effect - Yi-tao Zhou; Qing-sheng Chen; Fu-quan Chen; Xiao-hui Xue; Sudip Basack (European Journal of Environmental and Civil Engineering, 2018)

The Sesuvium portulacastrum Plasma Membrane Na+/H+ Antiporter SpSOS1 Complemented the Salt Sensitivity of Transgenic Arabidopsis sos1 Mutant Plants - Yang Zhou; Xiaochang Yin; Shumin Wan; Yanping Hu; Qing Xie; Ruimei Li; Baibi Zhu; Shaoping Fu; Jianchun Guo; Xingyu Jiang (Plant Molecular Biology Reporter, 2018)

High-resolution melting-based TILLING of γ ray-induced mutations in rice - Shan Li; Song-mei Liu; Hao-wei Fu; Jian-zhong Huang; Qing-yao Shu (Journal of Zhejiang University-SCIENCE B, 2018)

Genetic structure of six cattle populations revealed by transcriptome-wide SNPs and gene expression - Wei Wang; Huai Wang; Hui Tang; Jia Gan; Changgeng Shi; Qing Lu; Donghui Fang; Jun Yi; Maozhong Fu (Genes & Genomics, 2018)

PGC-1α coordinates with Bcl-2 to control the cell cycle in U251 cells through reducing ROS - Kun Yao; Xu-feng Fu; Xing Du; Yan Li; Shan-shan Yang; Min Yu; Qing-hua Cui (Journal of Zhejiang University-SCIENCE B, 2018)

Detoxification of aflatoxins on prospective approach: effect on structural, mechanical, and optical properties under pressures - Yong-Kai Wei; Xiao-Miao Zhao; Meng-Meng Li; Jing-Xin Yu; Selvaraj Gurudeeban; Yan-Fei Hu; Guang-Fu Ji; Dong-Qing Wei (Interdisciplinary Sciences: Computational Life Sciences, 2018)

Three-dimensional analysis of ozone and PM2.5 distributions obtained by observations of tethered balloon and unmanned aerial vehicle in Shanghai, China - Xiao-Bing Li; Dongfang Wang; Qing-Chang Lu; Zhong-Ren Peng; Qingyan Fu; Xiao-Ming Hu; Juntao Huo; Guangli Xiu; Bai Li; Chao Li; Dong-Sheng Wang; Hanyu Wang (Stochastic Environmental Research and Risk Assessment, 2018)

Comparisons of cadmium bioaccumulation potentials and resistance physiology of Microsorum pteropus and Echinodorus grisebachii - Yun-Yun Yan; Jun-Jun Wang; Xin-Yu Lan; Qing-Mei Wang; Fu-Liu Xu (Environmental Science and Pollution Research, 2018)

Identification, characterization and expression analysis of genes involved in steroidal saponin biosynthesis in Dracaena cambodiana - Jia-Hong Zhu; Hui-Liang Li; Dong Guo; Ying Wang; Hao-Fu Dai; Wen-Li Mei; Shi-Qing Peng (Journal of Plant Research, 2018)

Self-assembled microspheres feasibility study for conformance control in high temperature and high salinity reservoirs - Jirui Zou; Xiangan Yue; Junbin Zhang; Joseph Y. Fu; Jie He; Bin Kong; Qing Ling (Arabian Journal of Geosciences, 2018)

Laboratory tests and numerical simulations on the impact of subsurface barriers to saltwater intrusion - Fu-lin Li; Xue-qun Chen; Cai-hong Liu; Yan-qing Lian; Li He (Natural Hazards, 2018)

Gcn5‐dependent histone H3 acetylation and gene activity is required for the asexual development and virulence of Beauveria bassiana - Qing Cai; Juan‐Juan Wang; Bo Fu; Sheng‐Hua Ying; Ming‐Guang Feng (Environmental Microbiology, 2018)
Summary Gcn5 is a core histone acetyltransferase that catalyzes histone H3 acetylation on N‐terminal lysine residues in yeasts and was reported to catalyze H3K9/K14 acetylation required for activating asexual development in Aspergillus . Here, we report a localization of Gcn5 ortholog in the nucleus and cytoplasm of Beauveria bassiana , a fungal insect pathogen. Deletion of gcn5 led to hypoacetylated H3 at K9/14/18/27 and 97% reduction in conidiation capacity as well as severe defects in colony growth and conidial thermotolerance. Two master conidiation genes, namely brlA and abaA , were transcriptionally repressed to undetectable level in Δ gcn5 , but sharply upregulated in wild‐type, at the beginning time of conidiation. Based on chromatin immunoprecipitation, both DNA and acetylation levels of the distal and proximal fragments of the brlA promoter bound by acetylated H3K14 alone were upregulated in wild‐type, but not in Δ gcn5 , at the mentioned time. In Δ gcn5 , normal cuticle infection was abolished while virulence through cuticle‐bypassing infection was greatly attenuated, accompanied by drastically reduced activities of putative cuticle‐degrading enzymes, retarded dimorphic transition and transcriptional repression of associated genes. These findings unveil a novel mechanism by which Gcn5 activates asexual development pathway by acetylating H3K14 and regulates the virulence‐related cellular events in B. bassiana .

Microsatellite records for volume 10, issue 1 - Ai-Qing Yu; Chengxin Fu; Chongbo He; Fei Liu; Guo-Hua Ding; Hongman Hou; Jian Zhao; Jianmin Yang; Jiansheng Wang; Kun-ci Chen; Lan-lan Zhang; Pan Li; et al. (Conservation Genetics Resources, 2018)

Periodical drying or no drying during aquaculture affects the desiccation tolerance of a sublittoral Pyropia yezoensis strain - Xiao-lei Li; Wen-jun Wang; Fu-li Liu; Zhou-rui Liang; Xiu-tao Sun; Hai-qing Yao; Fei-jiu Wang (Journal of Applied Phycology, 2018)

Effect of the dark septate endophytic fungus Acrocalymma vagum on heavy metal content in tobacco leaves - Hui-Qing Jin; Hua-Bing Liu; Ying-Ying Xie; Yong-Gang Zhang; Qing-Quan Xu; Li-Juan Mao; Xin-Jun Li; Jin Chen; Fu-Cheng Lin; Chu-Long Zhang (Symbiosis, 2018)

Two alphapartitiviruses co-infecting a single isolate of the plant pathogenic fungus Rhizoctonia solani - Ruiling Lyu; Yi Zhang; Qing Tang; Yangyi Li; Jiasen Cheng; Yanping Fu; Tao Chen; Daohong Jiang; Jiatao Xie (Archives of Virology, 2018)

Soil physical properties response to tillage practices during summer fallow of dryland winter wheat field on the Loess Plateau - Jian-Fu Xue; Ai-Xia Ren; Hui Li; Zhi-Qiang Gao; Tian-Qing Du (Environmental Science and Pollution Research, 2018)

Fiber-type distribution and expression of myosin heavy chain isoforms in newborn heterozygous myostatin-knockout pigs - Xiao-Xu Xing; Mei-Fu Xuan; Long Jin; Qing Guo; Zhao-Bo Luo; Jun-Xia Wang; Qi-Rong Luo; Guang-Lei Zhang; Cheng-Du Cui; Zheng-Yun Cui; Jin-Dan Kang; Xi-Jun Yin (Biotechnology Letters, 2017)

Spatiotemporal variation of soil organic carbon in the cultivated soil layer of dry land in the South-Western Yunnan Plateau, China - Ji-xia Zhao; Fu-qiang Dai; Shou-jia He; Qing Zhang; Gang-cai Liu (Journal of Mountain Science, 2017)

Role of early environmental enrichment on the social dominance tube test at adulthood in the rat - Wen-Yu Cao; Zhao-Lan Hu; Yang Xu; Wen-Juan Zhang; Fu-Lian Huang; Xiao-Qing Qiao; Yan-Hui Cui; Wei Wan; Xue-qin Wang; Dan Liu; Ru-Ping Dai; Fang Li; et al. (Psychopharmacology, 2017)

Molecular diversity of phenothiazines: design and synthesis of phenothiazine–dithiocarbamate hybrids as potential cell cycle blockers - Dong-Jun Fu; Ruo-Han Zhao; Jia-Huan Li; Jia-Jia Yang; Ruo-Wang Mao; Bo-Wen Wu; Ping Li; Xiao-Lin Zi; Qing-Qing Zhang; Hui-Jie Cai; Sai-Yang Zhang; Yan-Bing Zhang; et al. (Molecular Diversity, 2017)

Synergistic effects of temperature and humidity on the symptoms of COPD patients - Zhe Mu; Pei-Li Chen; Fu-Hai Geng; Lei Ren; Wen-Chao Gu; Jia-Yun Ma; Li Peng; Qing-Yun Li (International Journal of Biometeorology, 2017)

Brg1 inhibits E-cadherin expression in lung epithelial cells and disrupts epithelial integrity - Ting Wang; Wenjing Zou; Chao Niu; Fengxia Ding; Yaping Wang; Shuang Cai; Hua Zhu; Daiyin Tian; Jihong Dai; Enmei Liu; Qing Lu; Zhou Fu; et al. (Journal of Molecular Medicine, 2017)

A new indole alkaloid with anti-inflammatory activity from Nauclea officinalis - Qing-Long Liu; A-Hong Chen; Jin-Ying Tang; Yan-Lei Ma; Zhi-Hua Jiang; Yan-Ping Liu; Guang-Ying Chen; Yan-Hui Fu; Wei Xu (Natural Product Research, 2017)

Long-term fertilization increases soil nutrient accumulations but decreases biological activity in navel orange orchards of subtropical China - Song-Ze Wan; Han-Jiao Gu; Qing-Pei Yang; Xiao-Fei Hu; Xiang-Min Fang; Anand Narain Singh; Fu-Sheng Chen (Journal of Soils and Sediments, 2017)

KIFC1 and myosin Va: two motors for acrosomal biogenesis and nuclear shaping during spermiogenesis of Portunus trituberculatus - Dan-Dan Ma; Meng-Ying Pan; Cong-Cong Hou; Fu-Qing Tan; Wan-Xi Yang (Cell and Tissue Research, 2017)

Field testing of the surface electromagnetic prospecting system - Qing-Yun Di; Chang-Min Fu; Zhi-Guo An; Cheng Xu; Ya-Lu Wang; Zhong-Xing Wang (Applied Geophysics, 2017)

Lateral dynamic response of a partially embedded pile subjected to combined loads in saturated soil - An-Feng Hu; Peng Fu; Chang-Qing Xia; Kang-He Xie (Marine Georesources & Geotechnology, 2017)

Molecular cloning, characterization, and promoter analysis of the isochorismate synthase (AaICS1) gene from Artemisia annua - Lu-yao Wang; Ying Zhang; Xue-qing Fu; Ting-ting Zhang; Jia-wei Ma; Li-da Zhang; Hong-mei Qian; Ke-xuan Tang; Shan Li; Jing-ya Zhao (Journal of Zhejiang University-SCIENCE B, 2017)

A new monoterpenoid indole alkaloid from Ochrosia elliptica - A-Hong Chen; Qing-Long Liu; Yan-Lei Ma; Zhi-Hua Jiang; Jin-Ying Tang; Yan-Ping Liu; Guang-Ying Chen; Yan-Hui Fu; Wei Xu (Natural Product Research, 2017)

Deletion of mammalian sterile 20-like kinase 1 attenuates neuronal loss and improves locomotor function in a mouse model of spinal cord trauma - Pan-feng Wang; Da-yuan Xu; Yuntong Zhang; Xiao-bin Liu; Yan Xia; Pan-yu Zhou; Qing-ge Fu; Shuo-gui Xu (Molecular and Cellular Biochemistry, 2017)

CDK inhibitor SU9516 induces tetraploid blastocyst formation from parthenogenetically activated porcine embryos - Qing Guo; Long Jin; Hai-Ying Zhu; Xiao-Chen Li; Yu-Chen Zhang; Xiao-Xu Xing; Guang-Lei Zhang; Mei-Fu Xuan; Qi-Rong Luo; Zhao-Bo Luo; Jun-Xia Wang; Jin-Dan Kang; et al. (Biotechnology Letters, 2017)

Phylogeny and biogeography of the genus Cephalenchus (Tylenchomorpha, Nematoda) - Tiago J. Pereira; Xue Qing; Kuei‐Fu Chang; Manuel Mundo‐Ocampo; Juvenil E. Cares; Erik J. Ragsdale; Chau N. Nguyen; James G. Baldwin (Zoologica Scripta, 2017)
The phylogenetic position of Cephalenchus is enigmatic with respect to other tylench nematodes. In this study, Cephalenchus populations representing 11 nominal species were sampled worldwide for molecular and morphological characterization. Species identification was based on light microscopy ( LM ) and scanning electron microscopy ( SEM ). Molecular analyses were based on the genes (i.e. 18S, 28S, 5.8S) and internal transcribed spacers ( ITS ‐1 and ITS ‐2) of the ribosomal RNA ( rRNA ). Phylogenetic analyses (i.e. full and reduced alignments) of either concatenated or single genes always supported the monophyly of Cephalenchus . A sister relationship between Cephalenchus and Eutylenchus excretorius was recovered by most analyses, although branch support varies depending on the dataset used. The position of Cephalenchus + E. excretorius within Tylenchomorpha nevertheless remains ambiguous, thus highlighting the importance of sampling additional genes as well as taxa. Placement of Cephalenchus + E. excretorius as sister of Tylenchinae or Boleodorinae could not be rejected on the basis of 18S and 28S rRNA genes. Within Cephalenchus , amphidial opening morphology shows congruence with molecular‐based phylogenetic relationships, whereas the number of lines in the lateral field is likely to be a convergent trait. Morphometric analyses clearly distinguished short tail from medium–long tail species, and SEM observations seem to suggest a relation between tail length and amphidial opening. In addition, molecular phylogenies support the non‐monophyly of Cephalenchus cephalodiscus , Cephalenchus cylindricus , Cephalenchus daisuce and Cephalenchus leptus . The known extent of Cephalenchus diversity is increased with the inclusion of two new species, and the biogeography of the genus is discussed.

Characterization and speciation of mercury in mosses and lichens from the high-altitude Tibetan Plateau - Jun-juan Shao; Cheng-bin Liu; Qing-hua Zhang; Jian-jie Fu; Rui-qiang Yang; Jian-bo Shi; Yong Cai; Gui-bin Jiang (Environmental Geochemistry and Health, 2017)

A novel non-ATP competitive FGFR1 inhibitor with therapeutic potential on gastric cancer through inhibition of cell proliferation, survival and migration - Jianzhang Wu; Xiaojing Du; Wulan Li; Yangyang Zhou; Encheng Bai; Yanting Kang; Qiuxiang Chen; Weitao Fu; Di Yun; Qing Xu; Peihong Qiu; Rong Jin; et al. (Apoptosis, 2017)

Rapid generation of genetic diversity by multiplex CRISPR/Cas9 genome editing in rice - Lan Shen; Yufeng Hua; Yaping Fu; Jian Li; Qing Liu; Xiaozhen Jiao; Gaowei Xin; Junjie Wang; Xingchun Wang; Changjie Yan; Kejian Wang (Science China Life Sciences, 2017)

Early-Life Social Isolation-Induced Depressive-Like Behavior in Rats Results in Microglial Activation and Neuronal Histone Methylation that Are Mitigated by Minocycline - Hong-Tao Wang; Fu-Lian Huang; Zhao-Lan Hu; Wen-Juan Zhang; Xiao-Qing Qiao; Yan-Qing Huang; Ru-Ping Dai; Fang Li; Chang-Qi Li (Neurotoxicity Research, 2017)

RepSox improves viability and regulates gene expression in rhesus monkey–pig interspecies cloned embryos - Hai-Ying Zhu; Long Jin; Qing Guo; Zhao-Bo Luo; Xiao-Chen Li; Yu-Chen Zhang; Xiao-Xu Xing; Mei-Fu Xuan; Guang-Lei Zhang; Qi-Rong Luo; Jun-Xia Wang; Cheng-Du Cui; et al. (Biotechnology Letters, 2017)

Full-scale field load testing of long drilled shafts with enlarged base constructed in marine sediment - Kai-Fu Liu; Xin-Yu Xie; Zhe Luo; Qing-Hong Hu; Chun-Xia Huang (Marine Georesources & Geotechnology, 2017)

A Missense Variant in TREML2 Reduces Risk of Alzheimer’s Disease in a Han Chinese Population - Teng Jiang; Yu Wan; Jun-Shan Zhou; Meng-Shan Tan; Qing Huang; Xi-Chen Zhu; Huan Lu; Hui-Fu Wang; Qi Chen; Lin Tan; Ying-Dong Zhang; Lan Tan; et al. (Molecular Neurobiology, 2017)

Association of oral endothelin receptor antagonists with risks of cardiovascular events and mortality: meta-analysis of randomized controlled trials - Yu Pan; Chun Hu; Pei Hua Chen; Yan Hong Gu; Qing Yan Qiao; Li Hua Pan; Dong Chi Zhou; Hui Fang Gu; Shun Kun Fu; Hui Min Jin (European Journal of Clinical Pharmacology, 2017)

Joint 3D traveltime calculation based on fast marching method and wavefront construction - Hui Sun; Jian-Guo Sun; Zhang-Qing Sun; Fu-Xing Han; Zhi-Qiang Liu; Ming-Chen Liu; Zheng-Hui Gao; Xiu-Lin Shi (Applied Geophysics, 2017)

Evolution Mechanism and Rainfall Warning Criteria for Maijianwo Slope in Henan Province, China - Yi-heng Pan; Jian-ping Chen; Li-qing Wu; Wei Wang; Fu-lin Tan (Geotechnical and Geological Engineering, 2017)

The developmental competence of oocytes parthenogenetically activated by an electric pulse and anisomycin treatment - Yu-Chen Zhang; Long Jin; Hai-Ying Zhu; Qing Guo; Xiao-Chen Li; Guang-Lei Zhang; Xiao-Xu Xing; Mei-Fu Xuan; Qi-Rong Luo; Zhao-Bo Luo; Jun-Xia Wang; Cheng-Du Cui; et al. (Biotechnology Letters, 2017)

bFGF Protects Against Blood-Brain Barrier Damage Through Junction Protein Regulation via PI3K-Akt-Rac1 Pathway Following Traumatic Brain Injury - Zhou-Guang Wang; Yi Cheng; Xi-Chong Yu; Li-Bing Ye; Qing-Hai Xia; Noah R. Johnson; Xiaojie Wei; Da-Qing Chen; Guodong Cao; Xiao-Bing Fu; Xiao-Kun Li; Hong-Yu Zhang; et al. (Molecular Neurobiology, 2016)

Frequency and type of inheritable mutations induced by γ rays in rice as revealed by whole genome sequencing - Shan Li; Yun-chao Zheng; Hai-rui Cui; Hao-wei Fu; Qing-yao Shu; Jian-zhong Huang (Journal of Zhejiang University-SCIENCE B, 2016)

Subinhibitory concentrations of phloretin repress the virulence of Salmonella typhimurium and protect against Salmonella typhimurium infection - Wu Shuai-Cheng; Fu Ben-Dong; Chu Xiu-Ling; Su Jian-Qing; Fu Yun-Xing; Cui Zhen-Qiang; Xu Dao-Xiu; Wu Zong-Mei (Antonie van Leeuwenhoek, 2016)

MoRad6‐mediated ubiquitination pathways are essential for development and pathogenicity in Magnaporthe oryzae - Huan‐Bin Shi; Guo‐Qing Chen; Ya‐Ping Chen; Bo Dong; Jian‐Ping Lu; Xiao‐Hong Liu; Fu‐Cheng Lin (Environmental Microbiology, 2016)
Summary The ubiquitin system modulates protein functions through targeting substrates for ubiquitination. Here, E2 conjugating enzyme MoRad6‐related ubiquitination pathways are identified and analyzed in Magnaporthe oryzae , the causal agent of rice blast disease. Disruption of MoRad6 leads to severe defects in growth, sporulation, conidial germination, appressorium formation, and plant infection. To depict the functions of MoRad6, three putative ubiquitin ligases, MoRad18, MoBre1 and MoUbr1, are also characterized. Deletion of MoRad18 causes minor phenotypic changes, while MoBre1 is required for growth, conidiation and pathogenicity in M. oryzae . Defects in ΔMobre1 likely resulted from the reduction in di‐ and tri‐methylation level of Histone 3 lysine 4 (H3K4). Notably, MoUbr1 is crucial for conidial adhesion and germination, possibly by degrading components of cAMP/PKA and mitogen‐activated protein kinase (MAPK) Pmk1 signaling pathways via the N‐end rule pathway. Germination failure of ΔMoubr1 conidia could be rescued by elevation of cAMP level or enhanced Pmk1 phosphorylation resulting from further deletion of MoIra1, the M. oryzae homolog of yeast Ira1/2. These reveal vital effects of cAMP/PKA and MAPK Pmk1 signaling on conidial germination in M. oryzae . Altogether, our results suggest that MoRad6‐mediated ubiquitination pathways are essential for the infection‐related development and pathogenicity of M. oryzae .

Haze is a risk factor contributing to the rapid spread of respiratory syncytial virus in children - Qing Ye; Jun-fen Fu; Jian-hua Mao; Shi-qiang Shang (Environmental Science and Pollution Research, 2016)

Antidepressant-like effects of standardized gypenosides: involvement of brain-derived neurotrophic factor signaling in hippocampus - Rong-Hao Mu; Xiao-Yan Fang; Shuang-Shuang Wang; Cheng-Fu Li; Shao-Mei Chen; Xue-Mei Chen; Qing Liu; Yu-Cheng Li; Li-Tao Yi (Psychopharmacology, 2016)

Effect of organic solvent on fungicide toxicity to Sclerotinia sclerotiorum and Botrytis cinerea - Hong-Jie Liang; Xiao-Ming Lu; Zu-Qing Zhu; Fu-Xing Zhu (European Journal of Plant Pathology, 2016)

PCI-24781 can improve in vitro and in vivo developmental capacity of pig somatic cell nuclear transfer embryos - Long Jin; Hai-Ying Zhu; Qing Guo; Xiao-Chen Li; Yu-Chen Zhang; Guang-Lei Zhang; Xiao-Xu Xing; Mei-Fu Xuan; Qi-Rong Luo; Xi-Jun Yin; Jin-Dan Kang (Biotechnology Letters, 2016)

Simulation for the Spatial–Time Characteristics of High Arch Dam - Lichun Zou; Shenghong Chen; Guojin Wang; Shaojun Fu; Xianliang Tang; Qing Xu; Zhiyong Zhao; Weiming Wang; Min Xie; Ji He (Geotechnical and Geological Engineering, 2016)

Suppression of dioxins by S-N inhibitors in pilot-scale experiments - Ming-Xiu Zhan; Jian-Ying Fu; Tong Chen; Xiao-Qing Lin; Xiao-Dong Li; Jian-Hua Yan; Alfons Buekens (Environmental Science and Pollution Research, 2016)

Two new triterpenoid glycosides from the stems of Camellia oleifera Abel - Qing-Wei Yan; Hui-Zheng Fu; Yue-Hua Luo; Guo-Ping Zhou; Kai-Hua Wan; Rui-Jian Zhong (Natural Product Research, 2016)

Degradation of litter quality and decline of soil nitrogen mineralization after moso bamboo (Phyllostachys pubscens) expansion to neighboring broadleaved forest in subtropical China - Qing-ni Song; Ming Ouyang; Qing-pei Yang; Hui Lu; Guang-yao Yang; Fu-sheng Chen; Jian-Min Shi (Plant and Soil, 2016)

Education and Risk of Dementia: Dose-Response Meta-Analysis of Prospective Cohort Studies - Wei Xu; Lan Tan; Hui-Fu Wang; Meng-Shan Tan; Lin Tan; Jie-Qiong Li; Qing-Fei Zhao; Jin-Tai Yu (Molecular Neurobiology, 2016)

The Regulatory Roles of ncRNA Rli60 in Adaptability of Listeria monocytogenes to Environmental Stress and Biofilm Formation - Ye-long Peng; Qing-ling Meng; Jun Qiao; Kun Xie; Cheng Chen; Tian-li Liu; Zheng-xiang Hu; Yu Ma; Xue-peng Cai; Chuang-fu Chen (Current Microbiology, 2016)

Current status and historical variations of phthalate ester (PAE) contamination in the sediments from a large Chinese lake (Lake Chaohu) - Lei Kang; Qing-Mei Wang; Qi-Shuang He; Wei He; Wen-Xiu Liu; Xiang-Zhen Kong; Bin Yang; Chen Yang; Yu-Jiao Jiang; Fu-Liu Xu (Environmental Science and Pollution Research, 2016)

CHD3 chromatin-remodeling factor PICKLE regulates floral transition partially via modulating LEAFY expression at the chromatin level in Arabidopsis - Xing Fu; Chaonan Li; Qing Liang; Yangyang Zhou; Hang He; Liu-Min Fan (Science China Life Sciences, 2016)

Plasma Homocysteine Levels Predict the Risk of Acute Cerebral Infarction in Patients with Carotid Artery Lesions - Wei Wu; Yi Guan; Kan Xu; Xi-Jia Fu; Xiao-Feng Lei; Li-Jian Lei; Zhi-Qing Zhang; Yan Cheng; Yun-Qian Li (Molecular Neurobiology, 2016)

Extraction and speciation analysis of roxarsone and its metabolites from soils with different physicochemical properties - Qing-Long Fu; Jian-Zhou He; Hua Gong; Lee Blaney; Dong-Mei Zhou (Journal of Soils and Sediments, 2016)

One new 19- nor cucurbitane-type triterpenoid from the stems of Momordica charantia - Yong-chao Li; Xin-juan Xu; Jing Yang; Xing-gang Wu; Qing-yun Fu (Natural Product Research, 2016)

Mechanism Underlying the Analgesic Effect Exerted by Endomorphin-1 in the rat Ventrolateral Periaqueductal Gray - Tao Chen; Jing Li; Ban Feng; Rui Hui; Yu-Lin Dong; Fu-Quan Huo; Ting Zhang; Jun-Bin Yin; Jian-Qing Du; Yun-Qing Li (Molecular Neurobiology, 2016)

Microsatellite records for volume 8, issue 1 - Maria Cristina Arias; Stéphane Aulagnier; Erin F. Baerwald; Robert M. R. Barclay; Jacqueline Silva Batista; Rochelle R. Beasley; Rodrigo A. Bezerra; Frédéric Blanc; Eli S. Bridge; Maria Teresa Cabria; Lívia Izabela Caputo; Jie Chen; et al. (Conservation Genetics Resources, 2016)

The potential function of prohibitin during spermatogenesis in Chinese fire-bellied newt Cynops orientalis - Jia-Min Jin; Cong-Cong Hou; Fu-Qing Tan; Wan-Xi Yang (Cell and Tissue Research, 2016)

Gabapentinoid Insensitivity after Repeated Administration is Associated with Down-Regulation of the α2δ-1 Subunit in Rats with Central Post-Stroke Pain Hypersensitivity - Yan Yang; Fei Yang; Fan Yang; Chun-Li Li; Yan Wang; Zhen Li; Yun-Fei Lu; Yao-Qing Yu; Han Fu; Ting He; Wei Sun; Rui-Rui Wang; et al. (Neuroscience Bulletin, 2016)

PGC-1α regulates the cell cycle through ATP and ROS in CH1 cells - Xu-feng Fu; Kun Yao; Xing Du; Yan Li; Xiu-yu Yang; Min Yu; Mei-zhang Li; Qing-hua Cui (Journal of Zhejiang University-SCIENCE B, 2016)

Zircon U–Pb dating constraints on the crustal melting event around 8 Ma in the eastern Himalayan syntaxis - Ji-Yao Tu; Jian-Qing Ji; Jun-Feng Gong; Quan-Ren Yan; Bao-Fu Han (International Geology Review, 2016)

Persistence Parameter: a Reliable Measurement for Behavioral Responses of Medaka (Oryzias latipes) to Environmental Stress - Li Yin; Haitang Yang; Guiyun Si; Qing Ren; Rongshu Fu; Biao Zhang; Xu Zhang; Xiaoguang Wang; Pingping Qi; Chunlei Xia; Zongming Ren; Tae-Soo Chon; et al. (Environmental Modeling & Assessment, 2016)

Cardioprotective Effect of Anisodamine Against Myocardial Ischemia Injury and its Influence on Cardiomyocytes Apoptosis - Kun Xing; Xianghua Fu; Lingling Jiang; Yanbo Wang; Wei Li; Xinshun Gu; Guozhen Hao; Qing Miao; Xiaolin Ge; Yuhong Peng; Wei Geng; Shiru Bai; et al. (Cell Biochemistry and Biophysics, 2015)

Preparation and characterization of heparin hexasaccharide library with N-unsubstituted glucosamine residues - Qun Tao Liang; Jia Yan Du; Qing Fu; Jiang Hui Lin; Zheng Wei (Glycoconjugate Journal, 2015)

Identification and structural elucidation of steroidal saponins from the root of Paris polyphylla by HPLC-ESI-QTOF-MS/MS - Yun Ling; Zhiwen Fu; Qing Zhang; Lingling Xu; Liang Liao (Natural Product Research, 2015)

Isolation and characterization of a crude oil degrading bacteria from formation water: comparative genomic analysis of environmental Ochrobactrum intermedium isolate versus clinical strains - Lu-jun Chai; Xia-wei Jiang; Fan Zhang; Bei-wen Zheng; Fu-chang Shu; Zheng-liang Wang; Qing-feng Cui; Han-ping Dong; Zhong-zhi Zhang; Du-jie Hou; Yue-hui She (Journal of Zhejiang University-SCIENCE B, 2015)

Direct cloning, expression of a thermostable xylanase gene from the metagenomic DNA of cow dung compost and enzymatic production of xylooligosaccharides from corncob - Ming-zhe Sun; Hong-chen Zheng; Ling-cai Meng; Jun-she Sun; Hui Song; Yun-juan Bao; Hai-sheng Pei; Zheng Yan; Xiu-qing Zhang; Jing-sheng Zhang; Yi-han Liu; Fu-ping Lu (Biotechnology Letters, 2015)

Transcriptional Responses in Adult Zebrafish (Danio rerio) Exposed to Propranolol and Metoprolol - Liwei Sun; Fang Liu; Haigang Chen; Sisi Wang; Xia Lin; Jian Chi; Qing Zhu; Zhengwei Fu (Ecotoxicology, 2015)

Reproductive Isolation of Ips nitidus and I. shangrila in Mountain Forests of Western China: Responses to Chiral and Achiral Candidate Pheromone Components - Fredrik Schlyter; Rastislav Jakuš; Fu-Zhong Han; Jian-Hai Ma; Blanka Kalinová; Pavel Mezei; Jiang-Hua Sun; Liana Ujhelyiová; Qing-He Zhang (Journal of Chemical Ecology, 2015)

Associations Between ApoEε4 Carrier Status and Serum BDNF Levels—New Insights into the Molecular Mechanism of ApoEε4 Actions in Alzheimer’s Disease - Yu-Hui Liu; Shu-Sheng Jiao; Ye-Ran Wang; Xian-Le Bu; Xiu-Qing Yao; Yang Xiang; Qing-Hua Wang; Lin Wang; Juan Deng; Jing Li; Xin-Fu Zhou; Hua-Dong Zhou; et al. (Molecular Neurobiology, 2015)

iTRAQ-based quantitative proteomic analysis of longissimus muscle from growing pigs with dietary supplementation of non-starch polysaccharide enzymes - Ji-ze Zhang; Yang Gao; Qing-ping Lu; Ren-na Sa; Hong-fu Zhang (Journal of Zhejiang University-SCIENCE B, 2015)

Polyphenols in Regulation of Redox Signaling and Inflammation During Cardiovascular Diseases - Ling Niu; Xiu-hua He; Qing-wen Wang; Ming-yu Fu; Feng Xu; Ying Xue; Zhen-zhou Wang; Xin-jiang An (Cell Biochemistry and Biophysics, 2015)

Hydrogeochemical and isotopic characteristics of groundwater in the salt chemical industrial base of Guyuan City, northwestern China - Ying Li; Fu Sheng Hu; Zhong Qi Xue; Yan Qing Yu; Ping Wu (Arabian Journal of Geosciences, 2015)

Rifampicin Loaded Mannosylated Cationic Nanostructured Lipid Carriers for Alveolar Macrophage-specific Delivery - Xu Song; Qing Lin; Ling Guo; Yao Fu; Jianfeng Han; Huan Ke; Xun Sun; Tao Gong; Zhirong Zhang (Pharmaceutical Research, 2015)

A comparison of the potential health risk of aluminum and heavy metals in tea leaves and tea infusion of commercially available green tea in Jiangxi, China - Lanhai Li; Qing-Long Fu; Varenyam Achal; Yonglin Liu (Environmental Monitoring and Assessment, 2015)

Optimization of Astragalus membranaceus hairy roots induction and culture conditions for augmentation production of astragalosides - Jiao Jiao; Qing-Yan Gai; Yu-Jie Fu; Wei Ma; Li-Ping Yao; Chen Feng; Xin-Xin Xia (Plant Cell, Tissue and Organ Culture (PCTOC), 2015)

Clinical effect of postconditioning in ST-elevation myocardial infarction patients treated with primary percutaneous coronary intervention: a meta-analysis of randomized controlled trials - Xian-qing Hu; Jian Cheng; Biao Tang; Zhong-heng Zhang; Ke Huang; Yi-ping Yang; Yan-yan Mao; Ming Zhong; Shen-wen Fu (Journal of Zhejiang University-SCIENCE B, 2015)

Interactions between household air pollution and GWAS-identified lung cancer susceptibility markers in the Female Lung Cancer Consortium in Asia (FLCCA) - H. Dean Hosgood; Minsun Song; Chao Agnes Hsiung; Zhihua Yin; Xiao-Ou Shu; Zhaoming Wang; Nilanjan Chatterjee; Wei Zheng; Neil Caporaso; Laurie Burdette; Meredith Yeager; Sonja I. Berndt; et al. (Human Genetics, 2015)

Expression of cytochrome P450 CYP81A6 in rice: tissue specificity, protein subcellular localization, and response to herbicide application - Hai-ping Lu; Martin Edwards; Qi-zhao Wang; Hai-jun Zhao; Hao-wei Fu; Jian-zhong Huang; Angharad Gatehouse; Qing-yao Shu (Journal of Zhejiang University-SCIENCE B, 2015)

Historical development and future perspectives of Environmental Specimen Bank in China: a mini review - Fang Qiu; Xiang-Zhou Meng; Yan-Ling Qiu; Qing-Hui Huang; Ying Liu; Ling-Ling Wu; Qian-Fen Xiao; Ya-Jie Sun; Rui Wang; Yi-Hui Zhou; Zhen-Yang Yu; Da-Qiang Yin; et al. (Environmental Science and Pollution Research, 2015)

The genetic basis of population fecundity prediction across multiple field populations of Nilaparvata lugens - Zhong Xiang Sun; Yi Fan Zhai; Jian Qing Zhang; Kui Kang; Jing Heng Cai; Yonggui Fu; Jie Qi Qiu; Jia Wei Shen; Wen Qing Zhang (Molecular Ecology, 2015)
Identifying the molecular markers for complex quantitative traits in natural populations promises to provide novel insight into genetic mechanisms of adaptation and to aid in forecasting population dynamics. In this study, we investigated single nucleotide polymorphisms ( SNP s) using candidate gene approach from high‐ and low‐fecundity populations of the brown planthopper ( BPH ) Nilaparvata lugens Stål (Hemiptera: Delphacidae) divergently selected for fecundity. We also tested whether the population fecundity can be predicted by a few SNP s. Seven genes ( ACE , fizzy, HMGCR , LpR, Sxl, Vg and VgR ) were inspected for SNP s in N. lugens , which is a serious insect pest of rice. By direct sequencing of the complementary DNA and promoter sequences of these candidate genes, 1033 SNP s were discovered within high‐ and low‐fecundity BPH populations. A panel of 121 candidate SNP s were selected and genotyped in 215 individuals from 2 laboratory populations ( HFP and LFP ) and 3 field populations ( GZP , SGP and ZSP ). Prior to association tests, population structure and linkage disequilibrium ( LD ) among the 3 field populations were analysed. The association results showed that 7 SNP s were significantly associated with population fecundity in BPH . These significant SNP s were used for constructing general liner models with stepwise regression. The best predictive model was composed of 2 SNP s ( ACE ‐862 and VgR ‐816 ) with very good fitting degree. We found that 29% of the phenotypic variation in fecundity could be accounted for by only two markers. Using two laboratory populations and a complete independent field population, the predictive accuracy was 84.35–92.39%. The predictive model provides an efficient molecular method to predict BPH fecundity of field populations and provides novel insights for insect population management.

Distribution of PCDD/Fs in the fly ash and atmospheric air of two typical hazardous waste incinerators in eastern China - Tong Chen; Ming-xiu Zhan; Xiao-qing Lin; Jian-ying Fu; Sheng-yong Lu; Xiao-dong Li (Environmental Science and Pollution Research, 2015)

High correlation between thermotolerance and photosystem II activity in tall fescue - Ke Chen; Xiaoyan Sun; Erick Amombo; Qing Zhu; Zhuangjun Zhao; Liang Chen; Qingguo Xu; Jinmin Fu (Photosynthesis Research, 2014)

Post-stroke pain hypersensitivity induced by experimental thalamic hemorrhage in rats is region-specific and demonstrates limited efficacy of gabapentin - Fei Yang; Han Fu; Yun-Fei Lu; Xiao-Liang Wang; Yan Yang; Fan Yang; Yao-Qing Yu; Wei Sun; Jia-Shuang Wang; Michael Costigan; Jun Chen (Neuroscience Bulletin, 2014)

A down-regulated epi-allele of the genomes uncoupled 4 gene generates a xantha marker trait in rice - Rui-Qing Li; Jian-Zhong Huang; Hai-Jun Zhao; Hao-Wei Fu; You-Fa Li; Guo-Zhen Liu; Qing-Yao Shu (Theoretical and Applied Genetics, 2014)

Similarities and Differences in Gastrointestinal Physiology Between Neonates and Adults: a Physiologically Based Pharmacokinetic Modeling Perspective - Guo Yu; Qing-Shan Zheng; Guo-Fu Li (The AAPS Journal, 2014)

Characteristics of Rocky Basin Structure of Yongshu Reef in the Southern South China Sea - Qing-Shan Meng; Ke-Fu Yu; Ren Wang; Yue Qin; Hou-Zhen Wei; Xin-Zhi Wang (Marine Georesources & Geotechnology, 2014)

Accumulation of FLT3+ CD11c+ dendritic cells in psoriatic lesions and the anti-psoriatic effect of a selective FLT3 inhibitor - Heng-Xiu Yan; Wei-Wei Li; Yan Zhang; Xia-Wei Wei; Li-Xin Fu; Guo-Bo Shen; Tao Yin; Xiu-Ying Li; Hua-Shan Shi; Yang Wan; Qing-Yin Zhang; Jiong Li; et al. (Immunologic Research, 2014)

Expression of bioactive porcine interferon-alpha in Lactobacillus casei - Shi-jie Ma; Kun Li; Xin-Sheng Li; Xiao-Qing Guo; Peng-Fei Fu; Ming-Fan Yang; Hong-Ying Chen (World Journal of Microbiology and Biotechnology, 2014)

Neuroprotective role of BNIP3 under oxidative stress through autophagy in neuroblastoma cells - M. Umer Farooq Awan; Murtaza Hasan; Javed Iqbal; Runhong Lei; Wang Fu Lee; Ma Hong; Hong Qing; Yulin Deng (Molecular Biology Reports, 2014)

Isolation and characterization of microsatellite loci in the Ussuri mamushi (Gloydius ussuriensis) - Rong-Fang Wang; Yan-Qing Wu; Zhe Liu; Yan-Fu Qu (Conservation Genetics Resources, 2014)

Photodegradation of Tri(Chloropropyl) Phosphate Solution by UV/O3 - Xin-Chao Ruan; Xiao Jin; Ze-Yu Yang; Qing-Fu Zeng (Water, Air, & Soil Pollution, 2014)

Isolation and characterization of phosphate-solubilizing bacteria from betel nut (Areca catechu) and their effects on plant growth and phosphorus mobilization in tropical soils - Fu-Ping Liu; Hai-Qing Liu; Hai-Long Zhou; Zhi-Guo Dong; Xu-Hao Bai; Peng Bai; Jian-Jun Qiao (Biology and Fertility of Soils, 2014)

Architecture and development of a multi-stage Baiyun submarine slide complex in the Pearl River Canyon, northern South China Sea - Lei Wang; Shi-Guo Wu; Qing-Ping Li; Da-Wei Wang; Shao-Ying Fu (Geo-Marine Letters, 2014)

Factors determining species displacement of related predatory mite species (Acari: Phytoseiidae) - Tetsuo Gotoh; Masumi Hanawa; Sayaka Shimazaki; Natsuki Yokoyama; Chun-Qing Fu; Reo Sugawara; Shuichi Yano (Experimental and Applied Acarology, 2014)

Enhanced methane hydrate storage using sodium dodecyl sulfate and coal - Shu-Qing Hao; Sungho Kim; Yong Qin; Xue-Hai Fu (Environmental Chemistry Letters, 2014)

Genetic diversity and differentiation in the critically endangered orchid (Amitostigma hemipilioides): implications for conservation - Qin Yang; Yan Fu; Yong-qing Wang; Yun Wang; Wen-hua Zhang; Xing-yuan Li; Yong-Quan Reng; Jie Zhang (Plant Systematics and Evolution, 2014)

A survey on the heavy metal contents in Chinese traditional egg products and their potential health risk assessment - Qing-long Fu; Yonglin Liu; Lanhai Li; Varenyam Achal (Food Additives & Contaminants Part B-Surveillance, 2014)

A promoter that drives gene expression preferentially in male transgenic rats - Qiling Li; Yamin Ma; Wenzhi Li; Wei Xu; Li Ma; Guoxing Fu; Xiaohua Tian; Yueling Wang; Xu Li; Tameka Bythwood; Jendai Richards; Mukaila A. Akinbami; et al. (Transgenic Research, 2014)

Physiological and morphological responses to the first bout of refeeding in southern catfish (Silurus meridionalis) - Ling-Qing Zeng; Shi-Jian Fu; Xiu-Ming Li; Feng-Jie Li; Bin Li; Zhen-Dong Cao; Yao-Guang Zhang (Journal of Comparative Physiology B, 2014)

Effects of practical dietary protein to lipid levels on growth, digestive enzyme activities and body composition of juvenile rice field eel (Monopterus albus) - Xiao Ma; Yi Hu; Xiao-Qing Wang; Qing-Hui Ai; Zhi-Gang He; Fu-Xian Feng; Xiang-Yang Lu (Aquaculture International, 2014)

Primordial follicle assembly was regulated by notch signaling pathway in the mice - Chun-Lei Chen; Xia-Fei Fu; Lin-Qing Wang; Jun-Jie Wang; Hua-Gang Ma; Shun-Feng Cheng; Zhu-Mei Hou; Jin-Mei Ma; Guo-Bo Quan; Wei Shen; Lan Li (Molecular Biology Reports, 2014)

Next generation sequencing-based molecular diagnosis of retinitis pigmentosa: identification of a novel genotype-phenotype correlation and clinical refinements - Feng Wang; Hui Wang; Han-Fang Tuan; Duy H. Nguyen; Vincent Sun; Vafa Keser; Sara J. Bowne; Lori S. Sullivan; Hongrong Luo; Ling Zhao; Xia Wang; Jacques E. Zaneveld; et al. (Human Genetics, 2014)

Variation of major minerals and trace elements in seeds of tartary buckwheat (Fagopyrum tataricum Gaertn.) - Xiao-Yan Huang; Friedrich J. Zeller; Kai-Feng Huang; Tao-Xiong Shi; Qing-Fu Chen (Genetic Resources and Crop Evolution, 2014)

Microsatellite primer development for the king ratsnakes Elaphe carinata (Colubridae) - Yan-Qing Wu; Rong-Fang Wang; Long-Hui Lin; Yan-Fu Qu (Conservation Genetics Resources, 2014)

Research on global change scientific satellites - HuaDong Guo; WenXue Fu; XinWu Li; Pei Chen; Guang Liu; Zhen Li; Cheng Wang; Qing Dong; LiPing Lei; LinYan Bai; QingJie Liu (Science China Earth Sciences, 2014)

Establishment and characterization of dairy cow growth hormone secreting anterior pituitary cell model - Jian-Fa Wang; Shou-Peng Fu; Su-Nan Li; Zhan-Qing Yang; Wen-Jing Xue; Zhi-Qiang Li; Wei Wang; Ju-Xiong Liu (In Vitro Cellular & Developmental Biology - Animal, 2014)

Monitoring of non-destructive sampling strategies to assess the exposure of avian species in Jiangsu Province, China to heavy metals - Jie Fu; Qing Wang; Hui Wang; Hongxia Yu; Xiaowei Zhang (Environmental Science and Pollution Research, 2014)

Charlson comorbidity index helps predict the risk of mortality for patients with type 2 diabetic nephropathy - You-Qun Huang; Rong Gou; Yong-Shu Diao; Qing-Hua Yin; Wen-Xing Fan; Ya-Ping Liang; Yi Chen; Min Wu; Li Zang; Ling Li; Jing Zang; Lu Cheng; et al. (Journal of Zhejiang University-SCIENCE B, 2014)

Organochlorine pesticides in the dust fall around Lake Chaohu, the fifth largest lake in China - Hui-Ling Ouyang; Qing-Mei Wang; Wei He; Ning Qin; Xiang-Zhen Kong; Wen-Xiu Liu; Qi-Shuang He; Yu-Jiao Jiang; Chen Yang; Bin Yang; Fu-Liu Xu (Environmental Monitoring and Assessment, 2014)

Assessment of landscape patterns affecting land surface temperature in different biophysical gradients in Shenzhen, China - Miaomiao Xie; Yanglin Wang; Qing Chang; Meichen Fu; Minting Ye (Urban Ecosystems, 2013)

Characterization of OsMIK in a rice mutant with reduced phytate content reveals an insertion of a rearranged retrotransposon - Hai-Jun Zhao; Hai-Rui Cui; Xiu-Hong Xu; Yuan-Yuan Tan; Jun-Jie Fu; Guo-Zhen Liu; Yves Poirier; Qing-Yao Shu (Theoretical and Applied Genetics, 2013)

Molecular characterization and expression analysis of a KIFC1-like kinesin gene in the testis of Eumeces chinensis - Jian-Rao Hu; Mei Liu; Da-Hui Wang; Yan-Jun Hu; Fu-Qing Tan; Wan-Xi Yang (Molecular Biology Reports, 2013)

Improvement of fluorescent chromosome in situ PCR and its application in the phylogeny of the genus Fagopyrum Mill. using nuclear genes of chloroplast origin (cpDNA) - Fen-Long Li; Friedrich J. Zeller; Kai-Feng Huang; Tao-Xiong Shi; Qing-Fu Chen (Plant Systematics and Evolution, 2013)

Regulation of paracellular permeability: factors and mechanisms - Yan-Jun Hu; Yi-Dong Wang; Fu-Qing Tan; Wan-Xi Yang (Molecular Biology Reports, 2013)

An exploratory analysis of vegetation strategies to reduce shallow landslide activity on loess hillslopes, Northeast Qinghai-Tibet Plateau, China - Xia-song Hu; Gary Brierley; Hai-li Zhu; Guo-rong Li; Jiang-tao Fu; Xiao-qing Mao; Qin-qin Yu; Na Qiao (Journal of Mountain Science, 2013)
Heavy summer rainfall induces significant soil erosion and shallow landslide activity on the loess hillslopes of the Xining Basin at the northeast margin of the Qinghai-Tibet Plateau. This study examines the mechanical effects of five native shrubs that can be used to reduce shallow landslide activity. We measured single root tensile resistance and shear resistance, root anatomical structure and direct shear and triaxial shear for soil without roots and five rootsoil composite systems. Results show that Atriplex canescens (Pursh) Nutt. possessed the strongest roots, followed by Caragana korshinskii Kom., Zygophyllum xanthoxylon (Bunge) Maxim., Nitraria tangutorum Bobr. and Lycium chinense Mill. Single root strength and shear resistance relationships with root diameter are characterized by power or exponential relations, consistent with the Mohr-Coulomb law. Root mechanical strength reflects their anatomical structure, especially the percentage of phloem and xylem cells, and the degree and speed of periderm lignifications. The cohesion force of root-soil composite systems is notably higher than that of soil without roots, with increasing amplitudes of cohesion force for A. canescens , C. korshinskii , Z. xanthoxylon , N. tangutorum and L. chinense of 75.9%, 75.1%, 36.2%, 24.6% and 17.0 % respectively. When subjected to shear forces, the soil without root samples show much greater lateral deformation than the root-soil composite systems, reflecting the restraining effects of roots. Findings from this paper indicate that efforts to reduce shallow landslides in this region by enhancing root reinforcement will be achieved most effectively using A. canescens and C. korshinskii .

Investigation of the relationship between chromobox homolog 8 and nucleus pulposus cells degeneration in rat intervertebral disc - Xu Zhou; Hai-Long Zhang; Guang-Fei Gu; Yue Ding; Jian-Bo Jia; Qing-Song Fu; Shi-Sheng He (In Vitro Cellular & Developmental Biology - Animal, 2013)

Water–gas exchange of organochlorine pesticides at Lake Chaohu, a large Chinese lake - Hui-Ling Ouyang; Wei He; Ning Qin; Xiang-Zhen Kong; Wen-Xiu Liu; Qi-Shuang He; Chen Yang; Yu-Jiao Jiang; Qing-Mei Wang; Bin Yang; Fu-Liu Xu (Environmental Science and Pollution Research, 2013)

The flavonoid content in leaves and inflorescences of the wild perennial Fagopyrum cymosum complex - Na Liu; Friedrich Josef Zeller; Qing-Fu Chen (Genetic Resources and Crop Evolution, 2013)

Flexible change and cooperation between mitochondrial electron transport and cytosolic glycolysis as the basis for chilling tolerance in tomato plants - Kai Shi; Li-Jun Fu; Shuai Zhang; Xin Li; Yang-Wen-Ke Liao; Xiao-Jian Xia; Yan-Hong Zhou; Rong-Qing Wang; Zhi-Xiang Chen; Jing-Quan Yu (Planta, 2013)

An in vivo molecular imaging probe 18F-Annexin B1 for apoptosis detection by PET/CT: preparation and preliminary evaluation - Ming-Wei Wang; Fang Wang; Yu-Jia Zheng; Ying-Jian Zhang; Yong-Ping Zhang; Qing Zhao; Clifton Kwang-Fu Shen; Yue Wang; Shu-Han Sun (Apoptosis, 2013)

Photodegradation of Tri (2-chloroethyl) Phosphate in Aqueous Solution by UV/H2O2 - Xin-Chao Ruan; Rui Ai; Xiao Jin; Qing-Fu Zeng; Ze-Yu Yang (Water, Air, & Soil Pollution, 2013)

Tissue concentrations, bioaccumulation, and biomagnification of synthetic musks in freshwater fish from Taihu Lake, China - Xiaolan Zhang; Qing Xu; Shoukuan Man; Xiangying Zeng; Yingxin Yu; Yuping Pang; Guoying Sheng; Jiamo Fu (Environmental Science and Pollution Research, 2013)

A comparison of the ultrastructure and composition of fruits’ cuticular wax from the wild-type ‘Newhall’ navel orange (Citrus sinensis [L.] Osbeck cv. Newhall) and its glossy mutant - De-Chun Liu; Qiong Zeng; Qing-Xun Ji; Chuan-Fu Liu; Shan-Bei Liu; Yong Liu (Plant Cell Reports, 2012)

Tetrodotoxin attenuates isoproterenol-induced hypertrophy in H9c2 rat cardiac myocytes - Ming-Zi Chen; Qing-Ting Bu; Shu-Chao Pang; Feng-Lan Li; Mei-Na Sun; Er-Fu Chu; Hui Li (Molecular and Cellular Biochemistry, 2012)

Protective effect of rat pancreatic progenitors cells expressing Pdx1 and nestin on islets survival and function in vitro and in vivo - Shu-yan Zhou; Yu-sen Zhang; Qing Li; Yi Zhang; Hui Qi; Han-xin Zhou; Chun-yan Deng; Fu-rong Li (Journal of Physiology and Biochemistry, 2012)

Efficacy of endosulfan and fipronil and joint toxic action of endosulfan mixtures against Leptinotarsa decemlineata (Say) - Xiao-qin Shi; Man-Hui Xiong; Wei-Hua Jiang; Zhi-Tian Wang; Wen-Chao Guo; Zhen-Han Xia; Wen-Jun Fu; Guo-Qing Li (Journal of Pest Science, 2012)

Identification and characterization of the soybean IPK1 ortholog of a low phytic acid mutant reveals an exon-excluding splice-site mutation - Feng-Jie Yuan; Dan-Hua Zhu; Yuan-Yuan Tan; De-Kun Dong; Xu-Jun Fu; Shen-Long Zhu; Bai-Quan Li; Qing-Yao Shu (Theoretical and Applied Genetics, 2012)

Erratum to: Validation of reference genes for real-time quantitative PCR normalization in soybean developmental and germinating seeds - Qing Li; Cheng-Ming Fan; Xiao-Mei Zhang; Yong-Fu Fu (Plant Cell Reports, 2012)

Validation of reference genes for real-time quantitative PCR normalization in soybean developmental and germinating seeds - Qing Li; Cheng-Ming Fan; Xiao-Mei Zhang; Yong-Fu Fu (Plant Cell Reports, 2012)

Effect of feeding on the function and structure of the digestive system in juvenile southern catfish (Silurus meridionalis Chen) - Ling-Qing Zeng; Feng-Jie Li; Shi-Jian Fu; Zhen-Dong Cao; Yao-Guang Zhang (Fish Physiology and Biochemistry, 2012)

Performance of Agasicles hygrophila (Coleoptera: Chrysomelidae), a biological control agent of invasive alligator weed, at low non-freezing temperatures - Jian-Ying Guo; Jian-Wei Fu; Xiao-Qing Xian; Ming-Yong Ma; Fang-Hao Wan (Biological Invasions, 2012)

Genetic variant in TP63 on locus 3q28 is associated with risk of lung adenocarcinoma among never-smoking females in Asia - H. Dean Hosgood; Wen-Chang Wang; Yun-Chul Hong; Jiu-Cun Wang; Kexin Chen; I-Shou Chang; Chien-Jen Chen; Daru Lu; Zhihua Yin; Chen Wu; Wei Zheng; Biyun Qian; et al. (Human Genetics, 2012)

Biodegradation of bensulfuron-methyl and its effect on bacterial community in paddy soils - Xiao-Yan Lin; Yu-Yi Yang; Yu-Hua Zhao; Qing-Lin Fu (Ecotoxicology, 2012)

The heterogeneity of Meiyu rainfall over Yangtze–Huaihe River valley and its relationship with oceanic surface heating and intraseasonal variability - Dan-Qing Huang; Yong-Fu Qian; Jian Zhu (Theoretical and Applied Climatology, 2012)

Analysis of 2,297 expressed sequence tags (ESTs) from a cDNA library of flax (Linum ustitatissimum L.) bark tissue - Song-Hua Long; Xin Deng; Yu-Fu Wang; Xiang Li; Rui-Qing Qiao; Cai-Sheng Qiu; Yuan Guo; Dong-Mei Hao; Wan-Qi Jia; Xin-Bo Chen (Molecular Biology Reports, 2012)

Molecular characterization of a KIF3B-like kinesin gene in the testis of Octopus tankahkeei (Cephalopoda, Octopus) - Ran Dang; Jun-Quan Zhu; Fu-Qing Tan; Wei Wang; Hong Zhou; Wan-Xi Yang (Molecular Biology Reports, 2012)

Molecular characterization of a KIF3A-like kinesin gene in the testis of the Chinese fire-bellied newt Cynops orientalis - Jian-Rao Hu; Na Xu; Fu-Qing Tan; Da-Hui Wang; Mei Liu; Wan-Xi Yang (Molecular Biology Reports, 2012)

Construction and characterization of a normalized cDNA library from the river snail Bellamya aeruginosa after exposure to copper - Zi-Cheng Li; Li-Hui An; Qing Fu; Ying Liu; Lei Zhang; Hao Chen; Xing-Ru Zhao; Li-Jing Wang; Bing-Hui Zheng; Lin-Bo Zhang (Ecotoxicology, 2012)

Three-dimensional evaluation of upper anterior alveolar bone dehiscence after incisor retraction and intrusion in adult patients with bimaxillary protrusion malocclusion - Qing-yuan Guo; Shi-jie Zhang; Hong Liu; Chun-ling Wang; Fu-lan Wei; Tao Lv; Na-na Wang; Dong-xu Liu (Journal of Zhejiang University-SCIENCE B, 2011)

A new bioorganic fertilizer can effectively control banana wilt by strong colonization with Bacillus subtilis N11 - Nan Zhang; Kai Wu; Xin He; Shu-qing Li; Zhen-hua Zhang; Biao Shen; Xing-ming Yang; Rui-fu Zhang; Qi-wei Huang; Qi-rong Shen (Plant and Soil, 2011)

Polycyclic aromatic hydrocarbons in surface sediments of the Jialu River - Jie Fu; Sheng Sheng; Teng Wen; Zhi-Ming Zhang; Qing Wang; Qiu-Xiang Hu; Qing-Shan Li; Shu-Qing An; Hai-Liang Zhu (Ecotoxicology, 2011)

Medium and coarsely crystalline dolomites in the Middle Devonian Ratner Formation, southern Saskatchewan, Canada: origin and pore evolution - Qilong Fu; Hairuo Qing (Carbonates and Evaporites, 2011)

Induction of lactadherin mediates the apoptosis of endothelial cells in response to advanced glycation end products and protective effects of grape seed procyanidin B2 and resveratrol - Bao-ying Li; Xiao-li Li; Qian Cai; Hai-qing Gao; Mei Cheng; Jian-hua Zhang; Jun-fu Wang; Fei Yu; Rui-hai Zhou (Apoptosis, 2011)

Identification of annexin A1 as a proinvasive and prognostic factor for lung adenocarcinoma - Ying-Fu Liu; Peng-Fei Zhang; Mao-Yu Li; Quo-Qing Li; Zhu-Chu Chen (Clinical & Experimental Metastasis, 2011)

Isolation and characterization of an antimicrobial peptide from bovine hemoglobin α-subunit - Jianhe Hu; Minglu Xu; Bolin Hang; Lan Wang; Qing Wang; Junjie Chen; Tao Song; Dengfeng Fu; Ziliang Wang; Sanhu Wang; Xingyou Liu (World Journal of Microbiology and Biotechnology, 2011)

Water resources planning and management based on system dynamics: a case study of Yulin city - Xiao-jun Wang; Jian-yun Zhang; Jiu-fu Liu; Guo-qing Wang; Rui-min He; Amgad Elmahdi; Sondoss Elsawah (Environment, Development and Sustainability, 2011)

Enrichment of cardiac differentiation of mouse embryonic stem cells by optimizing the hanging drop method - Ming Chen; Yong-Qing Lin; Shuang-Lun Xie; Hong-Fu Wu; Jing-Feng Wang (Biotechnology Letters, 2011)

Analyzing coastal wetland change in the Yancheng National Nature Reserve, China - Chang-Qing Ke; Dong Zhang; Fu-Qiang Wang; Shu-Xing Chen; Christance Schmullius; Wolfgang-Martin Boerner; Hui Wang (Regional Environmental Change, 2011)

Significant association of SNP rs2106261 in the ZFHX3 gene with atrial fibrillation in a Chinese Han GeneID population - Cong Li; Fan Wang; Yanzong Yang; Fenfen Fu; Chengqi Xu; Lisong Shi; Sisi Li; Yunlong Xia; Gang Wu; Xiang Cheng; Hui Liu; Chuchu Wang; et al. (Human Genetics, 2011)

Important Role of Catalase in the Production of β-carotene by Recombinant Saccharomyces cerevisiae under H2O2 Stress - Guo-liang Yan; Heng-yu Liang; Zhi-qun Wang; Xiao-fan Yang; Dan Liu; Jin-fu Liu; Chang-qing Duan (Current Microbiology, 2011)

Silencing USP22 by asymmetric structure of interfering RNA inhibits proliferation and induces cell cycle arrest in bladder cancer cells - Lei Lv; Xing-yuan Xiao; Zhao-hui Gu; Fu-qing Zeng; Lu-qi Huang; Guo-song Jiang (Molecular and Cellular Biochemistry, 2011)

Effect of temperature on excess post-exercise oxygen consumption in juvenile southern catfish (Silurus meridionalis Chen) following exhaustive exercise - Ling-Qing Zeng; Yao-Guang Zhang; Zhen-Dong Cao; Shi-Jian Fu (Fish Physiology and Biochemistry, 2010)

Short exposure to paclitaxel induces multipolar spindle formation and aneuploidy through promotion of acentrosomal pole assembly - MingLei Bian; JingYan Fu; Yan Yan; Qiang Chen; Chao Yang; QingHua Shi; Qing Jiang; ChuanMao Zhang (Science China Life Sciences, 2010)

Involvement of recF in 254 nm Ultraviolet Radiation Resistance in Deinococcus radiodurans and Escherichia coli - Xiaosong Chang; Lan Yang; Qing Zhao; Wenjuan Fu; Hao Chen; Zhiqun Qiu; Ji-an Chen; Ran Hu; Weiqun Shu (Current Microbiology, 2010)

Endemic Seed Plant Species from Hainan Island: A Checklist - Javier Francisco-Ortega; Fa-Guo Wang; Zhong-Sheng Wang; Fu-Wu Xing; Hong Liu; Han Xu; Wei-Xiang Xu; Yi-Bo Luo; Xi-Qiang Song; Stephan Gale; David E. Boufford; Mike Maunder; et al. (The Botanical Review, 2010)

Seed Plant Endemism on Hainan Island: A Framework for Conservation Actions - Javier Francisco-Ortega; Zhong-Sheng Wang; Fa-Guo Wang; Fu-Wu Xing; Hong Liu; Han Xu; Wei-Xiang Xu; Yi-Bo Luo; Xi-Qiang Song; Stephan Gale; David E. Boufford; Mike Maunder; et al. (The Botanical Review, 2010)

Genetic analysis and characterization of a new maize association mapping panel for quantitative trait loci dissection - Xiaohong Yang; Jianbing Yan; Trushar Shah; Marilyn L. Warburton; Qing Li; Lin Li; Yufeng Gao; Yuchao Chai; Zhiyuan Fu; Yi Zhou; Shutu Xu; Guanghong Bai; et al. (Theoretical and Applied Genetics, 2010)

The efficacy of FMD vaccine reduced non-structural proteins with a mAb against 3B protein - Dong Li; Zai-Xin Liu; Pu Sun; Yong-Liang Li; Zeng-Jun Lu; Mei-Na Tian; Ying-Li Chen; Bao-Xia Xie; Hui-Fang Bao; Yuan-Fang Fu; Yi-Mei Cao; Ping-Hua Li; et al. (Veterinary Research Communications, 2010)

Evaluation of genetic diversity in Lentinula edodes strains using RAPD, ISSR and SRAP markers - Li-Zhong Fu; Hong-Yu Zhang; Xue-Qian Wu; Hai-Bo Li; Hai-Long Wei; Qing-Qi Wu; Li-An Wang (World Journal of Microbiology and Biotechnology, 2010)

Hypoxic training increases metabolic enzyme activity and composition of α-myosin heavy chain isoform in rat ventricular myocardium - Ming-Chun Cai; Qing-Yuan Huang; Wei-Gong Liao; Zhou Wu; Fu-Yu Liu; Yu-Qi Gao (European Journal of Applied Physiology, 2010)

The physiological response and sub-cellular localization of lead and cadmium in Iris pseudacorus L. - Yu-Qing Zhou; Su-Zhen Huang; Shi-Long Yu; Ji-Guang Gu; Jiu-Zhou Zhao; Yu-Lin Han; Jia-Jia Fu (Ecotoxicology, 2010)

Digenean parasites of Chinese marine fishes: a list of species, hosts and geographical distribution - Sheng-fa Liu; Wen-feng Peng; Peng Gao; Ming-jun Fu; Han-zhou Wu; Ming-ke Lu; Ji-qing Gao; Jun Xiao (Systematic Parasitology, 2010)

Combined Effects of Repeated Administration of 2,3,7,8-Tetrachlorodibenzo-p-dioxin and Polychlorinated Biphenyls on Kidneys of Male Rats - Chun-Feng Lu; Yi-Mei Wang; Shuang-Qing Peng; Li-Bo Zou; De-Hong Tan; Gang Liu; Ze Fu; Qiao-Xu Wang; Jing Zhao (Archives of Environmental Contamination and Toxicology, 2009)

Undisturbed Strata Succession Sampling Technology and the Engineering Geological Characteristics of an Atoll in the Southern South China Sea - Qing-Shan Meng; Ren Wang; Ke-Fu Yu; Ming-Jian Hu; Xin-Zhi Wang; Chao Yang (Marine Georesources & Geotechnology, 2009)

A novel multi-stage preculture strategy of Rhizopus oryzae ME-F12 for fumaric acid production in a stirred-tank reactor - Yongqian Fu; Qing Xu; Shuang Li; He Huang; Yao Chen (World Journal of Microbiology and Biotechnology, 2009)

Effects of proteinase a on cultivation and viability characteristics of industrial Saccharomyces cerevisiae WZ65 - Hong-bo Zhang; Hai-feng Zhang; Qi-he Chen; Hui Ruan; Ming-liang Fu; Guo-qing He (Journal of Zhejiang University-SCIENCE B, 2009)

MoFLP1, encoding a novel fungal fasciclin-like protein, is involved in conidiation and pathogenicity in Magnaporthe oryzae - Tong-bao Liu; Guo-qing Chen; Hang Min; Fu-cheng Lin (Journal of Zhejiang University-SCIENCE B, 2009)

Effect of meal size on excess post-exercise oxygen consumption in fishes with different locomotive and digestive performance - Shi-Jian Fu; Ling-Qing Zeng; Xiu-Ming Li; Xu Pang; Zhen-Dong Cao; Jiang-Lan Peng; Yu-Xiang Wang (Journal of Comparative Physiology B, 2009)

Screening of AMP-activated protein kinase α2 subunit interacting proteins by bacterial two-hybrid system - Qing-Ying Fu; Yu-Qi Gao (Molecular Biology Reports, 2009)

Substitutions of 169Lys and 173Thr in nonstructural protein 1 influence the infectivity and pathogenicity of XJ-160 virus - Wu-yang Zhu; Yi-liang Yang; Shi-hong Fu; Li-hua Wang; You-gang Zai; Qing Tang; Guo-dong Liang (Archives of Virology, 2009)

Estrogen receptor expression in adrenocortical carcinoma - Xiao-cao Shen; Cai-xiao Gu; Yi-qing Qiu; Chuan-jun Du; Yan-biao Fu; Jian-jun Wu (Journal of Zhejiang University-SCIENCE B, 2009)

Variation in seed protein subunits among species of the genus Fagopyrum Mill - Jian-Hui Li; Qing-Fu Chen; F. J. Zeller (Plant Systematics and Evolution, 2008)

Construction of recombinant industrial Saccharomyces cerevisiae strain with bglS gene insertion into PEP4 locus by homologous recombination - Qiang Zhang; Qi-he Chen; Ming-liang Fu; Jin-ling Wang; Hong-bo Zhang; Guo-qing He (Journal of Zhejiang University-SCIENCE B, 2008)

Aldehyde volatiles emitted in succession from mechanically damaged leaves of poplar cuttings - Zeng-hui Hu; Ying-bai Shen; You-qing Luo; Fan-yi Shen; Hai-bo Gao; Rong-fu Gao (Journal of Plant Biology, 2008)

Gene transfer into primary cultures of fetal neural stem cells by a recombinant adenovirus carrying the gene for green fluorescent protein - Yong Fu; Shen-qing Wang; Ying-peng Liu; Guo-peng Wang; Jian-ting Wang; Shu-sheng Gong (Journal of Zhejiang University-SCIENCE B, 2008)

Reduced expression of GSTM2 and increased oxidative stress in spontaneously hypertensive rat - Si-Gui Zhou; Ping Wang; Rong-Biao Pi; Jie Gao; Jia-Jia Fu; Jian Fang; Jia Qin; Hui-Jie Zhang; Rui-Fang Li; Shao-Rui Chen; Fu-Tian Tang; Pei-Qing Liu (Molecular and Cellular Biochemistry, 2008)

Generation and characterization of two novel low phytate mutations in soybean (Glycine max L. Merr.) - Feng-Jie Yuan; Hai-Jun Zhao; Xue-Liang Ren; Shen-Long Zhu; Xu-Jun Fu; Qing-Yao Shu (Theoretical and Applied Genetics, 2007)

Analyses of the seed protein contents on the cultivated and wild buckwheat Fagopyrum esculentum resources - Yu-Zhen Guo; Qing-Fu Chen; Lan-Ying Yang; Yun-Hua Huang (Genetic Resources and Crop Evolution, 2007)

Methylenetetrahydrofolate reductase (MTHFR) C677T and A1298C polymorphisms and the risk of primary Hepatocellular Carcinoma (HCC) in a Chinese population - Li-Na Mu; Wei Cao; Zuo-Feng Zhang; Lin Cai; Qing-Wu Jiang; Nai-Chieh You; Binh Yang Goldstein; Guo-Rong Wei; Chuan-Wei Chen; Qing-Yi Lu; Xue-Fu Zhou; Bao-Guo Ding; et al. (Cancer Causes & Control, 2007)

Expression of a grape calcium-dependent protein kinase ACPK1 in Arabidopsis thaliana promotes plant growth and confers abscisic acid-hypersensitivity in germination, postgermination growth, and stomatal movement - Xiang-Chun Yu; Sai-Yong Zhu; Gui-Feng Gao; Xiao-Jing Wang; Rui Zhao; Ke-Qin Zou; Xiao-Fang Wang; Xiao-Yan Zhang; Fu-Qing Wu; Chang-Cao Peng; Da-Peng Zhang (Plant Molecular Biology, 2007)

Localization of vesicular glutamate transporters in the peripheral vestibular system of rat - Yuan Wang; You-Wang Pang; Yu-Lin Dong; Fu-Xing Zhang; Jin-Lian Li; Yun-Qing Li (Neuroscience Bulletin, 2007)

Silver nanoparticles: partial oxidation and antibacterial activities - Chun-Nam Lok; Chi-Ming Ho; Rong Chen; Qing-Yu He; Wing-Yiu Yu; Hongzhe Sun; Paul Kwong-Hang Tam; Jen-Fu Chiu; Chi-Ming Che (JBIC Journal of Biological Inorganic Chemistry, 2007)

The Effect of Plant Growth Regulators and Sucrose on the Micropropagation and Microtuberization of Dioscorea nipponica Makino - Feng-Qing Chen; Yang Fu; De-Li Wang; Xiang Gao; Li Wang (Journal of Plant Growth Regulation, 2007)

Generation and characterization of low phytic acid germplasm in rice (Oryza sativa L.) - Qing-Long Liu; Xiu-Hong Xu; Xue-Liang Ren; Hao-Wei Fu; Dian-Xing Wu; Qing-Yao Shu (Theoretical and Applied Genetics, 2007)

Measurement of soluble solids content in watermelon by Vis/NIR diffuse transmittance technique - Hai-qing Tian; Yi-bin Ying; Hui-shan Lu; Xia-ping Fu; Hai-yan Yu (Journal of Zhejiang University-SCIENCE B, 2007)

Application Fourier transform near infrared spectrometer in rapid estimation of soluble solids content of intact citrus fruits - Hui-shan Lu; Hui-rong Xu; Yi-bin Ying; Xia-ping Fu; Hai-yan Yu; Hai-qing Tian (Journal of Zhejiang University-SCIENCE B, 2006)

Expression and purification of a soluble B lymphocyte stimulator mutant modified with the T-helper cell epitope - Huiguang Gao; Weiling Fu; Rongfen Li; Linfeng Chen; Qing Ji; Li Zhang; Gang Huang; Fengtian He (Biotechnology Letters, 2006)

On the ability of the regional climate model RIEMS to simulate the present climate over Asia - Zhe Xiong; Congbin Fu; Qing Zhang (Advances in Atmospheric Sciences, 2006)

Fine mapping of a quantitative trait locus for grain number per panicle from wild rice (Oryza rufipogon Griff.) - Feng Tian; Zuofeng Zhu; Boshen Zhang; Lubin Tan; Yongcai Fu; Xiangkun Wang; Chuan Qing Sun (Theoretical and Applied Genetics, 2006)

Identification and characterization of piggyBac-like elements in the genome of domesticated silkworm, Bombyx mori - Han-Fu Xu; Qing-You Xia; Chun Liu; Ting-Cai Cheng; Ping Zhao; Jun Duan; Xing-Fu Zha; Shi-Ping Liu (Molecular Genetics and Genomics, 2006)

A Facile Method for Preparation of Polymerizable, Optically Active Ketoprofen Prodrug by Irreversible Lipase-catalysed Resolution - Xiao-Qing Cai; Zhi-Chun Chen; Na Wang; Xian-Fu Lin (World Journal of Microbiology and Biotechnology, 2006)

Heterologous Expression and Purification of Recombinant Allophycocyanin in Marine Streptomyces sp. Isolate M097 - Yan-Hua Hou; Song Qin; You-Xun Li; Fu-Chao Li; Huan-Zhang Xia; Fang-Qing Zhao (World Journal of Microbiology and Biotechnology, 2006)

Construction of introgression lines carrying wild rice (Oryza rufipogon Griff.) segments in cultivated rice (Oryza sativa L.) background and characterization of introgressed segments associated with yield-related traits - Feng Tian; De Jun Li; Qiang Fu; Zuo Feng Zhu; Yong Cai Fu; Xiang Kun Wang; Chuan Qing Sun (Theoretical and Applied Genetics, 2006)

Controllable Regioselective Acylation of Rutin Catalyzed by Enzymes in Non-aqueous Solvents - Yong-mei Xiao; Qi Wu; Wei-bo Wu; Qing-yi Zhang; Xian-fu Lin (Biotechnology Letters, 2005)

Genome-wide Introgression Lines and their Use in Genetic and Molecular Dissection of Complex Phenotypes in Rice (Oryza sativa L.) - Zhi-Kang Li; Bin-Ying Fu; Yong-Ming Gao; Jian-Long Xu; J. Ali; H. R. Lafitte; Yun-Zhu Jiang; J. Domingo Rey; C. H. M. Vijayakumar; R. Maghirang; Tian-Qing Zheng; Ling-Hua Zhu (Plant Molecular Biology, 2005)

Treatment of spinal cord injury with co-grafts of genetically modified schwann cells and fetal spinal cord cell suspension in the rat - Shi -Qing Feng; Xiao -Hong Kong; Shi -Fu Guo; Pei Wang; Li Li; Jin -Hua Zhong; Xin -Fu Zhou (Neurotoxicity Research, 2005)

Glycoprotein-mediated induction of apoptosis limits the spread of attenuated rabies viruses in the central nervous system of mice - Luciana Sarmento; Xia-qing Li; Elizabeth Howerth; Alan C. Jackson; Zhen F. Fu (Journal of NeuroVirology, 2005)

Induced Activity of Superoxide Dismutase and Peroxidase of in vitro Plants by Low Concentrations of Ethanol - Xiu-Qing Li; Shi-Hua Li; De-Fu Chen; Fan-Rui Meng (Plant Cell, Tissue and Organ Culture (PCTOC), 2004)

Role of tumor metastasis suppressor gene KAI1 in digestive tract carcinomas and cancer cells - Qiao Wu; Yuan Ji; Ming-qing Zhang; Yu-qiang Chen; Fu Chen; Da-lin Shi; Zong-hui Zheng; Yao-jian Huang; Wen-jin Su (Cell and Tissue Research, 2003)

Expression and production of bioactive human interleukin-18 in transgenic tobacco plants - Bin Zhang; Ying-Hua Yang; Yong-Ming Lin; Qing Rao; Guo-Guang Zheng; Ke-Fu Wu (Biotechnology Letters, 2003)

Protective effects of adenoviral cardiotrophin-1 gene transfer on rubrospinal neurons after spinal cord injury in adult rats - Zheng-Feng Zhang; Wei-Hong Liao; Qing-Feng Yang; Hong-Yun Li; Ya-Min Wu; Xin-Fu Zhou (Neurotoxicity Research, 2003)

A proteinase inhibitor II of Solanum americanum is expressed in phloem - Zeng-Fu Xu; Wen-Qing Qi; Xue-Zhi Ouyang; Edward Yeung; Mee-Len Chye (Plant Molecular Biology, 2001)

Inheritance of disarticulation derived from some hexaploid brittle rachis wheat - Qing-Fu Chen (Genetic Resources and Crop Evolution, 2001)

Cloning, tissue expression pattern and genomic organization of latexin, a human homologue of rat carboxypeptidase A inhibitor - Qing Liu; Long Yu; Jie Gao; Qiang Fu; Jianxuan Zhang; Pingzhao Zhang; Jian Chen; Shouyuan Zhao (Molecular Biology Reports, 2000)

Molecular Cloning and Tissue Expression Analysis of the β Subunit of Elongation Factor 1 in the Mouse - Qing Liu; Long Yu; Qiang Fu; Tieming Lang; Jianxuan Zhang; Daqin Mao; Shouyuan Zhao (Biochemical Genetics, 2000)

Chromosome location of the gene for the hulled character in the Tibetan weedrace of common wheat - Qing-Fu Chen; Chi Yen; Jun-Liang Yang (Genetic Resources and Crop Evolution, 1999)

Chromosome location of the gene for brittle rachis in the Tibetan weedrace of common wheat - Qing-Fu Chen; Chi Yen; Jun-Liang Yang (Genetic Resources and Crop Evolution, 1998)